Process and hydrocarbon soluble saline hydride catalyst for hydrogen mediated saline hydride initiated anionic chain transfer polymerization, and polymer distribution composition produced therefrom

The hydrogen-mediated salt-like hydride-initiated polymerization using LOXSH catalysts addresses inefficiencies in existing styrene polymerization methods by achieving high-yield, low molecular weight polystyrene with uniform 'head-to-tail' microstructure and reduced impurities.

JP2024178289AInactive Publication Date: 2024-12-24ALBEMARLE CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024161895
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2016-04-08
Filing Date
2024-09-19
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for anionic chain transfer polymerization of styrene result in unfavorable polymer microstructures with high impurity distributions, isomerization, and cleavage steps, leading to undesirable polymer chain lengths and inefficiencies, particularly when using ethylbenzene as a chain transfer agent.

Method used

A hydrogen-mediated salt-like hydride-initiated polymerization process using lithium aminoalkoxide complex salt-like hydride (LOXSH) as a catalyst, which allows for efficient chain transfer and regenerates the hydride catalyst under mild conditions, resulting in a uniform 'head-to-tail' microstructure and low molecular weight polystyrene distribution.

Benefits of technology

The process achieves high yields of low molecular weight polystyrene with minimal impurities and uniform chain lengths, reducing quaternary carbon content and improving the efficiency and control over polymer microstructure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178289000051
    Figure 2024178289000051
  • Figure 2024178289000052
    Figure 2024178289000052
  • Figure 2024178289000053
    Figure 2024178289000053
Patent Text Reader

Abstract

To provide processes for forming hydrogen mediated saline hydride initiated anionic polymer distributions via novel polymerization conditions.SOLUTION: The present invention provides processes wherein molecular hydrogen is a chain transfer agent, and a Lithium Aminoalkoxide Complexed Saline Hydride (LOXSH) forms an anionic polymer chain initiating species by addition of saline hydride to an anionically polymerizable hydrocarbon monomer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for the formation of hydrogen-mediated salt-analog hydride-initiated anionic polymer distributions by novel polymerization conditions in which molecular hydrogen is the chain transfer agent and lithium aminoalkoxide complexed salt-analog hydride (LOXSH) forms the anionic polymer chain initiating species by addition of the salt-analog hydride to an anionically polymerizable hydrocarbon monomer. All of this occurs in a very to highly efficient catalytic cycle in which the kinetic chain length distribution is hydrogen mediated or otherwise dictated by the relative supply of hydrogen to monomer. The present invention further relates to polystyrene compositions with significantly improved microstructure that are free of by-product polymer chain distributions. The present invention also relates to novel hydrocarbon-soluble salt-analog hydride catalysts and reagent compositions useful in carrying out the hydrogen-mediated salt-analog hydride-initiated polymerizations of the present invention. The present invention further relates to a hydrocarbon soluble lithium hydride catalyst and reagent composition formed from dimethylaminoethanol (also known as dimethylethanolamine), an alkyllithium reagent, and molecular hydrogen, which also relates to a method of forming the catalyst, its use in the hydrogen mediated anionic polymerization of styrene (HMAPS), and the resulting low molecular weight polystyrene distributions with low asymmetry and high "head-to-tail" microstructure. [Background technology]

[0002] Low molecular weight, i.e., M w Polystyrene compositions of <<4000 Daltons are polymers They are useful in a variety of applications, both as end uses such as lip agents (see EPO 741147) or as substrate precursors for further synthetic derivatization.

[0003] Such synthetic derivatization involves electrophilic aromatic substitution reactions (see US 8217120B2 "Functionalized styrene oligomers and polymers"). Anionic chain transfer polymerization of polystyrene is economically advantageous in forming low molecular weight polystyrene compositions because it substantially reduces the amount of organolithium and other alkaline earth metal reagents used in forming the chain transfer initiators and catalysts, and it makes cost-effective use of the anionic chain transfer catalyst. Thus, methylbenzene compounds (toluene), polymethylbenzene compounds (xylene, mesitylene, durene, etc.) are excellent chain transfer agents for the production of low molecular weight polystyrene compositions suitable for further synthetic processing. The effectiveness of such methylbenzene chain transfer agents is due in part to the pK of their most acidic carbon-hydrogen bonds. a is at least one order of magnitude smaller than that of the conjugate acid of the poly(styryl) anion (i.e. , more acidic). It has been reported (EPO 741147) or at least suggested that the more complex alkyl-substituted benzene organic chain transfer agents, especially the simplest ethylbenzene (EB), are suitable organic chain transfer agents for producing anionic chain transferred styrene distributions when using a catalyst made from potassium t-butoxide, sec-butyllithium, and N,N,N',N'-tetramethylethylenediamine (TMEDA).

[0004] Alkyl-substituted aromatic hydrocarbon chain transfer agents generally constitute a relatively large percentage of the molecular weight of the anionic chain transfer composition for low molecular weight compositions. For example, the weight average M w For the anionic chain transfer composition having =716, The composition is composed of 12.8% toluene. Similarly, the weight average M w For an anion chain transfer composition having 730, the composition The composition consisted of 14.5% ethylbenzene. It may be desirable to produce low molecular weight polystyrene compositions that are essentially free (containing less than 2 wt. % of the composition) of such organic chain transfer agents. Furthermore, the amount of anionic chain transfer agent, whether organic or inorganic, can be similarly controlled to produce a low molecular weight polystyrene composition that is essentially free (containing less than 2 wt. % of the composition). It may be desirable for the anionic chain transfer process to comprise less than 2 wt% of the polystyrene composition. In the anionic chain transfer process, each and every chain incorporates exactly one organic chain transfer initiator monomer added to the monomer(s) being polymerized. The alkyl-substituted aromatic hydrocarbon has a molecular weight of ≥ 92.14 Daltons, i.e., equal to or greater than the formula weight of toluene. Thus, the smallest M of the anionic chain transfer distribution consisting of ≥ 2 wt% toluene is w is M w It is a purely mathematical fact that the anionic chain transfer composition produced from the higher molecular weight alkyl-substituted aromatic chain transfer agents (e.g., ethylbenzene or xylene) has a minimum M > 4607 Daltons. w Have There is no choice.

[0005] In theory, an anionic chain transfer composition produced from ethylbenzene and styrene has exactly the same structure as an anionically polymerized styrene composition produced from styrene monomer only. However, quite the opposite, it has been found that when ethylbenzene is used as a chain transfer agent under prior art conditions, e.g., in EP O 741 147, such process conditions give a non-uniform microstructured polystyrene composition with additional impurities and impurity distribution (see FIG. 12). Such unfavorable impurities and impurity distributions result from the chain isomerization and cleavage processes (see FIGS. 1 and 2). As a result, the chain length distribution of, e.g., the compositions of the examples of EP O 741 147, is a distribution that, as a whole, contains an unfavorable population of isomeric polymer microstructures, i.e., microstructures that are less favorable for aromatic electrophilic substitution reactions. Such impurities and impurity distributions can be problematic in the further derivatization of such an anionic chain transfer composition. High concentrations of any individual impurity, i.e., amounts of 1000 ppm or more, are unfavorable from the point of view of producing a marketable product. It is therefore desirable to polymerize styrene to produce a low molecular weight polystyrene composition that has significantly reduced, or is essentially free of, undesirable polymer microstructural characteristics or impurity fragments, and which preferably consists solely of polymerized styrene monomer ( / 98 wt%).

[0006] Calculate the wt% ethylbenzene of the anion chain transfer styrene-based reaction distribution of EP O 741 147 (wt%EB=106 / M w *100%), as shown in Table I below. From the experimental details, a comparison of Examples 2-7 of EP 0 741 147 reveals that only Example 4 produced polymeric anionic chain transfer styrenic reaction distributions (ACTSR distributions) with limited width (standard deviation) and small polydispersity. Small changes in the relative feed or loading amounts or both simultaneously reportedly resulted in ACTSR distributions with extremely large standard deviations and with polydispersity that increased significantly, in some cases astronomically (e.g., Examples 2, 3, and 7 of EP 0 741 147). Thus, from such experimental details, it can be seen that the narrow width, i.e., the standard deviation (σ n To produce a small distribution of It can be seen that a very narrow limited process window is provided.

[0007] As shown in Table I below, from the experimental details of EP 0 741 147 A1, A comparison of Examples 2-7 and D in 741 147 reveals that only Example 4 produced anionic chain transfer styrenic reaction distributions (ACTSR distributions) with limited breadth (standard deviation) and small polydispersity. Small changes in the reported relative feed amounts or reagent loadings, or both simultaneously, resulted in ACTSR distributions with extremely large standard deviations and with polydispersity that increased dramatically, in some examples astronomically. Thus, from these experimental details, it is clear that the narrow breadth, i.e., standard deviation σ n To produce a small distribution of It can be seen that the process technology provides a very narrow and limited process window for the production of styrene-based styrene copolymers. This prior art study shows that this process technology suffers from the undesirable production of catalyst compositions that have low or limited solubility in the hydrocarbon reaction medium. It is therefore possible to have catalyst systems that produce low molecular weight styrenic distributions with significantly improved hydrocarbon solubility, improved availability or effectiveness, and a more uniform, if not completely uniform, polymer chain length distribution microstructure. It is desirable. [Table 1]

[0008] As shown in EP 0 741 147 Example D in Table I above, monometallic lithium-based catalyst systems are ineffective or at best extremely inefficient in catalyzing the anionic chain transfer polymerization of styrene with ethylbenzene. Moreover, it is well documented that monometallic TMEDA butyllithium catalyst-forming reagents have poor regioselectivity for the metallation of ethylbenzene. In a paper by Broaddus (Broaddus, CD, J. Org. Chem. 1970, 35, 10.), it is reported that the hydrogen at the alpha position of ethylbenzene produces only 38% benzylic lithium, with ortholithiation occurring at about 9%, metallithiation occurring at about 36%, and paralithiation occurring at about 17%. Thus, this prior art teaches that monometallic lithium catalyst-forming reagents for lithiating ethylbenzene produce many different polymer microstructures that are regioisomeric chain length distributions with respect to the starting ethylbenzene moiety. It would therefore be desirable to have a highly efficient chain transfer polymerization process for styrene in which pathways involving an anionic chain transfer step involving metallization of ethylbenzene (whether the ethylbenzene is added or generated in situ) are reduced, if not eliminated, yet still produce the desired anionic chain transfer distribution chain length microstructure. Such processes which have been realized to date involve a direct one-step hydride addition (e.g., one-step hydrolithiation reaction) to styrene or other styrenic monomers or other vinyl aromatic monomers. Such hydrolithiated monomers should be capable of efficiently initiating the polymerization of more monomers with subsequent chain transfer from molecular hydrogen. Such processes require the hydride catalyst to be consistently and repeatedly regenerated in active form. Thus, such hydrogen-mediated salt-like hydride-initiated polymerization processes should produce more than dimers, and should be able to produce more than 20% of the dimers, with the catalyst amount being 20%. It is characterized by a catalyst efficiency that is reduced by 00% to 10,000%.

[0009] This prior art study (in conjunction with comparative examples 46-48 of WO2010065468A1) shows that this process technology suffers from the unfavourable production of catalyst compositions with low or limited solubility in the hydrocarbon reaction medium. Small changes in reaction loading can therefore result in dramatic changes in product distribution resulting from reduced catalyst availability. The process of EP O 741 147 relies on extremely slow relative feed rates carried out over long feed times (6-18 hours) in an attempt to equilibrate the living and dead polymer chains. The main problem with ethylbenzene as a chain transfer agent is the high pK of ethylbenzene. a is approximately equal to that of the conjugate acid of the poly(styryl) anion. It is still of the same order of magnitude. The following advantages: 1) M n <930, then <7 It would be desirable to have new catalysts and anionic chain transfer polymerization conditions that could provide soluble catalyst compositions that would in turn result in 1) lower molecular weight polystyrene distributions of 0.100 Daltons, 2) more economical reagent utilization, and 3) reduced time with more efficient use and productivity of the polymerization reactor. The hydrogen-mediated salt-like hydride initiation process technology of the present invention does indeed provide such advantages.

[0010] Polymerization of styrene under hydrogen atmosphere is known as Ziegler-Natta polymerization of styrene (Murahashi, S., Nozakura, S., and Utsuhara Y. “Polymerization of Styrene with the Ziegler-Natta Catalysts in the Presence of Molecular Hydrogen.” Bulletin of the Chemical Society of Japan 1960 33 431). In addition, there is at least one report on the metallocene polymerization of styrene under a hydrogen atmosphere (Ref. 14: Tomotsu, N., Kuramoto, M., Takeuchi, M., & Maezawa, H. (1996). Metallocenes 1996, 96, 211.(i) Chien, J. C. W., in Tomotsu, N., et al. “Syndiospecific Polymerization of Styrene.” Journal of Molecular Catalysis A: Chemical 1998 128.1 167.). In both polymerization chemistries, the production of ethylbenzene, a hydrogenation product of styrene, is mentioned. Thus, Utsuhara et al. reported that low molecular weight isotactic polystyrene can be obtained in the presence of hydrogen, but in addition to this, another reaction competing with the polymerization reaction was found, namely the hydrogenation of styrene to ethylbenzene. In both methods for hydrogen-mediated styrene polymerization, i.e. Ziegler-Natta and metallocene catalysis, ethylbenzene is kinetically inactive and shows irrecoverable yield loss.

[0011] Deffieux et al. report that hydrogenolysis of poly(styryl)lithium (1 atm H2 at 50 °C) results in a hydrolysis reaction capable of reinitiating the rather inefficient anionic polymerization of styrene at 100 °C. They reported that this leads to the in situ generation of lithium hydride (Menoret, S., Deffieux, A., & Desbois, P. “Initiation of retarded styrene anionic polymerization using complexes of lithium hydride with “However, slow addition of LiH to styrene for chain propagation leads to incomplete initiation.” Deffieux reports that the addition of additional organometallic Lewis acid reagents (n,sec-Bu2Mg, or BuMgOBT or i-Bu3Al) improves the solubility and reinitiation efficiency of LiH, but the catalytic efficiency is only 50-150%. Furthermore, the bimetallic complexes produced reduce the rate of chain termination and are more efficient at forming the active or Lewis acid forms. The half-lives of the poly(styryl)lithium species range from 40 minutes for uncomplexed poly(styryl)lithium to 10 minutes for the bimetallic complex in cyclohexane and 1.1 atm H2 at 50 °C. The half-life of the living poly(styryl)lithium species is increased significantly to 34 hours for the oxidized poly(styryl)lithium. In fact, they report that 50 atmospheres (about 50 bar) of H2 is required to restore the half-life of the living poly(styryl)lithium species to 50 minutes. Deffieux et al. Lithium chloride is taught to be a potential initiator for the polymerization of styrene: "Lithium hydride is a potential initiator for the anionic polymerization of styrene even in non-polar solvents at least at 100 °C, as long as it is soluble. The efficiency of this initiator is improved by complexation with organometallic derivatives, which firstly ensures its solubility and then slows down the rate of chain propagation of styrene. When n,sec-Bu2Mg is used as an additive, The Li-H bond is not the actual initiation site, and polymerization proceeds after ligand exchange between the two metal atoms." "At high temperatures, H2 acts as a chain transfer agent in the anionic polymerization of styrene. However, However, for efficiency, its concentration in the medium should be high to shift the equilibrium in favor of the production of metal hydrides. This requires high operating pressures of hydrogen." However, Deffieux et al. require complexation of LiH with a Lewis acid, such as a dialkylmagnesium reagent, an aluminum alkyl, and / or an alkylaluminum hydride, to solubilize LiH. Such Lewis acid-complexed LiH reagents so produced are not efficiently reduced once used to initiate styrene polymerization. As a result, such Lewis acid-complexed poly(styryl)lithium chains are not efficiently reduced, nor do their reductions efficiently regenerate highly or superactive LiH initiators.

[0012] Only two highly soluble Group 1 metal hydrides that do not contain Lewis acid complexing agents are known in the literature. (See Stasch, A. and Fohlmeister, L. Aust. J. Chem. 2015, 68, 1190-1201. and Liptrot, DJ, Springer Thesis: Group 2 Mediated Dehydrocoupling, Chapter 2. Group 1-Group 2 Bimetallic Alkyls and Hydrides, Springer International Publishing, 2016, pp. 41-61.) These are: (1) "superaggregates" of the mixture ((t-BuOLi) 16 (LiH) 17 ] photolysis (Thomas, D. et. al., J. Am. Chem Soc. 1997, 119, 11998, and Thomas, D. et. al., Angew. Chem. Int. Ed. 1998, 37, 1537), and (2) Stash's hydrocarbon-soluble LiH complex, [(DipNPPh2)4Li8H4] (Dip, 2,6-iPr2C6H3) (Stasch, A. Angew. Chem. Int. Ed. 2012, 51, 1930). However, this hydrocarbon-soluble LiH reagent is not sufficiently reactive or available to hydrolithiate the highly active species diphenylacetylene or 1,1-diphenylethylene. Thus, one skilled in the art would understand that [(DipNPPh2)4Li8H4] would not hydrolithiate the less active styrenic or other less active vinyl aromatic monomers and, as a consequence, would not initiate polymerization of such monomers. Stash also reports the formation of an "initially clear solution" of LiH / Li(pz) (pz=3,5-di-tert-butyl-1H-pyrazole) that likely turns milky due to the formation of colloidal LiH. Such an "initial clear solution" is prepared by reacting 3,5-di-tert-butyl-1H-pyrazole (pzH) with more than one equivalent of n-butyllithium in an aromatic or aliphatic solvent, followed by conversion of the excess alkyllithium group to a hydride by the addition of phenylsilane or diphenylsilane. Stash is a more sterically complex 3-methylpyrazole with the same synthetic strategy as the LiH / Li(pz) method. The bulky pyrazolate ligand (pz) was used to prepare the first soluble NaH complex [(pz)6Na7H] by reacting [Na(pz)], [Na(nBu)], and diphenylsilane in an aromatic solvent. The same synthetic strategy used to prepare [(pz)6Na7H] was applied to generate the KH hydride analogue, resulting in the formation and isolation of only the crystalline polymer [K(pz)]. Thus, the only reaction between molecular hydrogen, i.e., H2 and Stable aliphatic and / or alicyclic and / or aromatic hydrocarbon soluble monometallic, dimetallic, or polymetallic alkali (Group 1) metal hydrides produced directly from such metals are not heretofore known.

[0013] In their publication (Stasch, A. and Fohlmeister, L. Aust. J. Chem. 2015, 68, 1190-1201), they teach the following additional emphasis: "Well-defined purely Group 1 metal hydride complexes are extremely rare, in fact only known so far for lithium and sodium...Most isolated compounds containing alkali metal and hydridic hydrogen centers are mixed element systems and are best represented as "ate" type complexes, where the strongest interaction of the hydride ligand is with a non-alkali metal center or metalloid...This makes the majority of these "ate" complexes covalent hydride complexes. The most prominent examples in this compound class are probably LiAlH4, NaBH4, and other related commercially available derivatives such as L-selectride®, N-selectride®, and K-selectride® (lithium, sodium, potassium tri-sec-butyl(hydrido)borate), or derivatives with sterically bulky ligands." Thus, the Lewis acid complexed lithium hydride, sodium hydride, and potassium hydride initiators of the prior art (such as those used by Deffieux et al. in their delayed anionic polymerization of styrene) are covalent hydrides and not the salt-like hydride catalysts of the present invention.

[0014] In contrast to covalent hydrides, salt-like hydrides (meaning ionic hydrides) contain hydrogen as a negatively charged ion, i.e., H, in combination with an alkali metal or alkaline earth metal. - It is defined by the presence of salt-like water without Lewis acid complexation. Regarding the addition of halogenides to styrene with simultaneous polymerization, Deffieux et al. (ibid.) provide the following background: "To our knowledge, there are few papers dealing with anionic polymerization of vinyl monomers initiated by metal hydrides. Williams briefly described one styrene polymerization experiment initiated by NaH in hexane at 25 °C. However, the initiation efficiency was extremely low, and the conversion only reached 90% after 3 days."

[0015] Liao et al. reported the formation of highly active alkali metal hydrides with nanometer (≒20 nm) particle size distribution (Liao, S., et.al. Journal of Molecular Catalysis, 1993, 84, 211). In this paper, Liao reported the formation of highly active salt-like hydrides (HASH) from the corresponding alkali metals and hydrogen (1 atm) in THF (40°C) catalyzed by TiCl4 and naphthalene. The complete conversion to the salt-like hydride was achieved by LiH * So, 2 hours, NaH * 4 hours, and KH * It took 28 hours. * indicates a highly or superactive hydride). These nanometer salt-like hydrides have been found to be somewhat useful in the dechlorination and debromination of certain aryl halides. They have also been reported to be active as cocatalysts for the hydrogenation of olefins such as 1-hexene when used with certain transition metal complexes. The transition frequencies range from 0.003 to 45.3 s -1 It has been reported that when used in combination with a transition metal catalyst (1 mol), highly active alkali metal hydrides (50-300 mol) only reduce olefins, and do not polymerize olefins. Even quantification is not disclosed.

[0016] Other applications of nanometer-sized alkali metal hydrides were later reported by Liao et al. (Liao, S., et.al. Synth. Comm. 1997, 27 3977). Such applications include the reduction of the carbonyl carbon of benzaldehyde, methyl benzoate, acrolein, and the methyl and n-butyl esters of acrylic acid to aldehydes and / or alcohols. These reactions were carried out in refluxing THF using a stoichiometric excess of the highly active salt-like hydride, i.e., NaH * or KaH * The reaction was carried out with either NaH * By Acro The reduction of lein (0.3 h) and methyl acrylate (0.25 h) afforded allylic alcohol in 97% and 96% yields, respectively. In another publication, Liao et al. reported that heat-treated nanometer LiH, NaH, and KH complexes with Cp2TiCl2, i.e., CP2TiCl2-MH (M=Li, Na, or K), could be used as catalysts for the hydrogenation of either styrene (M=Li or Na) or octene (M=K). Nanometer KH and CP2TiCl2 did not hydrogenate styrene under 1 atm H2, but instead initiated polymerization and produced a wide range of melting points T=1 60~180℃ Very high molecular weight (MW) polystyrene (M w =200,000) Moreover, nanometric KH alone has been found to polymerize styrene, and one skilled in the art would understand that such high MW anionic polystyrene (APS) compositions result from inefficient initiation and therefore produce very few living polymer chains that rapidly incorporate styrene monomer at the expense of consuming the remaining insoluble nanometric KH.

[0017] Zhang et al. reported a highly active catalyst for hydrogenating styrene (2 ml) in toluene (9 ml) under hydrogen atmosphere at -17°C to 42°C (Zhang, M., et.al. Catal Lett 2008, 124, 146). These highly active catalysts were prepared by using nanometer-sized sodium hydride (20 mg, 8.7×10 -4 ) and 12 different Lewis base-free titanocene complexes (4 × 10 -4 0.5mL of mol / L, i.e. 2 x 10 -7 mol), i.e., NaH * / Ti=4350) was generated. No incorporation of hydrogen was observed in the other two cases where the titanocene complex contained coordinated oxygen (ether) or nitrogen (tertiary amine) species. * Also However, there is no report or reference to any form of styrene polymerization, much less chain transfer chemistry.

[0018] The preparation of superactive, i.e. extremely finely divided, forms of lithium, sodium, and potassium hydrides has been reported by Schleyer et al. (Schleyer, PvR, et.al. J.Org.Chem. 1987. 52, 4299, and Schleyer, PvR, et.al. Angew Chem Int.Ed.Engl. 1986 25 465). The preparation of these superactive salt-like hydrides (SASH) as fine suspensions required the hydrogenation of the corresponding alkali metal alkyls in hexane in the presence of N,N,N',N'-tetramethylethylenediamine (TMEDA). The superactive LiH * The formation of superactive NaH occurs at temperatures between 30°C and 35°C. * is prepared under cryogenic conditions (-10℃ to -15℃) and is a super-active KH * It is grown at -20℃ to -25℃. It was reported that these hydrides could be synthesized. The application of these hydrides to organic synthesis was explored by Schleyer and reported in the open literature articles cited above. Most of these synthetic reactions (metallation, addition, and reduction) were carried out under cryogenic conditions at temperatures as low as -90°C, with a few reactions carried out between room temperature and 50°C. Also, there was no disclosure in Schleyer of the use of these hydrides for styrenic or vinyl polymerizations, let alone for hydrogen mediation of such polymerization processes.

[0019] Harder et al. reported that styrene was initially formed from phenylsilane in a 2.5 mol % Catalytic hydrogenation by organocalcium catalyst [DIPPnacnacCaH THF]2 It has been reported that it can be used in benzene at 20°C and 20 atm H2 for 15 hours (Har der, S., Speilman, J., Buch, F. Angew. Chem. 2008, 120, 9576. Also published in Angew. Chem. Int. Ed. 2008, 47, 9434). This hydrogenation produced ethylbenzene in 85% yield, with styrene dimer as the main component and small amounts of styrene trimer and tetramer oligomers in 15% yield. Harder further reported that 1,1-diphenylethene was reduced at low conversion to 14% Ph2CHCH3 and 7% dimers in benzene at 20 atm H2 in 15 h in a catalyst made from 5 mol% butyllithium / TMEDA complex at 20 °C. For this reaction, the authors report the following: As stated: "The reaction, catalyzed by commercially available nBuLi / TMEDA, proceeded only to low conversions... This is because the heavier alkaline earth metal complexes are more efficient when the H2 pressure is low. This suggests that it is an effective catalyst for

[0020] Tetrahydrofuran-soluble forms of magnesium hydride have been prepared by Ashby et al. from ortho-substituted (2,6-dimethyl and 2,6-diisopropylphenoxide) aryloxymagnesium reagents and activated solid magnesium hydride. Tetrahydrofuran-insoluble forms of magnesium hydride have been obtained from alkoxymagnesium and solid magnesium hydride reagents (see Ashbey, EC, Goel, AB, Lin, JJ Tetrahedron Letters, 1977, 3133). Ashby also reported the production of tetrahydrofuran-soluble dialkylaminomagnesium hydrides from a series of bulky dialkyl and bulky alkyl-substituted cycloalkyl secondary amines by reaction with activated solid magnesium hydride. The activated magnesium hydride was prepared by reduction of dimethylmagnesium with LiAlH4 in diethyl ether. Thus, these bulky dialkyl and bulky alkyl-substituted cycloalkyl secondary amines were reacted with dimethylmagnesium to produce bis(dialkylmagnesium)magnesium compounds which were then reacted with activated magnesium hydrides in THF (see Ashbey, EC, Goel, AB, Lin, JJJ Or. Chem., 1978, 43, 1564. Such aminomagnesium hydrides, if capable of initiating polymerization, may to some extent initiate polymerization by amide addition to the monomer, incorporating undesirable amine functionality into the resulting polymer distribution.

[0021] Michalczyk has reported that in the presence of "suitable ligands" in ether or hydrocarbon solvents, a precipitated form of magnesium hydride, MgH2L x Such suitable ligands include tetrahydrofuran, ethylene glycol dimethyl ether, and TMEDA. The reducing agent used was phenylsilane (see Michalczyk, MJ Organometallics, 1992, 11, 2307). In a recent review entitled "Molecular Early Main Group Metal Hydrides: Synthetic Challenge, Structures and Applications", Harder outlines the state of the art in the controlled synthesis of well-defined Group 1 and Group 2 metal hydrides. In general, such hydrides have been prepared by the methods described above, including: photolysis, "ate complexes", reactions of activated hydrides to produce aryloxymagnesium hydrides and dialkylaminomagnesium hydrides as reported by Ashby, Harder's [DIPPnacnacCaH·THF]2, first produced from phenylsilane, and and phenylsilane. Harder has also reported the formation of a magnesite complex [(iPr2N)3Mg - ]M + (M + =Na + , K+ This paper reviews the many hydrides that are produced from the thermal decomposition of soluble salt-like hydride compositions. A common feature of all methods to generate the product is the use of bulky (usually isopropylated) ligands. ) to achieve solubility. [DIPPnacnacCaH THF]2 In all cases, except for the poorly catalytic species produced during the hydrogenation of styrene to ethylbenzene (85% yield), such as with phenylsilane (which was also produced first from phenylsilane), the salt-like hydride complexes were produced from some other reagent besides molecular hydrogen. Only Scheyer's insoluble form of the superactive salt-like hydride (SASH) was produced directly from molecular hydrogen as the initial reducing agent.

[0022] Thus, the prior art does not disclose the use of lithium aminoalkoxide complex salt-like hydride (LOXSH) species for the anionic chain transfer polymerization of vinyl aromatic monomers, such as styrenic monomers. Indeed, the prior art does not even predict the formation of LOXSH catalysts, particularly as hydrocarbon soluble species, particularly when generated directly from simple, non-bulky ligands, much less H2. The present inventors have surprisingly discovered that these hydrides, as well as the novel hydrides, can be used to catalyze hydrogen-mediated, salt-like hydride-initiated polymerization processes. Thus, the present invention provides an efficient anionic chain transfer polymerization process for vinyl aromatic monomers at mild temperatures (e.g., from about 20° C. to less than 100° C.) where hydrogen is the primary or only chain transfer agent. The process can be carried out at relatively low to very low hydrogen partial pressures. Furthermore, the present inventors have discovered that the novel polymerization catalysts of the present invention provide a low molecular weight anionically polymerized styrene distribution that is essentially, if not completely, free of quaternary carbons in the polymer microstructure, consisting of only styrene ( / 98 wt % styrene) with a unique, uniform, beneficial "head-to-tail" microstructure. Thus, such polystyrene distributions have less than 3.0 wt %, preferably less than 2.0 wt %, and more preferably less than 1.0 wt % of the polymer chains of polystyrene that contain quaternary carbons in the backbone of the polymer chain. Thus, such compositions generally contain less than 1000 ppm, or even less than 200 ppm, or even less than 20 ppm of quaternary carbons.Similarly, the polystyrene compositions of the present invention contain less than 1.0%, preferably less than 0.5%, and most preferably less than 0.1% polymer chain distribution or impurities resulting from cleavage of the desired anionic chain transfer polystyrene distribution.

[0023] Chemical Abbreviations and Value Definitions PTA is an abbreviation for the general class of polytertiary amines used as accelerators, and in the use of "·XPTA", X is a positive number indicating an integer or fractional number of moles of PTA complexed to the catalyst composition.

[0024] TMEDA is an abbreviation for N,N,N',N'-tetramethylethylenediamine, a PTA, and in the use of "·XTMEDA", X is a positive number indicating an integer or fractional number of moles of TMEDA used and / or complexed in the catalyst composition.

[0025] PCAH is an abbreviation for the general class of polar complexing agents used to form the catalysts of the present invention, and represents the polar complexing agent as a neutral alcohol. - The use of The polar complexing agents are represented as alkoxides that have donated one proton to a more basic species. - The use of ] is therefore convenient since the alkoxide is converted from PCAH It indicates that it was generated. - ] x M y H z The use of the formula in the formula is to be interpreted as a neutral catalyst complex or aggregate, and the charge of the metal atom of y is the charge of the metal atom of x [PCA - ] anion The charge is balanced by the combination of z and the hydride ion. [PCA - ] x M y H z The use of is for the entire catalyst formula and not for any potential "ate" complexes, e.g.: [[PCA - ] x M y H z-n ] n+ [[PCA - ] x M y H z+n ] n- It should be understood that this includes:

[0026] DMEAH is the abbreviation for N,N-dimethylethanolamine (synonyms: N,N-dimethyl-2-hydroxyethylamine, N,N-dimethylethanolamine) as a neutral amino alcohol, [DMEA - The use of ] adds one proton to the more basic species. This represents N,N-dimethylethanolamine as the alkoxide.

[0027] DMAEOEH is the abbreviation for 2-N,N-dimethylaminoethoxyethanol (N(CH3)2CH2CH2O-CH2CH2OH) as a neutral amino ether alcohol, [DMAEOE - The use of alkoxides that donate one proton to a more basic species This represents N,N-dimethylaminoethoxyethanol as a dimethylaminoethyl ether.

[0028] MEOEH is the abbreviation for 2-methoxyethanol as a neutral ether alcohol, [MEOE - The use of alkoxides that donate one proton to a more basic species This represents 2-methoxyethanol as a

[0029] Efficiency of the anion chain transfer process (Eff CT ) is the formula: Effect CT .=M n Th / M n exp , where M n Th is the theoretical number average molecular weight, and the term M n exp is an actual experiment or the number average molecular weight obtained in the process. The percent efficiency is obtained by multiplying this efficiency by 100%.

[0030] A summary of the parameters used to describe molecular weight distributions and the equations that define them are given in Table II below (A. Rudin, The Elements of Polymer Science and Engineering, Academic Press, Orlando, 1982, pp. 54-58). Number average DP (DP n ) is M n is calculated using as 100% polystyrene composition. [Table 2] Summary of the Invention

[0031] The hydrogen-mediated salt-analog hydride-initiated polymerization (HMSHIP) process of the present invention is characterized by: a) the novel ability of soluble salt-analog hydride species to rapidly add to vinyl aromatic monomers to generate initiating species, b) the novel high efficiency with which the addition of said salt-analog hydride species to monomers occurs, thus competing with the chain propagation step during the reinitiation step to grow active, transient, living poly(styryl) anionic chains, thus maintaining a constant or nearly constant number of active, growing chains, and c) the ability of chain transfer from hydrogen under mild and novel process conditions to terminate such living poly(styryl) anionic species and regenerate said salt-analog hydride in a form capable of efficiently and effectively resuming the polymerization process. Thus, the present invention relates to a method of carrying out a hydrogen-mediated salt-analog hydride-initiated polymerization, characterized in that one or more anionically polymerizable hydrocarbon monomers are fed to a reaction medium containing a soluble salt-analog hydride catalyst under an atmosphere containing molecular hydrogen. Without such characteristics, the chemical process would produce, on the one hand, mainly reduced mono(styryl) anionic monomers, and, on the other hand, the polymerization would be carried out in a manner that would allow the polymerization process to ... In some embodiments of the invention, the aforementioned features work in concert and in a balanced competitive manner to produce anionic chain transfer polymer distributions with high yields, high efficiency, and exceptional control of polymer chain length microstructure.

[0032] The present invention also relates to an anionic chain transfer polymerization process, which comprises feeding vinyl aromatic monomers and / or preferably styrenic monomers to a reaction mixture in a reaction vessel under an atmosphere containing molecular hydrogen, the reaction mixture comprising (i) an organolithium compound and / or an organomagnesium compound, (ii) optionally a polytertiary amine compound, (iii) a polar complexing agent selected from a tertiary amino alcohol compound, a tertiary amino ether alcohol, an ether alcohol, or a combination thereof, (iv) optionally an alkali metal or metal alloy and / or a solid salt-like hydride and / or a salt-like metal amide, (v) optionally a compound having a pK of at least one C-H covalent bond, a is the pK of toluene a 2.75 pK lower than that of a unit From above, pK of toluenea -4.30pK a (vi) an aromatic hydrocarbon within the range below the unit; (vii) optionally from a vinyl aromatic monomer; a (viii) a hydrocarbon solvent, which may be the same as or different from the aromatic hydrocarbon, having a high solubility in molecular hydrogen and including the catalyst or reagent, the solubility of the hydride is at least about 0.0080 moles per liter.

[0033] The present invention also relates to an anionic chain transfer polymerization process which comprises adding vinyl aromatic monomers and / or preferably styrenic monomers to a reaction mixture having the formula [DMEA - ] x Li y H z (ii) optionally a TMEDA compound; (iii) about x equivalents of dimethylaminoethanol; (iv) optionally ethylbenzene; (v) a hydrogen mediated chain transfer polymerization catalyst having a pK of 100 to 1500 nm; and (vi) about 1000 nm. a and (vi) molecular hydrogen, the amount of hydride produced, z, is given by the formula z=yx, where x, y, and z are positive real integers or fractions greater than zero, which formula further represents an N,N,N',N'-tetramethylethylenediamine (TMEDA) ligand complex, i.e., [DMEA - ] x Li y H z ·XTMEDA, TMEDA, catalyst [DMEA - ] x Li y H z The compound can be contained in a molar ratio X per mole of the compound, where X=0.0001 to about 8.0.

[0034] Accordingly, the present invention also relates to an anionic chain transfer polymerization process comprising: (a) providing styrene monomer to a reaction mixture and / or (b) providing styrene monomer with a reaction mixture in a reaction vessel under an atmosphere containing molecular hydrogen, the reaction mixture being initially treated with (i) about y equivalents of an organolithium compound, (ii) optionally a TMEDA compound, (iii) about x equivalents of dimethylaminoethanol, (iv) optionally ethylbenzene, and (v) a pK of 1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37 a (vi) a hydrocarbon solvent, which may be the same as or different from the aromatic hydrocarbon, optionally produced from molecular hydrogen and having the formula [DMEA - ] x Li y H z of hydrocarbon-soluble lithium hydride is produced, the amount of hydride produced, z, being given by the formula z=yx, where x, y, and z are positive real integers or fractions greater than zero, and the solubility of the hydride constituting the catalyst or reagent is at least about 0.0080 moles per liter.

[0035] The present invention also relates to highly hydrocarbon soluble bimetallic tertiary aminoalkoxide and / or tertiary aminoetheralkoxide and / or etheralkoxide complexed lithium and / or magnesium hydride catalysts and / or reagents comprising: (i) molecular hydrogen; (ii) organolithium and / or organomagnesium compounds; (iii) optionally polytertiary amine compounds; (iv) a polar complexing agent selected from a tertiary aminoalcohol compound, a tertiary aminoether alcohol, an ether alcohol, or a combination thereof; (v) a tertiary aminoether alcohol, a tertiary aminoether alcohol, an ether alcohol, or a combination thereof; ) optionally an alkali metal or metal alloy and / or a solid salt-like hydride and / or a salt-like metal amide, (vi) optionally a pK of at least one C-H covalent bond. a Toluene pK a 2.75 pK lower than that of a From the units, the pK of toluene a -4.30pK a (vii) an aromatic hydrocarbon within the range below the unit, (vii) an optional vinyl aromatic monomer, and (viii) a pKa The solubility of the hydride containing catalyst or reagent is at least about 0.0080 moles per liter.

[0036] The present invention also provides highly hydrocarbon soluble monometallic tertiary aminoalkoxide and / or tertiary aminoether alkoxide and / or ether alkoxide complexed lithium hydrides or lithium polyhydrides (LiH n , n=1+2x, x being a positive integer) complexes and / or With respect to the aggregate, this comprises: (i) molecular hydrogen, (ii) an organolithium compound, (iii) optionally a polytertiary amine compound, (iv) a polar complexing agent selected from a tertiary amino alcohol compound, a tertiary amino ether alcohol, an ether alcohol, or a combination thereof, (v) optionally lithium metal or a lithium alloy and / or a solid lithium hydride and / or a lithium amide, (vi) optionally a pK of at least one C-H covalent bond. a Gato Ruen's pK a The pK of toluene is 2.75 pKa units higher than that of a -4.30pK a Aromatic hydrocarbons within the range below the unit, (vii) pK from H2 a The aromatic carbon The hydride produced from a reaction medium comprising a hydrocarbon solvent, which may be the same as or different from the hydride, and including the catalyst or reagent, has a solubility of at least about 0.0080 moles per liter.

[0037] The present invention also provides a highly hydrocarbon soluble dimethyl ether derivative having the formula [DMEA - ] x Li y H z Lithium tertiary aminoalkoxide complex with lithium hydride (LiH) or lithium polyhydride (LiH n , n=1+2x, x being a positive integer), the catalyst (i) about y equivalents of an organolithium compound and / or an organomagnesium compound, (ii) optionally a TMEDA compound, (iii) about x equivalents of dimethylaminoethanol, (iv) optionally ethylbenzene, (v) a pK a and (vi) molecular hydrogen, the amount of hydride produced, z, is given by the formula z=yx, where x, y, and z are positive real integers or fractions greater than zero, which formula further represents an N,N,N',N'-tetramethylethylenediamine (TMEDA) ligand complex, i.e., [DMEA - ] x Li y H z ·XTMEDA, TMEDA, catalyst [DMEA - ] x Li y H z The compound can be present in a molar ratio X per mole of the compound, where X=0.0001 to about 8.0.

[0038] The present invention also provides highly hydrocarbon soluble tertiary amino alkoxide and / or tertiary amino ether alkoxide and / or ether alkoxide complexed lithium deuteride (Li 2 H), or lithium tritide (Li 3 H), or lithium polydeuteride (Li 2 H n , n = 1 + 2x, x is a positive integer), or polylithium tritide (Li 3 H n , n=1+2x, x being a positive integer) complex and / or which comprises: (i) isotopically enriched molecular hydrogen; (ii) organolithium compounds and / or organomagnesium compounds; (iii) optionally polytertiary amine compounds; (iv) polar complexing agents selected from tertiary amino alcohol compounds, tertiary amino ether alcohols, ether alcohols, or combinations thereof; (v) optionally an alkali metal or metal alloy and / or a solid salt-like hydride and / or a salt-like metal amide; (vi) optionally a complex having a pK of at least one C-H covalent bond. a is the pK of toluenea 2.75 pK lower than that of a From the units, the pK of toluene a -4.30pK a (vii) an aromatic hydrocarbon falling within the range of the units below; and (vii) optionally a vinyl aromatic monomer. - and (viii) pK from H2 a The solubility of the hydride containing catalyst or reagent is at least about 0.0080 moles per liter.

[0039] The present invention further provides highly hydrocarbon soluble lithium tertiary aminoalkoxide complexes of lithium hydride (LiH) or lithium polyhydride (LiH n , n=1+2j, j is zero (positive integer inclusive) complexes and / or aggregates, which comprise: (i) molecular hydrogen, (ii) about y equivalents of an organolithium compound, (iii) optionally TMEDA, (iv) about x equivalents of dimethylaminoethanol, (vi) optionally ethylbenzene, and (vii) a pK greater than H a and a reaction medium containing a hydrocarbon solvent, which may be the same as or different from the ethylbenzene, having a high - ] x Li y H n of hydrocarbon soluble lithium hydride is produced, where the amount of hydride produced, z, is given by the equation z=yx, where x, y, and z are positive real integers greater than zero, and n=z+2j, and the solubility of the hydride containing catalyst or reagent is at least about 0.0080 moles per liter.

[0040] The present invention also relates to a hydrogen-mediated anionic polymerization of styrene (HMAPS) process characterized by: a) the novel ability of soluble lithium hydride to rapidly polymerize styrene; b) the novel high efficiency with which addition of the lithium hydride species to styrene monomer occurs, thus allowing the reinitiation step to compete with the chain propagation step to grow active, transient, living poly(styryl)lithium anionic chains, thus maintaining a constant or near constant active, growing chain; c) the ability of chain transfer from hydrogen under mild and novel process conditions to terminate such living poly(styryl)lithium anionic species and regenerate the soluble lithium hydride in a form capable of efficiently resuming the polymerization process; d) the elimination or near elimination of intramolecular chain transfer steps that lead to the generation of undesirable quaternary carbons in the anionic polystyrene polymer chains; and f) control of MWD is achieved through high relative monomer-to-catalyst feed rates, catalyst concentrations, and hydrogen activities.

[0041] Thus, the present invention also relates to a HMAPS process for anionic chain transfer polymerization, which comprises feeding styrene monomer to a reaction mixture in a reaction vessel under an atmosphere containing H2. The reaction mixture contains a compound having the formula [DMEA - ] x Li y H z (i) about y equivalents of an organolithium compound and / or an organomagnesium compound; (ii) optionally a TMEDA compound; (iii) about x equivalents of dimethylaminoethanol; (iv) optionally ethylbenzene; (v) a pK a and (vi) optionally, molecular hydrogen, wherein the amount of hydride produced, z, is given by the formula z=yx, where x, y, and z are positive real integers or fractions greater than zero, and the solubility of the hydride containing catalyst or reagent is at least about 0.0080 moles per liter.

[0042] The present invention also relates to salt-analog hydride initiated anionic polystyrene and anionic chain transferred polystyrene distributions, the polystyrene chain length distributions of individual or separate polymer chain constituents being represented by the general formula: [ka] wherein n is the number of repeating styrene monomer units covalently bonded between the starting and terminating styrene monomers, and the chain length distribution of the above general formula is at least about 97.0 wt.%, preferably at least about 98.0 wt.%, more preferably at least about 99.0 wt.%, and most preferably at least about 99.2 wt.%, of the total weight of the polystyrene composition. t%, with the remainder of the chain length distribution comprising no more than 3.0 wt.%, or more preferably no more than 2.0 wt.%, more preferably no more than 1.0%, and most preferably no more than 0.8 wt.% and consisting of: 1) a distribution of polymer chains which are isomers of 1, and / or 2) a distribution produced from a chain scission process step, thereby resulting in a distribution of isomers of the formula:

number

[0043] The present invention further relates to lithium hydride initiated anionic polystyrene and anionic chain transferred polystyrene distributions, the polystyrene chain length distributions of individual or separate polymer chain constituents having the general formula 1: i ), i.e.

number

[0044] Glossary It is to be understood and appreciated that the term "polymer" as used anywhere in this specification, including the claims, refers to the term "polymer" as defined in the OECD definition of a "polymer," which is as follows: "A chemical substance consisting of molecules characterized by a sequence of one or more types of monomeric units, including a simple majority by weight of molecules containing at least three monomeric units covalently bonded to at least one other monomeric unit or to other reactants, and less than a simple majority by weight of molecules of the same molecular weight. Such molecules must be distributed over a range of molecular weights whose differences in molecular weight are attributable primarily to differences in the number of monomeric units."

[0045] Salt-like hydrides (meaning ionic hydrides) are compounds that contain hydrogen as a negatively charged ion, i.e., H, in combination with an alkali metal or alkaline earth metal. - The existence of The alkali metals include lithium, sodium, potassium, rubidium, and cesium, and the alkaline earth metals include magnesium and calcium.

[0046] The salt-like metal amides are metal amides or diamides formed from ammonia and / or primary amines and / or secondary amines, in which the metal ions in combination with the amides are alkali metals selected from lithium, sodium, potassium, rubidium, and cesium, and in combination with the diamides are alkaline earths including magnesium and calcium.

[0047] As used herein, "polymer microstructure" refers to the arrangement of individual polymer chains (or the chain length distribution of such chains) in terms of their composition, sequence distribution, configuration, geometric isomerism, and substitution isomerism. Refers to...

[0048] The term "head-to-tail" polymer microstructure describes the microstructure represented by the styrenic polymer structure (1) above. A head-to-tail microstructure exists when the head of each styrenic monomer unit (derived from the vinyl carbon bearing a phenyl substituent) is covalently bonded to the tail (derived from the vinylidene carbon) of exactly one other styrenic monomer unit.

[0049] The term "tail-to-tail" microstructure exists when the tail of a styrenic monomer unit is covalently bonded to the tail of another styrenic monomer unit. Such tail-to-tail microstructures are common as part of the microstructure of anionic polymerization of styrenic monomers initiated by an electron transfer mechanism.

[0050] The term "tail-to-head-to-tail" microstructure refers to a polymer backbone bond in which the head of one styrenic monomer is covalently bonded to the tails of two other styrenic monomers. This microstructure introduces disorder into the polymer backbone and incorporates undesirable chemically unstable (easily cleaved under certain reaction conditions) quaternary carbons into the polymer chain.

[0051] The terms "organolithium (activated) alkyl", "activated" lithium, and "activated organolithium alkyl" (abbreviated as Li-activated) and "organomagnesium (activated) alkyl" and "activated organomagnesium alkyl" refer to metal alkyls that are charged in excess of the amount of organolithium and / or organomagnesium compound required to titrate any protic reagent and any protic impurity species, such as water, and / or alcohol and / or primary or secondary amines, in total. Without wishing to be bound by theory, it is believed that the molar amount of activated organolithium is equal to the molar amount of salt-like hydride produced 1:1. It is also believed that one molar equivalent of activated organomagnesium compound produces up to two equivalent moles of salt-like hydride. To this end, "activated metal alkyl" refers to an alkyl radical to which lithium and / or magnesium is covalently attached, which may be an aliphatic, alicyclic, aromatic, allylic, benzylic, or vinylic hydrocarbon radical.

[0052] Protic means that when combined with the species, or reagent, or solvent, or impurity of the term, it has a pK lower than that of H2 under the conditions of the chemical process of the invention. a The covalently bonded protons (H + ) means a chemical species having the structure (Buncel, E., Menon, B J. Am. Chem.Soc., 1977, 99, 4457: “Carbanion mechanisms.6. Metalation of Arylmethanes by Potassium Hydride / 18-Crown-6 Ether in Tetrahydrofuran and the Acidity of Hydrogen”).

[0053] "LOXSH" means a lithium aminoalkoxide or lithium amine ether alkoxide or lithium ether alkoxide complex salt-like hydride, which comprises: (i) molecular hydrogen, (ii) an organolithium compound with or without an organomagnesium compound, (iii) optionally a polytertiary amine compound, (iv) a tertiary amino alcohol and / or a tertiary amino ether alcohol and / or an ether alcohol, (v) optionally a solid alkali metal or alkaline earth metal hydride or an alkali metal or alkali metal alloy, (vi) optionally a compound having a pK of at least one C-H covalent bond. a is the pK of toluene a 2.75 pK lower than that of a From the units, the pK of toluene a -4.30pK a Within the range below the unit From aromatic hydrocarbons in (vii) H2, a The aromatic hydrocarbon is formed in a hydrocarbon solvent, which may be the same or different from the aromatic hydrocarbon, having a high pK a for some Hydrocarbon s and Aldehydes and Solvantion Energies of the Corresponding Anions”).

[0054] LOXLiH is the term for the monometallic form of LOXSH, where the catalyst / reagent is made using lithium reagent as the only metal reagent. LOXKH is the term for the bimetallic catalyst of lithium and potassium, where some of the active salt-like hydrides are potassium hydrides. LOXMgH2 is the term for the bimetallic catalyst of lithium and magnesium. and one part of the active salt-like hydride is magnesium hydride.

[0055] [DMEA - ]xLiyHz is a hydrocarbon soluble lithium aminoalkoxide complex hydrogen (i) molecular hydrogen; (ii) about y equivalents of an organolithium compound; (iii) optionally, TMEDA; (iv) about x equivalents of dimethylaminoethanol; (v) optionally, ethylbenzene; (vii) a pK 1 equivalent of 1,2-dichlorophenylhydrazine; a It has a high pK and is formed in a hydrocarbon solvent, which may be ethylbenzene or another (Daasbjerg, K., Acta Chemica Scandinavica, 1995, 49, 878: “Estimation of the pK a for some H hydrocarbons and aldehydes and solvation (see "Energies of the Corresponding Anions"), the index values ​​x, y, and z are positive real numbers, the equivalent of hydride produced is z, where z=yx, and for the stoichiometric ratio x:y:z, a) y is in the range of about 2 to about 6, and b) x is in the range of about 1 to about 5, so that z is in the range of about 5 to about 1. [DMEA - ] A preferred composition of xLiyHz is [DMEA] in a stoichiometric ratio of x:y:z of 2:3:1. - ]2Li3H or [DMEA - ]4Li6H2 or [DMEA - ]6Li9H3, or any larger multiple of the catalyst composition where x=2, y=3, and z=1.

[0056] The term "molecular hydrogen" means 1 H2 as H2, an isotope of hydrogen 2 H2 or 3 H2 It may contain either a mixture of said isotopes or be enriched in a particular isotope, whether in the gaseous state in vapor space or dissolved in a condensed phase.

[0057] The term "alkali metal alloy" refers to a metal alloy of at least two metals, at least one of which is an alkali metal, such as NaK or NaK2. The alloy may also consist of a species of alkali metal, which may be dissolved or in some physical combination with the alloy.

[0058] The term "and / or" means singular or combination. For example, "A and / or B" means "A" alone, "B" alone, or A and B in combination.

[0059] The term "with or without" means singular or in combination. For example, A with or without B means "A" alone or A and B in combination.

[0060] The terms "about x equivalents", "about y equivalents", "about z equivalents", etc., mean ±50%, ±30%, ±20%, ±10%, or ±5% of the stoichiometric equivalent, with the proviso that the amount x is always less than the total amount of active y (i.e., "active organolithium reagent, a.k.a. active lithium) such that the amount z is a positive real number greater than zero and not less than zero.

[0061] The term "organolithium compound" refers to an organic group bonded to a lithium atom. Non-limiting examples of the organic group can be an aliphatic (e.g., alkyl group), an alicyclic (e.g., cycloalkyl), a vinyl group, an allyl group, a benzyl group, an aromatic group (e.g., phenyl), or a poly(styryl)lithium.

[0062] The term "organomagnesium compound" refers to an organic group bonded to a magnesium atom. Non-limiting examples of the organic group may be aliphatic (e.g., alkyl), alicyclic (e.g., cycloalkyl), vinyl, allyl, benzyl, aromatic (e.g., phenyl), or poly(styryl)magnesium. A preferred organomagnesium compound is an organomagnesium compound having two organic groups.

[0063] The term "poly tertiary amine (PTA) promoter" refers to a compound containing at least two tertiary amine groups, which promotes or activates the production of a hydride catalyst during the HMSHIP process. A non-limiting general formula is: [ka] where R′ and R″ are independently organic groups capable of forming bonds with two or more amines; R 1 , R 2 , R 3 , R 4 , and R 5 Independently, other 3rd grade A Polytertiary Amine Structure 2 is an organic group that may be substituted with amine, where the index value n is independently 0 or an integer greater than 0 (i.e., n=0, 1, 2, 3...). It is understood that when n=0, the group within the brackets is not present and the structure is intended to mean that the chemical bond is between two groups that traverse either side of the brackets. Thus, polytertiary amine Structure 2 becomes Structure 4 when n=0.

[0064] The term "polar complexing agent" is a general term for the naturally occurring alcohols, such as tertiary amino alcohols, tertiary amino ether alcohols, or ether alcohols, used to produce the catalysts of the present invention.

[0065] The terms "alkali or alkaline earth aminoalkoxide", "alkali or alkaline earth aminoetheralkoxide" and "alkali or alkaline earth etheralkoxide" refer to alkoxides formed from tertiary aminoalcohols, or tertiary aminoether alcohols, or ether alcohols, and alkali metals, and / or alkali or alkaline earth metal hydrides, and / or alkali or alkaline earth metal amides, and / or alkali or alkaline earth metal alkyls, respectively. The tertiary aminoalcohols, or tertiary aminoether alcohols, or ether alcohols include, but are not limited to, the following general structure: [ka] where R is an organic group capable of forming bonds with one or more tertiary amines and one hydroxyl, and R 1 may be further substituted, independently, with other tertiary amines. i) 5, 6, 7, 8, 9, and 10 are O or NR 1 and ii) O or NR for 11. 1 or CH2, where the index value n is independently 0 or an integer greater than 0 (i.e., n=0, 1, 2, 3...). It is to be understood that when n=0, the group within the brackets is not present and the structure is intended to mean that the chemical bond is between the two groups or atoms that interconnect the two sides of the brackets. Preferred amino alcohols include dimethylaminoethanol, diethylaminoethanol, 3-dimethylamino-1-propanol, N-methyldiethanolamine, triethanolamine, 2-[2-(dimethylamino)ethoxy]ethanol, 1-(2-hydroxyethyl)piperidine, 1-(2-hydroxyethyl)morpholine, 1-(2-hydroxyethyl)pyrrolidine, 1-methyl-2-pyrrolidinemethanol, and the like.

[0066] The tertiary amino alcohol, or tertiary amino ether alcohol, or ether alcohol preferably does not undergo further metallization reactions other than the reaction to produce the alkoxide. Thus, not all tertiary amino alcohols, or tertiary amino ether alcohols, or ether alcohols are suitable for use in the production of certain catalyst compositions, especially those produced in certain alkyl lithium reagents with an excess of certain organolithium compounds. By excess is meant a molar amount greater than the molar amount of the alcohol portion of the tertiary amino alcohol, or tertiary amino ether alcohol, or ether alcohol used to produce the catalyst. Furthermore, the tertiary amino alkoxide, or tertiary amino ether alkoxide, or ether alkoxide should function as a solubilizing bystander ligand. This means other than serving as an activating polar complexing agent that provides solubility to the salt-like hydrides of the catalyst composition and contributes to the activation and production of the salt-like hydrides during the HMSHIP process. Thus, the polar ligand is otherwise inert and does not participate in the polymerization process or in the decomposition reaction of the catalyst. It is not preferred to incorporate the tertiary amino alcohol, or tertiary amino ether alcohol, or ether alcohol decomposition products of such ligands into the polymer structure or product distribution. [Brief description of the drawings]

[0067] [Figure 1] FIG. 1 illustrates a chemical reaction pathway that results in the isomerization and further polymerization of living (meaning ionized) anionic styrene trimer or styrene trimer equivalents (i.e., ethylbenzene combined with two styrene monomers) to produce undesirable quaternary "tail-to-head-to-tail" microstructures. [Diagram 2]FIG. 1 illustrates a chemical reaction pathway involving the cleavage of isomerized living (in the ionized sense, or as a poly(styryl) anion or alkyl) anionic styrene trimer or styrene trimer equivalents and subsequent polymerization to produce polymer chains with a formula weight given by the formula FWi=[i(104)+2-14] Daltons and individual oligomers of FWi=[i(104)+2+14] Daltons. [Diagram 3] FIG. 1 is a gas chromatogram of the structural assignment of the desired high purity “head-to-tail” styrene oligomers obtained from a polystyrene composition of the invention produced from a LOXLiH catalyst of the invention using the hydrogen-mediated, salt-analog hydride initiated polymerization process of the invention. [Figure 4] 1 is a gas chromatogram of styrene oligomers obtained from a polystyrene composition of the present invention produced from another LOXLiH catalyst of the present invention using the hydrogen-mediated, salt-like hydride initiated polymerization process of the present invention. [Diagram 5] 1 is a gas chromatogram of the structural assignment of styrene oligomers obtained from a polystyrene composition produced from a HASH catalyst using the hydrogen-mediated, salt-like hydride initiated polymerization method of the present invention. [Figure 6] 1 is a gas chromatogram of the structural assignment of styrene oligomers obtained from a polystyrene composition produced from a LOXKH catalyst using the hydrogen-mediated salt-analog hydride initiated polymerization method of the present invention. [Figure 7] 1 is a gas chromatogram of the structural assignment of styrene oligomers obtained from a polystyrene composition produced from a SASH catalyst using the hydrogen-mediated, salt-like hydride initiated polymerization method of the present invention. [Figure 8] 1 is a gas chromatogram of the structural assignment of trace amounts of "head-to-tail" styrene oligomers initiated with unreduced butyl magnesium and high purity "head-to-tail" styrene oligomers obtained from the polystyrene composition of the invention produced from the LOXMgH2 catalyst of the invention using the hydrogen mediated salt-like hydride initiated polymerization process of the invention. [Figure 9]FIG. 1 is a gas chromatogram of the structural assignment of a comparative ACTVAP composition of WO2008154453 produced from n-propylbenzene and styrene under nitrogen atmosphere given as a comparison standard. [Figure 10] FIG. 2 is a gas chromatogram of the structural assignment of the comparative ACTSP composition of WO2008154453 produced from toluene and styrene under nitrogen atmosphere given as a comparison standard to identify FWi=[i(104)+2-14] (i=2-6) Daltons resulting from the unfavorable cleavage polymerization process. [Figure 11] FIG. 2 is a gas chromatogram of the structural assignment of a comparative monoadduct of α-methylstyrene to ethylbenzene, given as a comparison standard to identify FWi=[i(104)+2+14] (i=2) Daltons resulting from an undesired cleavage polymerization process occurring in situ after the introduction of α-methylstyrene. [Figure 12] FIG. 2 is a gas chromatogram of oligomers resulting from the ethylbenzene chain transfer polymerization of styrene process technology of EPO 741147, showing undesirable levels of polymer microstructure resulting from isomerization and fragmentation polymerization reactions characteristic of the catalyst and process of this technology. [Figure 13] FIG. 2 is a gas chromatogram of oligomers resulting from the process technology of styrene (1 molar part) with ethylbenzene (2 molar parts) chain transfer polymerization of WO2008154453, showing undesirable levels of polymer microstructure resulting from isomerization and fragmentation polymerization reactions characteristic of the catalyst and process of this technology when ethylbenzene is the chain transfer agent. [Figure 14] FIG. 2 is a gas chromatogram of oligomers resulting from the styrene (2 molar parts) with ethylbenzene (1 molar part) chain transfer polymerization process technology of WO2008154453, showing undesirable levels of polymer microstructure resulting from isomerization and fragmentation polymerization reactions characteristic of the catalyst and process of this technology when ethylbenzene is the chain transfer agent. [Figure 15]FIG. 2 is a gas chromatogram of styrene oligomers obtained from a polystyrene composition of the present invention produced from another LOX LiH catalyst of the present invention, [DMEA-]xLiyHz·2TMEDA (where x:y:z is about 3:2:1), using a hydrogen mediated anionic polymerization of styrene (HMAPS) process of the present invention conducted at about 80° C., showing 99.94% head-to-tail microstructure. [Figure 16] FIG. 2 is a gas chromatogram of styrene oligomers obtained from a polystyrene composition of the present invention produced from another LOX LiH catalyst of the present invention, [DMEA-]xLiyHz (x:y:z is about 3:2:1), using a hydrogen mediated anionic polymerization of styrene (HMAPS) process of the present invention conducted at about 80° C., showing 99.97% head-to-tail microstructure. [Figure 17] FIG. 2 is a gas chromatogram of styrene oligomers obtained from a polystyrene composition of the present invention produced from another LOX LiH catalyst of the present invention, [DMEA-]xLiyHz (x:y:z is about 3:2:1), using a hydrogen mediated anionic polymerization of styrene (HMAPS) process of the present invention conducted at about 90° C., showing 99.93% head-to-tail microstructure.

[0068] explanation The present invention relates to a method for carrying out the hydrogen-mediated, salt-like hydride initiated polymerization (HMSHIP) of anionically polymerizable hydrocarbon monomers, a catalyst composition for carrying out such a method, and the formation under certain preferred conditions of a novel and useful distribution of low molecular weight anionically chain-transferred polymers having extremely pure "head-to-tail" microstructure. The method comprises feeding at least one anionically polymerizable hydrocarbon monomer to a suitable solvent containing an active, generally soluble salt-like hydride catalyst under an atmosphere containing molecular hydrogen, where chain transfer from the molecular hydrogen results in a kinetic chain length (ν) distribution and hence a number average molecular weight (M) distribution of the resulting product distribution. n ) is an important component of the mechanism that determines One embodiment of the present invention relates to a process for the hydrogen-mediated anionic polymerization of styrenic monomers, e.g., vinyl aromatic monomers such as styrene, using a hydrocarbon soluble LOXSH catalyst comprising: (i) an organolithium compound with or without an organomagnesium compound; (ii) optionally a polytertiary amine accelerator compound; (iii) a polar complexing agent selected from a tertiary amino alcohol, a tertiary amino ether alcohol, an ether alcohol, or combinations thereof; (iv) optionally, a catalyst having a pKa of at least one C-H covalent bond that is between 2.75 pKa units above the pKa of toluene and -4.30 pKa units below the pKa of toluene; a (v) optionally a solid alkali metal or alkaline earth metal hydrides, or alkali metals or alkali metal alloys, or alkali or alkaline earth amides; (vi) pK a The process is produced from a reaction medium comprising (vii) a hydrocarbon solvent, which may be the same as or different from the aromatic hydrocarbon, having a high molecular weight, and (vii) molecular hydrogen. The product distribution produced from such a process, in which the monomer is only styrene, is hereinafter referred to as the LOXSH PS distribution. More specifically, when the catalyst is a monometallic catalyst consisting of only lithium as the metal, the catalyst is referred to as LOXLiH and the resulting anionic chain transferred styrene polymer distribution is LOXLiH PS. However, when the catalyst is a bimetallic catalyst consisting of lithium and potassium, the catalyst is referred to as LOXKH and the resulting anionic chain transferred styrene polymer distribution is LOXKH PS. Similarly, when the catalyst is a bimetallic catalyst consisting of lithium and magnesium, the catalyst is referred to as LOXMgH2. The resulting anionic chain transfer styrene polymer distribution is called LOXMgH2PS. .

[0069] In the practice of the present invention, the LOXSH catalyst can optionally be formed in a variety of ways, including, but not limited to: A. forming a solution or suspension of (i), optionally (ii), (iii), optionally (iv), and optionally (v) thoroughly mixed and reacted in (vi) under an inert atmosphere, and then: 1) feeding a portion of the monomer to the "ate" complex thus formed, and then 2) exchanging or otherwise replacing the inert atmosphere with H2 to obtain LOXSH How to convert to, or B. forming a solution or suspension of (i), optionally (ii), (iii), optionally (iv), and optionally (v) thoroughly mixed and reacted in (vi) under an inert atmosphere to produce a precursor "ate" complex, which is then converted to LOXSH by exchanging or otherwise replacing the inert atmosphere with hydrogen; or C. forming a solution or suspension of a portion of (i) and optionally (ii), (iii), a desired amount of (iv), and optionally (v) thoroughly mixed and reacted in (vi) in an external reactor, transferring the solution under hydrogen to the polymerization reactor, and then charging the remainder of (i); or D. forming a solution or suspension of optionally (ii), (iii), optionally (iv), and optionally (v) thoroughly mixed and reacted in (vi) under a hydrogen atmosphere, feeding a portion of the monomer, and then feeding (i) in one portion; or E. forming a solution or suspension of optionally (ii), (iii), optionally (iv), and optionally (v) thoroughly mixed and reacted in (vi) under a hydrogen atmosphere, followed by feeding (i) for a period of more than about 3 minutes, followed by feeding monomers, if any or if necessary; or F. Forming a solution or suspension of (iii), optionally (iv), and optionally (v) by thorough mixing and reacting in (vi) under a hydrogen atmosphere, followed by feeding (i) over a period of more than about 3 minutes, followed by addition of a desired amount of (ii), followed by feeding monomer, if any or if required.

[0070] It has been found that LOXLiH and LOXMgH2 catalysts / reagents are conveniently prepared in highly active and soluble form according to methods E and F under a hydrogen atmosphere at H2 pressures of 1.0-2.0 atm, although higher or lower H2 pressures may be used. The OXMgH2 catalyst is reduced to a hydride by hydrogen until the monomer styrene is introduced. The introduction of styrene resulted in the formation of a poly(styryl)magnesium reagent, which was completely reduced to the hydride during the hydrogen-mediated chain transfer polymerization. Thus, it was not possible to form a sufficient catalyst for LOXMgH2. The presence of a vinyl aromatic monomer may be necessary for the formation of the copolymer, in which case the monomer supply is required and not optional.

[0071] As described in the following examples, the LOXLiH and LOXMgH2 catalysts of the present invention and / or Initial temperatures of about -5°C to about 40°C have been used in forming the reagent. Lower or higher initial temperatures may be used to form the catalyst, particularly when aminoalkoxides are used. Thus, the organolithium (n-butyllithium) and / or organomagnesium (di-n-butylmagnesium) compound (i) is then added to a well-stirred reaction mixture containing dissolved H2, (ii), (iii) in (vi) with appropriate back pressure through a metering needle valve. The reaction mixture is gradually fed with H2. When the organolithium and / or organomagnesium compound produces light hydrocarbons such as butane during the catalyst formation process, a heat kick occurs first, causing the reactor pressure to rise. It is observed that the temperature then continues to rise, but the reactor pressure generally remains constant or lower than the initial pressure as hydrogen is consumed during the catalyst formation process. If the initial pressure is 0 PSIG, a negative pressure or a slight reduced pressure is or can be created in the reactor. In most cases, under the conditions described in the examples, the H2 pressure usually drops during the feeding of the organolithium reagent. However, In some examples, when temperatures are below 15° C. and / or when an organomagnesium reagent is used, the reactor pressure does not appear to drop during introduction of the organometallic reagent. Instead, reduction to the hydride occurs while the reaction mixture is warmed to the desired reaction temperature. In the case of the LOXMgH2 catalyst, the monomer styrene is introduced at reaction temperatures above 70° C. Hydrogen uptake did not appear to be significant until the LOXMgH2 experiment Mass spectrometry of the lowest molecular weight oligomers revealed traces of butyl-initiated oligomers. It has been demonstrated that hydrogen is present in the reaction mixture. This has not been observed with any other catalyst system that does not contain magnesium. To facilitate reduction of the LOXSH catalyst in forming the catalytic reaction mixture, after the reaction mixture is warmed to the desired initial polymerization reaction temperature, additional hydrogen is charged to the reactor such that the reactor pressure is between 40-70 PSIG, although higher pressures can and have been used.

[0072] The catalytic composition of the present invention: LOXSH, LOXLiH, LOXMgH2, or In forming the manufacturable reagent, hydrogen pressures from 0.1 bar to over 300 bar can be used. Preferred H2 pressures are in the range of 0.25 bar to 10.00 bar, more preferably A more preferred range is from 0.5 bar to 7.0 bar, and a most preferred range is from 0.75 bar to about 5.0 bar. We have not overlooked that pressures as high as 100 GPa are theoretically possible, and perhaps even practical, to produce polyhydride compositions from the catalysts and reagents of the present invention, and thus the application of such pressures and the formation of such products are within the scope of the present invention.

[0073] Commercially available organomagnesium compounds may contain about 0.12-0.25 wt% triethylaluminum (TEA) as an additive to the reagent, which is usually supplied in heptane. Such organoaluminum reagents may have a retarding effect on the anionic polymerization reaction, so it is desirable for the lithium metal to aluminum metal ratio to be greater than 50.0:1.0, preferably greater than 101.0:1.0. As shown in Figure 8, TEA initiation or involvement in the HMSHIP process of the LOXMgH2 experiments conducted. There was no evidence of. Thus, by analogy, other organometallic reagents, such as organoaluminum and / or organoberyllium and / or organoboron agents, can be present in the reaction mixture until hydride addition to monomer is inhibited and / or hydrogen chain transfer to the growing polymer chain is terminated or otherwise substantially hindered by and as a result forms an unfavorable molecular weight parameter distribution, so long as the added reagent does not retard the HMSHIP process.

[0074] Preferred, but non-limiting examples of organolithium compounds suitable for forming the LOXSH catalyst are n-butyllithium, sec-butyllithium, t-butyllithium, allyllithium, vinyllithium, phenyllithium, 1-hexyl-1-phenyllithium, 1-hexyl-1,1-diphenyllithium, cyclohexyllithium, and poly(styryl)lithium compounds, which may be added or generated in situ.

[0075] Non-limiting preferred organomagnesium compounds suitable for forming the LOXMgH2 catalyst include Good examples are butylethylmagnesium (BEM), di-n-butylmagnesium (DBM), n-butyl-n-octylmagnesium, di-n-octylmagnesium, dicyclohexylmagnesium, and poly(styryl)magnesium compounds. A comprehensive list of potential organomagnesium compounds is given in U.S. Pat. No. 3,817,955.

[0076] In forming the LOXMgH2 catalyst, it is possible to preform an "ate" complex having the stoichiometry R3MgLi or R4MgLi2, where the groups R are independently alkyl, vinyl, cycloalkyl, poly(styryl), phenyl, and selected from, but not limited to, any combination of organolithium and organomagnesium compounds listed above.

[0077] [PCA] - ]M + or [PCA - ]2M 2+ The [PCA H] is formed from the general structure of the appropriate polar complexing agent [PCAH] shown above. - ]M + and / or PCA - ]2M 2+ It should be apparent that the alkali or alkaline earth amino alkoxides, alkali or alkaline earth amino ether alkoxides, and alkali or alkaline earth ether alkoxides can be formed in situ when forming the LOXSH catalyst, and / or can be fully preformed and charged to the reactor for catalyst formation. - ] Precursor (e.g. For example, the appropriate N,N-dialkylamino acid can be converted to [PCA - ]M + and / or [PCA - ]2M 2+ Any alkali or alkaline earth reagent capable of forming either of the following may be used in the practice of the present invention, and is therefore within the scope of the present invention. As demonstrated by Examples 25-27, the [PCA - ]Nari The components may be preformed and then charged during the catalyst formation reaction. Thus, solid alkali and alkali metal hydrides, alkali metals and alkali metal alloys, alkali metal alkyls and alkaline earth alkyls, alkali metal amides and / or alkaline earth amides (salts similar to metal amides) may be used in the practice of the present invention to produce PCAH and / or [PCA - ] precursor, and reacting it with the catalyst and reagent of the present invention, - ] can be formed. - ]M + and / or [PCA - ]2M 2+ Said formation of [PCA] can be carried out (a) either fully in situ in the reactor for forming the catalyst, prior to and / or during catalyst formation, and / or (b) in an external reactor associated with the reactor for forming the catalyst or completely separate from the reactor for forming the catalyst. However, it should be noted that the use of salt-like metal amides can result in the introduction of amine functionality into the polymer compositions of the present invention, which may be undesirable in some applications. Furthermore, [PCA] - ]Li + The use of a complex metal hydride such as LiAH4 to form The [PCA - ]Li + Separation of the

[0078] Examples 28 and 29 below demonstrate that the aminoether alkoxides may degrade or decompose under certain conditions during production or during the LOXLiH-catalyzed HMSHIP process. Example 30 demonstrates that under certain process conditions, the LOXLiH catalysts formed from ether alkoxides derived from 2-methoxyethanol and organolithium compounds do not sufficiently activate the hydrogen chain transfer process. Thus, the preferred polar complexing agent, particularly for the LOXLiH process, is an aminoalkoxide. However, it should be understood that aminoether alkoxides may be well suited for LOXSH bimetallic catalysts with low LiH activity. Similarly, conditions or processes where the LOXLiH catalyst derived from 2-methoxyethanol is more suitable or more active may be found through the practice of the present invention.

[0079] There are many chiral tertiary amino alcohols available that can be synthesized by reduction of chiral amino acids and further synthetic processing, and the list of suitable amino alcohols as examples can be endless. Any advantage that the use of such chiral tertiary amino alcohols may bring in terms of selectivity, tacticity, or stereoregularity is well within the scope of the present invention. Nevertheless, less complex tertiary amino alcohols that can be prepared by simple reaction of amines with reactive cyclic ethers such as ethylene oxide and other epoxides are preferred. Non-limiting examples of such readily available tertiary amino alcohols include: dimethylaminoethanol, diethylaminoethanol, N-methyldiethanolamine, 3-dimethylamino-1-propanol, 2-[2-(dimethylamino)ethoxy]ethanol, 1-(2-hydroxyethyl)piperidine, 1-(2-hydroxyethyl)morpholine, 1-(2-hydroxyethyl)pyrrolidine, 1-methyl-2-pyrrolidinemethanol, etc.

[0080] Non-limiting examples of poly(tertiary amine) promoters useful for LOXSH catalysis include di(tertiary amine) ligands derived from propylene diamine, di(tertiary amine) ligands derived from ethylene diamine or polyethyleneimine. Preferred examples include N,N Examples of suitable poly(tertiary amine) promoter ligands include, N',N'-tetramethylethylenediamine (TMEDA), N,N,N',N'',N''-pentamethyldiethylenetriamine (PMDETA), sparteine, isosparteine, and 1,4-methylpiperazine, with TMEDA being the most preferred. The most preferred poly(tertiary amine) promoter ligands are the most volatile and / or most water- and / or acid-soluble compounds, and therefore TMEDA is preferred. The presence of the polytertiary amine promoter compound appears to facilitate the formation of the LOXSH catalyst / reagent. Although the LOXSH process can be carried out in the absence of the polytertiary amine promoter, in some examples the presence of the polytertiary amine promoter provided a less asymmetric LOXSH PS distribution with high yields at low monomer feed and low hydrogen pressure.

[0081] Preferred aromatic hydrocarbons that can be used are those having a pK a is ±2.75 pK for toluene a Any aromatic hydrocarbon that is a unit, but pK a Diphenyl ether is 4.32 units lower than toluene. Aromatic hydrocarbons such as diphenylmethane are not acceptable: 1) as long as the incorporation of diphenylmethane moieties into the polymer microstructure does not affect the ultimate end use, and / or 2) the pK ais sufficiently higher than that of H2 under the reaction conditions and does not interfere with the hydrogen-mediated chain transfer mechanism. Non-limiting examples of aromatic hydrocarbons that can be used are benzene, toluene, mesitylene, ethylbenzene, n-propylbenzene, n-butylbenzene, isobutylbenzene, amylbenzene, 1,2-diarylethane, 1,3-diarylpropane, cumene, t-butylbenzene, 1-alkylnaphthalene, 2-alylnaphthalene, or styrene dimer, or low molecular weight oligomer distribution (styrene dimer, trimer, tetramer, and pentamer). Although the use of such aromatic hydrocarbons is optional, their use is preferred because their presence is believed to weaken or avoid or otherwise reduce the undesirable attack of the organolithium, more specifically alkyllithium, reagent on the polytertiary amine promoter. LOXSH catalysts can reduce or inhibit attack of the organolithium reagent on the alkali or alkaline earth aminoalkoxides, alkali or alkaline earth aminoether alkoxides, and alkali or alkaline earth ether alkoxides that make up the catalyst. Hydrocarbons that are easily removed from the product distribution by distillation or by polymer precipitation are preferred. The most preferred aromatic hydrocarbon for a HMSHIP process using styrene is ethylbenzene.

[0082] Hydrocarbon solvents that may be used have a higher pK than molecular hydrogen (H2) under the reaction conditions. a The solvent is any hydrocarbon having the formula: ##STR00011## Non-limiting examples of such preferred solvents are cyclohexane, methylcyclohexane, and the aromatic hydrocarbons listed above. Other hydrocarbon solvents can be used as long as their use does not affect the solubility of the salt-like hydride catalyst, reactive intermediates, transient living polymer chains, and the product of the polymer chain distribution.

[0083] The aromatic hydrocarbon and the aromatic solvent may be the same or different. This means that the aromatic hydrocarbon can perform the functions of both the aromatic hydrocarbon and the solvent. For example, ethylbenzene is a preferred component in the polymerization of styrene and can be used as both the aromatic hydrocarbon and the solvent. In this case, for the LOXSH process, components (iv) and (vi) are integrated into one component (or constraint) and become the same. Similarly, they may be different. For example, the aromatic hydrocarbon may be ethylbenzene and the hydrocarbon may be cyclohexane. Thus, components (iv) and (vi) are different. Furthermore, component (iv) may be optional when no aromatic hydrocarbon is used, for example, cyclohexane is used as component (vi).

[0084] The hydrogen partial pressure in the LOXSH catalyst formation step is maintained at a pressure between about 0.001 and about 10.0 bar, about 0.3 and about 6.8 bar, about 0.5 and about 5.2 bar, or about 1.0 and about 4.2 bar.

[0085] In forming the monometallic LOX LiH catalyst from a tertiary amino alcohol and an organolithium compound, the ratio of tertiary amino alcohol to organolithium may vary widely. However, it should be understood that a molar excess of the organolithium compound over a molar equivalent of the tertiary amino alcohol must be used so that the lithium-carbon bond is available for reduction to the lithium hydride species to form the lithium hydride species. Although it is conceivable to use a loading ratio of 40 moles of tertiary amino alcohol per 41 moles of organolithium reagent, such a loading ratio is a waste of expensive reagents. The preferred loading ratio (tertiary amino alcohol:organolithium) is in the range of (1.00:1.05) to about (1:6), with a more preferred range being (1.00:1.10) to about (1:5), an even more preferred range being (1.0:1.2) to about (1:4), and a most preferred range being (1.00:1.40) to about (1:3).

[0086] Without wishing to be bound by theory, the results reported in Examples 33 and 34 below indicate that a loading ratio of N,N-dimethylaminoethanol (DMEAH) to n-butyllithium (1:1.5), i.e. (2:3), together with simultaneous or subsequent reduction with hydrogen to form the hydride, affords a product of the formula [DMEA - ]Li6H2 dihydride catalyst was obtained, demonstrating that only one of these two hydrides initiates the polymerization of styrene under a cyclohexane atmosphere. Similarly, Examples 35 and 36 show that a 1:2 ratio of DMEAH to n-butyllithium can be used to produce a dihydride catalyst of the formula [DMEA - ]4Li8H4 tetrahydride catalyst was obtained, indicating that only one of these four hydrides initiates the polymerization of styrene under a hydrogen atmosphere. Similarly, at the (1:3) loading ratio used in Example 37), a catalyst of the formula [DMEA - ]2Li6H4, a soluble hydride catalyst, was produced, in which only about one in nine hydrides initiated the polymerization of styrene in a cyclohexane atmosphere. Thus, this theoretically preferred catalyst composition has the empirical formula [DMEA - ]4Li 12 H8 and [DMEA - ]5Li 15 H 10 and only one hydride of both catalysts is available to initiate styrene polymerization in the absence of additional molecular hydrogen. The most preferred catalyst composition comprises a mixture of aggregates having an overall empirical formula: (a) [DMEA - ]5Li 12 H7, and / or (b) [DMEA - ]2Li5H3 comprising a catalytic aggregate having In this case, the ratio of tertiary amino alcohol to organolithium is in the range of 1:2.4 to 1:2.5. The same preferred ranges apply to the formation of soluble lithium hydride complexes, catalysts, and reagents from tertiary amino ether alcohols and / or ether alcohols.

[0087] It should be noted that LOXLiH catalysts, when formed under hydrogen, exist as aggregates that under certain stoichiometries exist as well-defined species of a given molecular weight, while other stoichiometries or loading ratios are believed to result in catalysts that exist as a mixture of less well-defined but heterogeneous aggregates. It is further believed that the presence of a polytertiary amine promoter can either further stabilize certain aggregates or promote the dispersion of a less homogeneous mixture of larger aggregates into smaller, more active aggregates. Thus, although there can be considerable differences in the activity of the catalyst systems, overall this class of catalysts is relatively poor at initiating living anionic polymerization. That is, the LOXLiH reagent as an initiator under an H2-free atmosphere is more efficient at initiating living anionic polymerization than the LOXLiH reagent under H2-free atmosphere. It is relatively inefficient in terms of the availability of hydrides for initiation (Eff CT <1.0 and Eff CT =0.1~Eff CT =0.67). Thus, these same catalysts are so efficient at initiating and catalyzing the hydrogen-mediated anionic chain transfer polymerization of the present invention that the %Eff CT = 1000% - 16000%, it remains very surprising that the lower values, i.e. values ​​close to 1000%, only result from the deliberately limited use of monomers.

[0088] The hydrocarbon soluble LOXSH catalyst has the following empirical chemical formula: - ]4Li6H2, b) [PCA - ]4Li8H4, c) [PCA - ]2Li6H4, d) [PCA - ]4Li 12 H8, e) [PCA - ]5Li 15 H 10 , f) [PCA - ]5Li 12 H7, g) [PCA - ]2Li5H3 , h) [PCA - ]4Li4MgH2, i)[PCA- ]4Li4Mg2H4, j)[PCA - ]2 Li4MgH4, k) [PCA - ]4Li6Mg3H8, l)[PCA - ]5Li9Mg3H 10 , m ) [PCA - ]5Li6Mg3H7, n)[PCA - ]2Li3MgH3,o)[PCA - ]4Li5KH2, p)[PCA - ]4Li7KH4, and q)[PCA - ]2Li5KH4 In addition, the empirical formula may optionally further include a PTA promoter ligand complex in a molar ratio of the sum of the alkali metal and alkaline earth metal to the PTA of about 10,000 to 1.0 to about 1.0 to about 8.0. - ] is [DMEA - ], [DMAEOE - ],or [MEOE - ].

[0089] In forming the bimetallic Group I alkali metal LOXSH catalyst, the ratio of the total tertiary amino alcohol to alkali metal (tertiary amino alcohol:alkali) is in the range of (1.00:1.05) to about (1:6), more preferably (1.00:1.10) to about (1:5), even more preferably (1.0:1.2) to about (1:4), and most preferably (1.00:1.40) to about (1:3). Also, the ratio of lithium to alkali metal other than lithium (such as Li:Na and / or Li:K and / or Li:Cs) is in the range of (10,000:1) to (1:2), with a preferred ratio being (34:1) to (2:1), and most preferably being (17:1) to (3:1). In this context, the loading ratio (10,000:1) may represent the unintentional presence of trace amounts of alkali metals, especially potassium, due to amounts left in the reactor or charge lines or tanks from previous experiments in which the alkali metal was intentionally charged. Potassium and other alkali metal-based bimetallic lithium catalysts tend to deposit trace amounts of catalyst or catalyst by-products on the reactor walls, and such traces have been found to adversely affect the highly selective microstructure otherwise produced by the pure LOXLiH catalyst system during the hydrogen-mediated, salt-like hydride-initiated polymerization of styrene.

[0090] Bimetallic lithium bimetallic complexes with sodium and / or potassium and / or cesium LOXSH catalysts with experimental chemical formula: a) [DMEA - ]4Na4Li4H4, b) [DMEA - ]6 Na4Li4H2), c) [DMEA - ]6Na4Li6H4, d) [DMEA - ]4K4Li4H4 , e) [DMEA - ]6K4Li4H2), f)[DMEA - ]6K4Li6H4, g)[DMEA - ]4Cs4Li4H4,h)[DMEA - ]6Cs4Li4H2), and i) [DMEA -]6Cs4Li6H4 can be produced from the present invention. Furthermore, such bimetallic LOXSH Combinations of catalyst formulations with the monometallic LOX LiH catalyst formulations described above are within the scope of the present invention.

[0091] In forming the magnesium hydride-based bimetallic Group II alkaline earth lithium complex, i.e., LOXMgH2 catalyst, lithium provides one equivalent and magnesium provides two equivalents. The ratio of tertiary amino alcohol to total metal equivalents ranges from (1.00:1.05) to about (1:6), more preferably from (1.00:1.10) to about (1:5), even more preferably from (1.0:1.2) to about (1:4), and most preferably from (1.00:1.40) to about (1:3). Thus, the empirical formula [DMEA - ]4Li4 The catalyst composition of MgH2 (4 moles of DMEAH to 5 moles total metal) is therefore (4:6 or is 1.0:1.5 DMEAH:total metal equivalents) and is preferred. - ]4Li4Mg2H4(1:2 DMEAH:total metal equivalent), b)[DMEA - ]6Li4Mg2H2 (1.00:1.33 DMEAH:total metal equivalents), and c) [DMEA - ]6Li4Mg3H4 (1.00:1.67 DMEAH:total metal equivalents) catalyst alone or combinations with the LOXLiH or LOXSH catalyst formulations from above are within the scope of the present invention. The same preferred ranges apply to the soluble bimetallic lithium magnesium hydride complexes, catalysts, and reagents tertiary amino ether alcohols and / or ether alcohols. The same preferred ranges may be used in the formation of soluble bimetallic lithium calcium hydride complexes, catalysts, and reagents from tertiary amino alcohols and / or tertiary amino ether alcohols and / or ether alcohols.

[0092] The present invention further relates to a hydrocarbon soluble catalyst or reagent composition formed from a reagent comprising a solid alkali hydride, an alkali metal and / or an alkali metal alloy, wherein the ratio of the total polar complexing agent to the alkali metal ranges from about 1:1.05 to about 1:6, and the molar ratio of the organolithium compound to the alkali metal is from 10,000 to 1:2.

[0093] Another embodiment is a hydrocarbon soluble monometallic LOX LiH catalyst or reagent composition formed from molecular hydrogen and any of the following: a. a polar complexing agent reacted with a lithium alkoxide and an organolithium compound, the total molar ratio of polar complexing agent to alkali metal being in the range of about 1:1.05 to about 1:6; b. a polar complexing agent and an organolithium compound, the total molar ratio of polar complexing agent to alkali metal being in the range of about 1:1.05 to about 1:6; or c. a polar complexing agent, at least one solid lithium hydride and / or lithium metal, and an organolithium compound, wherein the total molar ratio of polar complexing agent to lithium is in the range of about 1:1.05 to about 1:6.

[0094] Another embodiment is a magnesium hydride alkaline earth metal LOXMgH2 catalyst or A hydrocarbon soluble catalyst or reagent composition comprising a reagent formed from molecular hydrogen and any of the following: a. a polar complexing agent, an organolithium compound, and / or an organomagnesium compound reacted to form lithium and / or magnesium alkoxides, the molar ratio of polar complexing agent to total metal equivalents being in the range of about 1:1.05 to about 1:6, with lithium providing one equivalent and magnesium providing two equivalents; b. a polar complexing agent, an organolithium compound, and an organomagnesium compound, wherein the molar ratio of polar complexing agent to total metal equivalents is in the range of about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium providing 2 equivalents; c. a polar complexing agent, at least one solid lithium hydride, metallic lithium, solid magnesium hydride, at least one organolithium compound and / or organomagnesium compound, wherein the molar ratio of polar complexing agent to total metal equivalents is in the range of about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium providing 2 equivalents; d. a polar complexing agent, at least one solid lithium hydride and / or metallic lithium, and an organomagnesium compound, wherein the molar ratio of polar complexing agent to total metal equivalents is in the range of about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium providing 2 equivalents; e. A polar complexing agent, solid magnesium hydride, and an organolithium compound, wherein the molar ratio of polar complexing agent to total metal equivalents is in the range of about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium supplying 2 equivalents. f. The molar ratio of lithium to magnesium in the catalyst composition is in the range of 10,000:1 to 1:6.

[0095] Another embodiment is a process for preparing a hydride complex comprising: (i) molecular hydrogen; (ii) an organolithium compound and / or an organomagnesium compound; (iii) optionally a polytertiary amine compound; (iv) a polar complexing agent selected from a tertiary amino alcohol compound, a tertiary amino ether alcohol, an ether alcohol, or a combination thereof; (v) optionally an alkali metal or metal alloy and / or a solid salt-like hydride and / or an alkali amide; (vi) optionally a compound having a pK of at least one C-H covalent bond; a is the pK of toluene a 2.75 pK lower than that of a From the unit, Torue pK a -4.30pK a From aromatic hydrocarbons within the range below the unit, (vii) H 2 than pK a a method for forming a hydrocarbon soluble catalyst or reagent composition having a high catalytic activity, the catalyst or reagent composition being formed in a hydrocarbon solvent, which may be the same as or different from the aromatic hydrocarbon.

[0096] In the above method, the hydrogen partial pressure used in forming the catalyst or reagent ranges from about 0.1 bar to about 300 bar. Furthermore, the temperature used in forming the catalyst or reagent ranges from about -96°C to about 130°C. Furthermore, the loading ratio of the polar complexing agent to the molar equivalents of the organolithium compound and / or organomagnesium is in the range of about 1:1.05 to about 1:6 moles of polar complexing agent per mole of metal alkyl equivalent, where lithium provides 1 equivalent and magnesium provides 2 equivalents. When PTA is used in forming the catalyst or reagent, the molar ratio of PTA to total metal (magnesium and lithium) is about 10,000:1.0 to about 1:8.

[0097] One embodiment of forming the hydrocarbon soluble catalyst or reagent composition comprises the steps of: A. The polar complexing agent is first contacted with at least one of the following alkoxide-forming reagents: a) solid lithium hydride, b) lithium metal, c) magnesium hydride, d) lithium amide, e) magnesium amide, f) organolithium compound, g) organomagnesium compound, thereby forming a reaction mixture, where the stoichiometric molar equivalent ratio of polar complexing agent to alkoxide-forming reagent is from about 1:1 to less than 1:1, with lithium providing 1 equivalent and magnesium providing 2 equivalents. B. The organolithium compound and / or the organomagnesium compound are further added. C. The polar complexing agent to total metal equivalent ratio ranges from about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium providing 2 equivalents. D. The molar ratio of lithium to magnesium ranges from about 10,000:1 to about 1.0:6.0. E. The reaction products formed are further reduced with hydrogen to form the hydrocarbon soluble salt-like hydride catalyst or reagent.

[0098] Another embodiment of forming the hydrocarbon soluble catalyst or reagent composition comprises the steps of: A. The polar complexing agent is first contacted with an alkali alkoxide-forming reagent, thereby forming a reaction mixture, wherein the stoichiometric molar equivalent ratio of polar complexing agent to alkoxide-forming reagent is from about 1:1 to less than 1:1. B. The alkoxide-forming reagent is at least one of a) a solid alkali hydride, b) an alkali metal, c) an alkali metal alloy, d) an alkali amide, e) a magnesium amide, f) an organolithium compound, g) an organomagnesium compound. C. Further adding the organolithium compound and / or organomagnesium compound. D. The ratio of polar complexing agent to total alkali metal ranges from about 1:1.05 to about 1:6. E. The molar ratio of lithium to non-lithium alkali metal ranges from 1:2 to about 10,000:1, or the alkali metal of the catalyst composition is lithium only. F. The reaction product formed is further reduced with hydrogen to form the hydrocarbon soluble salt-like hydride catalyst or reagent.

[0099] In the above methods and steps for forming the hydrocarbon soluble catalyst or reagent composition, the method may further include providing a styrenic monomer to form a poly(styryl)magnesium and / or poly(styryl)lithium compound, which is then reduced by contact with molecular hydrogen to form the soluble salt-like hydride, wherein the molar ratio of styrenic monomer to total metal is from about 1:10 to about 20:1. In another embodiment, the method further includes providing a styrenic monomer to form a transient 1-phenylhexylmagnesium compound and / or a poly(styryl)magnesium compound, This may be further reduced with molecular hydrogen to form the soluble salt-like hydride, where the molar ratio of styrenic monomer to magnesium is from about 1:5 to about 20:1.The preferred styrenic monomer is styrene.

[0100] In another embodiment of the invention, the hydrocarbon soluble catalyst or reagent composition comprises: (i) molecular hydrogen, (ii) an organolithium compound and / or an organomagnesium compound, (iii) optionally a polytertiary amine compound, (iv) a polar complexing agent selected from a tertiary amino alcohol compound, a tertiary amino ether alcohol, an ether alcohol, or a combination thereof, (v) optionally an alkali metal or metal alloy and / or a solid salt-like hydride and / or an alkali amide, (vi) optionally a compound having a pK of at least one C-H covalent bond. a Toluene pK a 2.75 pK lower than that of a From the units, the pK of toluene a -4.30pK a Aromatic hydrocarbons within the range below the unit, (vii) vinyl aromatic monomers, (viii) pK from H2 a The solubility of the hydride, including the catalyst or reagent, formed in a hydrocarbon solvent, which may be the same as or different from the aromatic hydrocarbon, having a high solubility is at least about 0.0080 moles per liter.

[0101] Another embodiment of the present invention is a hydride compound comprising: (i) molecular hydrogen; (ii) an organolithium compound and / or an organomagnesium compound; (iii) optionally a polytertiary amine compound; (iv) a tertiary amino alcohol compound and / or a tertiary amino ether alcohol and / or an ether alcohol; (v) optionally an alkali metal or metal alloy and / or a solid salt-like hydride; (vi) optionally a pK of at least one C-H covalent bond. a is the pK of toluene a 2.75 pK lower than that of a From the units, the pK of toluene a -4.30pK a Within the range of units From aromatic hydrocarbons, (vii) pK from H2 a The present invention relates to a catalyst or reagent composition formed in a hydrocarbon solvent, which may be the same as or different from the aromatic hydrocarbon, having a high catalytic activity.

[0102] The most preferred LOXSH catalyst is a bimetallic LOXMgH2 catalyst composition or agglomerate formed when the tertiary amino alcohol is N,N-dimethylamino alcohol (DMEAH). Depending on the loading ratio of the reagents, it can have an empirical formula and / or a molecular formula as a well-defined composition or as an average composition of the catalyst mixture in solution: a) [DMEA - ]4Li4MgH2, b) [DMEA - ]4Li4Mg2H4, c) [DMEA - ]2Li4MgH4, d) [DMEA - ]4Li6Mg3H8, e) [DMEA - ]5Li9Mg3H 10 , (f) [DM EA - ]5Li6Mg3H7, and (b) [DMEA - ]2Li3MgH3.

[0103] Particularly preferred LOXSH catalysts are monometallic LOXLiH catalyst compositions or aggregates formed when the tertiary amino alcohol is N,N-dimethylamino alcohol (DMEAH), which, depending on the loading ratio of the reagents, can have an empirical and / or molecular formula as a well-defined composition or as an average composition of the catalyst mixture in solution: a) [DMEAH] - ]4Li6H2, b) [DMEA - ]4Li8H4, c)[DMEA - ]2Li6H4, d) [DMEA - ]4Li 12 H8, e) [DMEA - ]5Li 15 H 10 , (f) [DMEA - ]5Li 12 H7, and (g) [DMEA - ]2Li5H3.

[0104] Thus, a preferred hydrocarbon soluble LOXLIH catalyst has the formula [DMEA - ] x Li y Hz where z=yx, and x, y, and z are positive real integers or fractions greater than zero and not equal to zero, which formula can optionally further include a TMEDA ligand complex in a molar ratio of the sum of lithium to TMEDA of about 10,000 to 1.0 to about 1.0 to about 8.0.

[0105] Thus, the present invention also relates to a hydrocarbon-soluble catalyst or reagent composition formed from a reagent comprising hydrogen, an organolithium compound, and dimethylaminoethanol, and having one or more of the following empirical and / or molecular formulas, depending on the loading ratio of the reagents: I) 1) to 105) in solution: II) as an average LiH aggregate composition of any two or more from 1) to 105) in any proportion in solution; or III) as a combination of one or more well-defined LiH aggregate compositions or average compositions in solution and some insoluble LiH aggregate composition from 1) to 105) outside of solution: [Table 3-1] [Table 3-2] or IV) I), II), or III), and the total composition of the catalyst aggregates is [DMEA - ] x Li y H z Therefore, the hydrocarbon soluble [DMEA - ] x Li y H z The catalyst is: (i) y equivalents of an organolithium compound, (ii) an optional amount of TMEDA, (iii) x equivalents of dimethylaminoethanol, (iv) optionally ethylbenzene, (v) a pK aand (vi) molecular hydrogen, the amount of hydride produced, z, is given by the equation z=yx, where x, y, and z are positive real integers or fractions greater than zero and not less than zero.

[0106] In the practice of the present invention, the [DMEA - ] x Li y H z The catalyst can optionally be formed in a variety of ways, including, but not limited to: a) forming a solution or suspension of about y equivalents of (i), optionally (ii), about x equivalents of (iii), and optionally (iv) thoroughly mixed and reacted in (v) under an inert atmosphere, followed by: 1) feeding a portion of styrene to the "ate" complex thus formed, followed by 2) exchanging or otherwise replacing the inert atmosphere with H2 to form [DMEA - ] x Li y H z How to convert to, or b) forming a solution or suspension of about y equivalents of (i), optionally (ii), about x equivalents of (iii), and optionally (iv) thoroughly mixed and reacted in (v) under an inert atmosphere to form a precursor "ate" complex, which is then reacted by exchanging or otherwise replacing the inert atmosphere with hydrogen to form [DMEA - ] x Li y H z How to convert to, or c) forming in an external reactor a solution or suspension of about x equivalents of a portion of (i) and optionally (ii), about x equivalents of (iii), and optionally (iv), thoroughly mixed and reacted in (vi), and transferring said solution under hydrogen to a hydride-forming reactor, followed by charging with about z or yx equivalents of the remainder of (i); or d) forming a solution or suspension of optionally (ii), about x equivalents of (iii), and optionally (iv) in (v) under a hydrogen atmosphere, which are thoroughly mixed and reacted, and then adding y equivalents of (i) all at once or in large part gradually; or e) forming a solution or suspension of optionally (ii), about x equivalents of (iii), and optionally (iv) in (v) under a hydrogen atmosphere, which have been thoroughly mixed and reacted, and then continuously or gradually adding about y equivalents of (i) over a period of more than about 3 minutes; or f) forming a solution or suspension of about x equivalents of (iii) and, optionally, (iv) in (v) under a hydrogen atmosphere, which are thoroughly mixed and reacted, and then continuously or gradually feeding about y equivalents of (i) over a period of more than about 3 minutes, followed by the addition of the desired amount of (ii); g) forming a solution or suspension of x equivalents of (iii) and, optionally, (iv) in a portion of (v) under a hydrogen atmosphere, which have been thoroughly mixed and reacted, and then continuously or gradually feeding about y equivalents of (i), previously diluted with a portion of (iv) and / or (v), over a period of more than about 3 minutes, followed by the addition of a desired amount of (ii); h) forming a solution or suspension of about x equivalents of (i) and, optionally, (iv) in a portion of (v) under a hydrogen atmosphere, which have been thoroughly mixed and reacted, and then feeding about x equivalents of (iii), previously further diluted with a portion of (iv) and / or (v), all at once, or continuously, or gradually, until the entire charge of (iii) is completed, followed by feeding about z or yx equivalents of (i), followed by the desired amount of (ii).

[0107] [DMEA - ] x Li y H z The catalyst / reagents were placed in an initial hydrogen atmosphere with H2 pressure of 1.0-3.0 atm. It has been found to be conveniently prepared in a highly active and soluble form at ambient temperature according to methods e), f), and g), although higher or lower H2 pressures can be used.

[0108] Depending on the melting points of (iv) and (v) and the solubility and stability of (i), (ii), and (iii) under the reaction conditions, initial temperatures from -96°C to over 100°C may be used to prepare the [DMEA - ] x Li y H z It can be used to form a catalyst and / or reagent. As described in the Examples, the [DMEA - ] x Li y H z The catalyst is conveniently prepared at a temperature in the range of 35°C to 40°C.

[0109] Therefore, [DMEA - ]2Li3H catalyst, most typically about 3 equivalents (y 3) of organolithium compound (16.5 wt% n-butyllithium in cyclohexane) (i) further diluted with cyclohexane and / or methylcyclohexane (v) and / or ethylbenzene (iv) is then gradually (over a period of 15-25 minutes) added to a well-stirred (about 50-about 2000 RPM, preferably about 200-about 1500 RPM, most preferably about 500-about 1200 RPM, when using a pitched blade or any other suitable gas dispersion mixer as described herein below) solution of dissolved H2 (15-22P) at 35°C-40°C with adequate back pressure through a metering needle valve (20-30 PSIG back pressure drop through said valve). SIG H2), about 2 equivalents (x ≒ 2) of dimethylaminoethanol (ii) are added to ethyl benzene. The reaction mixture is fed in cyclohexane and / or methylcyclohexane (v), with or without benzene (iv). Initially, during the first 1 / 3 to about 2 / 3 of the (i) feed, there is a barely noticeable heat kick due to butanes being produced, i.e., when (i) is a butyllithium reagent, there is a 2-3 PSIG reactor pressure rise. The reactor pressure rise is also due in part to compression of headspace vapors and gases due to the volume of feed being introduced, especially when (i) is diluted with larger amounts of (iv) and / or (v). During about the last 1 / 3 of the (i) feed, the temperature rises (1.0° to 3.0° C. in the reactor described in the Examples) and the [DMEA - ] x Li y H z Depending on the conditions used to form the catalyst the pressure will either stabilize or drop by 1-3 PSIG.

[0110] Upon formation of the catalytic reaction mixture, the [DMEA - ] x Li y H z To facilitate complete reduction of the catalyst, hydrogen is further charged to the reactor vessel after the reaction mixture is warmed to the desired initial polymerization reaction temperature such that the reactor pressure is between 60 and 80 PSIG. Although not necessary to form an active catalyst, the most active form of [DMEA - ] x Li y H z It was found that catalysts were prepared when this additional hydrogen charge up to high pressure was used, and the most active and most reproducible catalysts were those prepared by adding the [DMEA - ] x Li y H z It has also been found that the catalyst is formed when maintained at or near the desired reaction temperature for the hydrogen-mediated anionic polymerization (about 68°C to about 82°C) for more than about 1 hour, preferably more than about 2 hours to about 5 hours, and can then be released to the desired H2 pressure for polymerization. It is not essential to carry out a catalyst maturation procedure, but this procedure works well for reproducibility between experiments. Without wishing to be bound by theory, the catalyst maturation step may provide a high concentration of available hydride in the form of a well-defined catalyst composition having 2, or 3, or 4 LiH moieties in individual aggregates depending on the loading ratio of (i):(iii). The catalyst maturation step is considered as an equilibration or redistribution of the initially occurring higher order aggregates having more than 4 LiH moieties or equivalents per aggregate, and / or a redistribution of less desirable ratio x:y:z aggregate compositions to form a high concentration of desired ratio x:y:z catalyst aggregates.

[0111] Thus, the most active catalyst is: (a) about 3 equivalents of (i) (2.0M in 1 part by weight of cyclohexane) further dissolved in 8-10 parts by weight of ethylbenzene; (b) (a) mixed with 24-28 parts by weight of (iv) and / or (v) without (ii) stirred at about 500 RPM under a hydrogen atmosphere of 16-21 PSIG at about 35-40° C. for about 15-25 minutes; (c) optionally adding (ii), (d) increasing the hydrogen pressure to 50 PSIG and the mixing RPM to 900 to about 1200 RPM, (e) warming the solution formed in (b) to about 65°C to about 85°C, (f) further increasing the hydrogen pressure to about 75 PSIG, and (g) aging the catalyst for a period of about 1 hour to about 5 hours or more. After the aging period, the hydrogen pressure is carefully vented from the reactor to a pressure desired for carrying out the hydrogen-mediated anionic polymerization process of styrene of the present invention. Hydrocarbon-soluble lithium hydride compositions that do not contain any covalently bonded Lewis acid groups formed directly from hydrogen are heretofore unknown. Thus, this equilibration or catalyst aging step under hydrogen at elevated temperatures is also a feature of the present invention. This feature is not without basis from published literature reports of the formation of vicinal lithium aminoalkoxide aggregates and lithium aminoalkoxide complexed organolithium reagents. Thus, certain organolithium reagents prepared from chiral vicinal lithium aminoalkoxides have been reported to be more enantioselective for the addition of the organolithium reagent to ketones following certain loading protocols and aging of the reagent components under cryogenic conditions prior to introduction of the ketone. See Collumn, DB, et.al. "Highly Enantioselective 1,2 Addition of Lithium Acetylide-Ephedrate Complexes: Spectroscopic Evidence for Reaction Proceeding via 2:2 Tetramer, and X-ray Characterization of Related Complexes", J. Am. Chem. Soc. 2000, 122. 11212.

[0112] Preferred, but non-limiting examples of organolithium compounds suitable for forming the LOXSH catalyst are n-butyllithium, sec-butyllithium, t-butyllithium, allyllithium, vinyllithium, phenyllithium, 1-hexyl-1-phenyllithium, 1-hexyl-1,1-diphenyllithium, cyclohexyllithium, and poly(styryl)lithium compounds, which may be added or generated in situ.

[0113] [DMEA] from dimethylaminoethanol and organolithium compounds - ] x Li y H z In forming the catalyst, the ratio of dimethylaminoethanol to organolithium may vary widely. However, it should be understood that a molar excess of the organolithium compound over a molar equivalent of dimethylaminoethanol must be used so that the lithium-carbon bond is available for reduction to the lithium hydride species to form the lithium hydride species. Although it is conceivable to use a loading ratio of 40 moles of dimethylaminoethanol per 41 moles of organolithium reagent, such a loading ratio is a waste of expensive reagent. The preferred loading ratio (dimethylaminoethanol:organolithium) is in the range of (1.00:1.05) to about (1:6), with a more preferred range being (1.00:1.10) to about (1:5), an even more preferred range being (1.0:1.2) to about (1:4), and a most preferred range being (1.00:1.40) to about (1:3). In the examples, [DMEA - The 4Li6H2 catalyst was formed from a loading ratio of approximately 2 moles of dimethylaminoethanol to 3 moles of n-butyllithium.

[0114] Further dilution of the organolithium reagent solution of about 2.0 molar or greater with a portion of a hydrocarbon solvent, particularly ethylbenzene, to about ≦0.2 molar can result in the formation of the more active [DMEA - ] x Li y H z It has been found to be advantageous (but not essential) in the formation of the catalyst. One explanation is that at lower concentrations of the organolithium compounds, the organolithium species are less likely to exist in polymer aggregates. The complex relationships resulting from the degree of association of alkyllithium compounds in living anionic polymerization reactions of styrene and conjugated dienes are well established in the art (see, for example, Hsieh HL and Quirk, RP Anionic Polymerization Principles and Practical Applications, Marcel Dekk, 1999). (See, e.g., J. Chem. Soc., 1996, New York, pp 135-132, especially page 138, Table 6.2). As typically supplied as relatively concentrated solutions (>1.0 molar solutions), n-butyllithium typically has a degree of association of 6, and t-butyllithium and sec-butyllithium typically have a degree of association of 4 in hydrocarbon solvents. Dilution of the organolithium compound with the solvent reduces the association of the organolithium reagent and thus the [DMEA - ] x Li y H z This may lead to a decrease in the local organolithium concentration during catalyst formation. Although it is not desirable to do so, it is believed that the high local concentrations of the organolithium compounds during catalyst formation may lead to the formation of less active, i.e. less available, active forms of LiH superaggregates [DMEA - ] x Li y H z This can result in the formation of catalysts. Low pK compared to aliphatic or cycloaliphatic hydrocarbons a Lithium DMEA - There may also be some advantage in suppressing any undesired attack of the organolithium reagent on DMEAH beyond the initial formation of the alkoxide. Thus, the use of sec-butyllithium may prove to be more efficient than n-butyllithium due to the inherent lower state of association of this organolithium compound compared to n-butyllithium.

[0115] When formed under a hydrogen atmosphere, [DMEA - ] x Li y H z It is noted that the catalyst exists as aggregates, which under a certain stoichiometry can exist as well-defined species of a given molecular weight, while other stoichiometries or loading ratios are believed to result in catalysts that exist as a mixture of less well-defined but heterogeneous aggregates or superaggregates.Furthermore, it is believed that the presence of poly tertiary amine promoters or any other suitable organic Lewis bases (e.g., tetrahydrofuran) can either further stabilize certain aggregates or promote the dispersion of less homogeneous mixtures of larger aggregates into smaller, more active aggregates.Therefore, the activity of the catalyst system can vary considerably based on the loading ratio, catalyst components, and protocol followed in the preparation of the catalyst.

[0116] [DMEA - ] x Li y H z The partial pressure of molecular hydrogen used in forming the catalyst is maintained at a pressure between about 0.1 and 300 bar, or about 0.5 and about 12.0 bar, or about 1.0 and about 10.0 bar, or about 1.1 and about 5.0 bar. A low or high hydrogen partial pressure can be used to obtain adequate mixing for mass transfer of H2 from the gas phase to the condensed phase, and thus to ensure that the mixture is [DMEA - ]xLiyHz can be used as long as it is important for the formation of the catalyst in a reasonably short period of time.

[0117] [DMEA - The temperature used to form the ]xLiyHz catalyst is about -96°C to about 130°C. The temperature is preferably maintained in the range of about 20° C. to about 110° C., and more preferably in the range of 30° C. to 90° C. [DMEA - ]xLiyHz In the formation of the catalyst and subsequently the first During the heating process, the catalyst components can be mixed and reacted at a temperature merely above the melting point of the hydrocarbon solvent (or solvent mixture) or the freezing point of the monomers that are or will be fed. Mixing the catalyst components at low temperatures (i.e., −10 to 15° C.) and even under cryogenic conditions (−10 to −126° C.) may have the advantage of avoiding or suppressing lithiation reactions that may lead to partial decomposition of the TMEDA promoter and / or DMEAH used.

[0118] Nitrogen is the [DMEA - ]xLiyHz can be "fixed" by the catalyst, i.e. It is possible that N2 can be reduced (although no evidence of this has been observed), and thus the reaction It may be advisable to remove or at least minimize N2 from the headspace and system. It is possible, but probably not necessary, to operate with other gases that are generally considered inert to the activated hydride, such as the presence of the noble gases (He, Ne, Ar) or relatively light aliphatic or cycloaliphatic hydrocarbons (hydrocarbons with boiling points close to or below the reaction temperature).

[0119] Of these inert gases, relatively light hydrocarbons are preferred (such as any C4 hydrocarbons resulting from butyllithium reagent), since such hydrocarbons are generally soluble in the reaction medium and therefore do not displace H2 as the headspace volume decreases, thereby allowing a constant The partial pressure of H2 is reduced by a significant amount during the monomer feed at a reactor pressure of Therefore, inert gases that compress in the headspace as the volume of the condensed phase increases are less desirable. However, the presence of such low solubility gases, such as noble gases, in a continuous process when the headspace volume is fixed may possibly be used to some advantage. It is difficult to operate commercial reactors at constant low positive pressures, therefore, it is necessary to operate at a constant positive pressure so that the desired H2 partial pressure, and hence activity, can be maintained at higher total reactor pressures. It may be advantageous to have low boiling (petroleum ether) hydrocarbons present. Such light hydrocarbons may even provide the added benefit of some reflux cooling means.

[0120] [DMEA - In the formation of the ]xLiyHz catalyst, TMEDA is reduced or hydrided. It may be optionally present during the formation process or may be optionally added following hydride formation. - ]xLiyHz catalyst formation under certain conditions In some cases, it may be promoted under [DMEA - ]xLiyHzEffective in promoting catalytic activity Although it may be effective, it is not essential for the formation of the catalyst. In fact, there is some evidence that the presence of even traces of TMEDA during the catalyst formation process can lead to a decrease in the catalytic activity. It seems that organolithium reagents complexed with TMEDA can undergo competitive reduction to produce Schleyer's superactive nanometer-sized LiH (Schleyer, PvR, et.al. J.Org.Chem. 1987. 52, 4299, and Schleyer, PvR, et.al. Angew Chem Int.Ed.Engl. 1986 25 465). Such nanometer LiH has been found to be extremely inefficient as a catalyst for the HMAPS process (described below), and therefore its simultaneous formation reduces the potency of the active catalyst. Thus, although not completely necessary, the [DMEA] - It is recommended to add TMEDA after the formation of the ]xLiyHz catalyst. Similarly, the catalyst formation reactor and reactor trains may be rinsed prior to use, as well as the [DMEA] by acid extraction or removal of TMEDA from the regeneration solvent. - ]xLiyHz catalyst formation stage It is recommended that some effort be made to reduce, if not eliminate, extraneous TMEDA from the reactor. - To form the ]xLiyHz catalyst, TMEDA was pretreated. It may also be advisable, although not necessary, to transfer the catalyst to the HMAPS polymerization reactor which has been charged or is to be charged with TMEDA.

[0121] In the case of using TMEDA, the molar ratio of lithium to TMEDA (lithium:TMEDA) includes ratios from about the limit (∞:1) or more practically (10,000:1) to about (1:8), or preferably about (5:1) or about (1:5), or more preferably (3:1) to about (1:3). In this context, a loading ratio of (∞:1) or more practically (10,000:1) may represent the unintentional presence of trace amounts of TMEDA promoter due to amounts left in the reactor or loading line or tank from a previous experiment in which the TMEDA was intentionally loaded. Additionally, while it is within the scope of the present invention for loading ratios of total lithium to TMEDA to exceed (1:8), such loading ratios provide little, if any, advantage and represent a wasteful use of not only the TMEDA promoter but also any reagents and / or additional efforts required to remove and / or recover the TMEDA promoter from the reactant or product mixture.

[0122] LOXLIH "DMEA - Hydrocarbon solvents that may be used to form the ]xLiyHz catalyst include Higher pK than molecular hydrogen (H2) under the reaction conditions a Non-limiting examples of such preferred solvents are cyclohexane, methylcyclohexane, with or without ethylbenzene. Other hydrocarbon solvents are also suitable. These solvents may be used so long as their use: 1) does not affect the solubility of the salt-like hydride catalyst, reactive intermediates, transient living polymer chains, and the polymer chain distribution product, or 2) when the catalyst is used in a HMSHIP or HMAPS process, the solvents may be used so long as the hydrocarbon solvent does not act as a sufficiently active organic chain transfer agent to be introduced into the HMAPS product distribution at levels of about 2 wt % or greater.

[0123] Further detailed description of the invention Another embodiment of the present application relates to a hydrogen-mediated anionic chain transfer polymerization process, which comprises feeding anionically polymerizable monomers, such as vinyl aromatic and / or styrenic monomers, under an atmosphere containing molecular hydrogen to a reaction vessel containing a reaction mixture of a hydrocarbon solvent and a hydrocarbon-soluble salt-like hydride catalyst. The soluble salt-like hydride catalyst includes LOXSH catalysts, used either separately or in combination. A preferred embodiment of the LOXSH catalyst process is to measure the kinetic chain length distribution (ν), and thus the degree of polymerization (DP n ), hence the number Average molecular weight (M n ), which are determined by the following relations or else Specified:

number

number

[0124] Accordingly, the present invention also relates to a process for anionic chain transfer polymerization with LOXSH catalyst, comprising feeding anionically polymerizable monomers (e.g., vinyl aromatic monomers and / or preferably styrenic monomers) to a reaction mixture in a reaction vessel under an atmosphere containing molecular hydrogen, the reaction mixture comprising (i) an organolithium compound and / or an organomagnesium compound, (ii) optionally a polytertiary amine compound, (iii) a polar complexing agent selected from a tertiary amino alcohol compound, a tertiary amino ether alcohol, an ether alcohol, or a combination thereof, (iv) optionally an alkali metal or metal alloy and / or a solid salt-like hydride and / or a salt-like metal amide, (v) optionally a compound having a pK of at least one C-H covalent bond, a is the pK of toluene a 2.75 pK lower than that of a From the unit viewpoint, toluene pK a -4.30pK a (vi) optionally, a vinyl aromatic monomer; and (vii) a pK a (viii) the solubility of the hydride produced from molecular hydrogen and including the catalyst or reagent is at least about 0.0080 moles per liter in a hydrocarbon solvent, which may be the same as or different from the aromatic hydrocarbon, having a high solubility in the aromatic hydrocarbon solvent;

[0125] The same non-limiting examples and amounts of components described above for forming the LOXSH catalyst and used in the catalyst and / or reagent compositions may be used in carrying out the salt-like hydride-initiated hydrogen-mediated polymerization process of the LOXSH catalyst and need not be repeated.

[0126] The hydrocarbon and aromatic hydrocarbon solvents may be the same or different. This means that the aromatic hydrocarbon can perform the functions of both the aromatic hydrocarbon and the solvent. Ethylbenzene is the preferred component in the commercial hydrogen-mediated anionic polymerization of styrene, considering that a portion of styrene is reduced to ethylbenzene, and thus ethylbenzene is the presumed component of the regenerating solvent, so long as a high degree of care, time, and energy is not required to fractionate the by-product ethylbenzene from the hydrocarbon solvent used in forming the LOXSH catalyst and in carrying out the LOXSH process of the present invention. It is also contemplated to use only ethylbenzene, in which case components (v) and (vii) are combined into one component (or constraint) and are the same with respect to the process of forming the LOXSH catalyst. It is also contemplated to use an ethylbenzene-free process using an ethylbenzene-free regenerating and / or virgin hydrocarbon solvent.

[0127] The anionically polymerizable hydrocarbon monomer may include one or more vinyl aromatic monomers, particularly styrenic monomers. Preferably, the vinyl aromatic monomer is a styrenic monomer, such as styrene, or an alkylated styrenic monomer, such as o-, m-, and p-isomers of methylstyrene, p-isopropylstyrene, 2,4-diethylstyrene, o-ethylstyrene, 3,5-diisobutylstyrene, 2,6-dimethylstyrene, 2-ethyl-4-methylstyrene, and combinations thereof. To form a linear polymer microstructure that does not contain branched molecular structures, styrene is the preferred vinyl aromatic monomer. The alkylated styrenic monomer behaves as a chain transfer agent itself under certain process conditions, resulting in some branching and potential crosslinking. Divinyl aromatic monomers such as divinylbenzene can also be used as comonomers, although branching and crosslinking may occur. Styrenic monomers such as alpha-alkylated styrenes (e.g., α-methylstyrene) generally do not homopolymerize under chain transfer conditions, but can be used as comonomers, especially with conjugated dienes. It should be noted, however, that the use of alpha-alkylated styrenes will result in the formation of quaternary carbons in the polymer microstructure. Therefore, the use of such alpha-alkylated styrenes should be avoided for styrenic polymers formed as substrates for derivatization by electrophilic aromatic substitution reactions.

[0128] The partial pressure of molecular hydrogen used in the LOXSH catalytic process is maintained at a pressure between about 0.5 and about 19.0 bar, alternatively between about 1.5 and about 12.0 bar, alternatively between about 2.5 and about 10.0 bar, alternatively between about 3.0 and about 7.0 bar.

[0129] Hydrogen partial pressures above about 10.0 bar are tolerated for some time during the process when process conditions involve normal operation with adequate mixing to maintain hydrogen transport to the condensed phase. However, such high hydrogen partial pressures for any significant period of time usually lead to hydrogenation of the monomer and substantial degradation of the molecular weight of the polymer. In contrast, hydrogen pressures below 0.1 bar (below 1.5 PSI) are tolerated during normal operation of processes involving potassium hydride form of LOXKH catalyst. Under such low hydrogen partial pressure conditions, and therefore low H activity in the condensed phase, the added Chain transfer from organic chain transfer agents, whether generated during the course of the experiment or from the HOMO chain transfer agent, competes more strongly when using LOXLiH, LOXMgH2, or combinations thereof. Feeding monomer for a short time under conditions of poor hydrogen mass transfer leads to the production of polymer chains with higher molecular weights and therefore a more asymmetric product distribution with a higher molecular weight tail (a substantial increase in the value of "M w (Reflected in 10% higher Daltons). is set so that the partial pressure reflects the condensed phase activity of molecular hydrogen, i.e., the steady state of H2 into the condensed phase. It is pointed out that this only makes sense if adequate mass transfer of molecular hydrogen to the condensed phase is maintained so that mass transfer of the state is established. Thus, much higher H2 partial pressures can be applied where mass transfer to the condensed phase is reduced due to poor mixing of the gas and condensed phases, which in turn results in poor mass transfer.

[0130] Nitrogen can be "fixed" by the salt-like hydride catalyst of the present invention, i.e., N2 is reduced. Because of the possibility that N2 may be re-introduced (although no evidence of this has been observed) and because the monomer feed reduces the reactor headspace volume when operating under semi-batch conditions, it is desirable to remove or at least minimize N2 from the reactor headspace and system. It is possible, but probably not necessary, to operate with other gases that are generally considered inert to the activated hydride, such as the presence of noble gases (He, Ne, Ar) or relatively light aliphatic or cycloaliphatic hydrocarbons (hydrocarbons having boiling points close to or below the reaction temperature). Of these inert gases, the relatively light hydrocarbons are preferred, since such hydrocarbons are generally soluble in the reaction medium and therefore can displace H2. This is because there is no significant variation in the partial pressure of H2 during the course of the monomer feed at constant reactor pressure. Compressing inert gases in the headspace is less desirable. However, the presence of such low solubility gases, such as noble gases, in a continuous process when the headspace volume is fixed may possibly be used to some advantage. It is difficult to operate commercial reactors at constant low positive pressures, therefore the desired H2 partial pressure, and hence activity, may be increased by a higher total reactor pressure. It may be advantageous to have low boiling (e.g., petroleum ether) hydrocarbons present so that the temperature can be maintained at 40° C. Such light hydrocarbons may even provide the added benefit of some reflux cooling means.

[0131] The temperature of the reaction mixture and / or process is maintained in the range of about 20°C to about 130°C, more preferably in the range of about 40°C to 110°C, and most preferably in the range of about 60°C to about 90°C.

[0132] The molar ratio of monomer to the total charge of metal hydride initially formed (monomer:metal hydride) is from about (10:1) to about (1000:1), or from about (10:1) to about (600:1), or from (40:1) to about (600:1), or from about (150:1) to about (360:1). The molar amount of metal hydride formed is considered to be equal to the molar amount of organometallic bonds, i.e., organolithium and / or organomagnesium carbon-metal bonds, but is not necessarily dependent on the pK a >H2 has a pK aIt remains after reaction under the catalyst-forming reaction conditions with all proton species having H2. Any decrease in the amount of metal hydride due to decomposition reaction is not considered, and conditions (e.g., temperature) and reagents (e.g., organic species such as certain ethers that are easily metallated and decomposed by organolithium reagents) that contribute to catalyst deactivation should simply be avoided.

[0133] In the batch or semi-batch operation of the process technology of the present invention, the monomer (e.g., styrene) is fed to the reaction medium over time, and thus the initial ratio of the monomer to the salt-like metal hydride formed at the moment when the vapor derived from the first drop or increment of the monomer is fed is mathematically close to the limit (1:∞). Therefore, the molar ratio of the total loaded monomer to the salt-like metal hydride formed first outside the described preferred range, i.e., the range from the limit (1.00:∞ to 1.00:0.101), which is the molar ratio of the monomer to the formed salt-like metal hydride of about (1:10,000 to about 9.9:1.0), is shown as the actual range at the start of each of the following examples. However, the monomer feed is usually continued until a higher desired monomer-to-metal hydride ratio is achieved. The implementation of the loaded molar ratio limited to (1:10,000 to about 9.9:1.0) is within the scope of the present invention but only shows a wasteful use of organolithium compounds and / or organomagnesium compounds.

[0134] Conversely, it becomes impossible to carry out by feeding the monomer to the salt-like metal hydride compound at a relative molar ratio initially exceeding about 1000:1. That is, it results in a decrease in chain transfer and produces a composition with an unfavorable molecular weight distribution (MWD). The process catalyzed by LOXLiH is a more preferred process for both the ease of formation of the medium and the selectivity regarding the microstructure, and ultimately for the catalytic activity. In Examples 14 and 15, it has been demonstrated that a catalytic efficiency of 15,000% can be achieved using a monomer:metal hydride loading ratio of >600:1. With the combination of these two experiments, M =730 with PD w =730 with PD nA dimer-free polymer distribution characterized as having an .alpha.=1.4 was produced in 75% isolated yield.

[0135] For the LOXSH process, the polytertiary amine (PTA) accelerator is optional. Thus, when a monomeric PTA composition is used, the PTA accelerator is used in a molar ratio of the sum of the alkali metal and alkaline earth metal to PTA (metal:PTA) of about (∞:1) or more practically (10,000:1) to about (1:8), or preferably about (5:1) or about Preferably, the PTA promoter is present in a ratio of (1:5) or even more preferably (3:1) to about (1:3). In this regard, it is understood that a loading ratio of (1:∞) or more practically (10,000:1) may represent the unintentional presence of trace amounts of PTA promoter due to amounts left in the reactor or loading lines or tanks from a previous experiment in which the PTA was intentionally loaded. Furthermore, while it is within the scope of the present invention for total metal to PTA loading ratios in excess of (1:8), such loading ratios provide little, if any, advantage and represent a wasteful use of not only the PTA promoter but also any reagents and / or additional effort required to remove and / or recover the PTA promoter from the reactant or product mixture.

[0136] The monomer feed rate relative to the catalyst amount is governed by the polydispersity of the polymer composition, i.e., PD n ,fire For details, please see M n , M w , M z , P.D. n , number average standard deviation (σ n ), and asymmetry ( n α3) value Therefore, at a given H activity (or partial pressure), for a given reactor design or configuration, It is prudent to feed the monomers in a certain relative ratio. It should be clear that a very low relative feed rate of monomer to catalyst (i.e., less than about 15 moles of monomer / hour / mol active Li) will result in undesirable levels of reduced (essentially hydrogenated) monomer and some dimers. Furthermore, the resulting compositions have high asymmetry values, which are less desirable. On the other hand, very high relative feed rates usually result in higher molecular weight distributions, and such compositions can otherwise be produced economically with little or no chain transfer. Since the molecular formulas of the LOXSH catalysts are not necessarily determined, and are not necessarily completely defined due to the formation of aggregates, nor are the molecular weights of the aggregates of these catalysts known, the feed rate of monomer (styrene) per hour to the catalyst is still expressed in terms of the amount of active hydride formed in the catalyst composition. It is assumed that each equivalent mole of active organolithium alkyl and / or active organomagnesium alkyl forms one equivalent mole of salt-like hydride, with the organolithium compound providing one equivalent and the organomagnesium providing two equivalents. Thus, in the practice of the present invention, the hourly feed rate of monomer to the salt-like hydride compound should be in the range of about 10 to about 500 moles of monomer per mole of activated salt-like hydride reagent charged to the reactor, or more preferably, in the range of about 65 to about 380 moles of monomer per mole of salt-like hydride initially generated in the reactor, per hour. Again, an equivalent mole of salt-like hydride is considered to be equal to the molar equivalent of activated organolithium alkyl and / or activated organomagnesium alkyl initially charged. Again, a molar equivalent of activated organolithium alkyl and / or activated organomagnesium alkyl refers to a molar equivalent of activated organolithium alkyl and / or activated organomagnesium alkyl having a lower pK than H2 contained in the reaction mixture. a By this term is meant the amount of organolithium alkyl and / or magnesium alkyl radical remaining after reaction with any and all proton species having the formula:

[0137] The temperature of the reaction mixture during the monomer feed is maintained in the range of about 20° C. to about 130° C., or in the range of about 40° C. to about 99° C., or in the range of about 60° C. to about 90° C. It is contemplated that higher temperatures may be used during the entire experiment or for portions of the experiment, but without the need for any modification of the catalyst. Temperatures that promote the decomposition of the hydride from the polymer chain and / or the formation of unsaturated terminated chain lengths should be avoided. The amount of such hydride elimination termination reactions should vary with temperature and catalyst composition. In the formation of the LOXSH catalyst and during the initial heating process, the catalyst can be mixed at a temperature just above the melting point of the hydrocarbon solvent (or solvent mixture) or the freezing point of the monomers fed. Mixing the catalyst components at low temperatures (i.e., -10 to 15°C) and even under cryogenic conditions (-10 to -126°C) may have the advantage of avoiding or suppressing lithiation or other metallation reactions that may lead to partial decomposition of the polytertiary amine promoter and / or polar complexing agent used. However, conditions that lead to precipitation of the salt-like hydride catalyst or its precursor complexes and reagents should probably be avoided.

[0138] The desired level of dispersion of monomer in the reaction medium depends on the efficiency with which hydrogen is transported from the gas phase and / or from the hydrogen gas feed to the condensed phase throughout the course of the experiment. Ideally, commercial, pilot, and even bench scale reactors can be designed and constructed such that hydrogen transfer from the gas phase to the condensed phase is essentially uniform throughout the course of the monomer feed. Under such uniform hydrogen transport between the phases, it is desirable to minimize reduction of the monomer to its saturated analog by feeding the monomer such that there is a locally high concentration in the reactor. In bench or small pilot scale reactors, such locally high monomer concentrations are achieved by using relatively low feed rates and very high relative monomer to catalyst feed rates and feed ratios. In large commercial units, the monomer is fed to a reaction section that can be physically separate or distinct from the bulk of the reaction mixture (i.e., a pump-around loop). Nevertheless, the advantage of the LOXLiH catalyst generated from 2-[2-(dimethylamino)ethoxy]ethanol (DMAEOE), a salt-like hydride catalyst in these HMSHIP processes of the present invention, is that such catalyst appears to be very stable under the process conditions, does not reduce catalytic activity, and does not introduce impurities from the polytertiary amine promoter or aminoalkoxide polar complexing agent used. Under these conditions, the production of reduced monomers is kept well below 10% of the total monomer charge. The dimer content can also be kept below 12% of the product distribution, and thus the trimer and higher yields can be well above 80%-90% of the monomer charge.

[0139] For example, at constant heat flux, this is indicated by a sudden drop in process temperature and / or cessation of H2 uptake. Upon completion of the monomer feed and reaction of the LOXSH catalysis process, the reaction mixture is maintained under hydrogen pressure and then transferred to a wash reactor for quenching and water washing. The wash reactor is charged with water (with or without mineral acid such as H2SO4 and / or organic acid such as acetic acid). In addition, the wash reactor may be pre-charged with any additional amount of solvent, preferably a hydrocarbon solvent. Quenching can be carried out with cooling or at ambient temperature up to the temperature at which the hydrocarbon solvent forms an azeotrope with water under the pressure conditions of the wash reactor. The product is water washed to remove at least a portion of the alkali metal salts and PTA promoter, if present, as well as the polar complexing agent. Under very acidic conditions, such reagents are almost completely removed along with the alkali metal salts and alkaline earth metal salts resulting from the acid. Under basic conditions, where up to an equivalent amount of acid is used, the PTA promoter and polar complexing agent, if present, are distributed between the organic reaction mixture and the aqueous wash. Washing is continued until the desired pH of the outlet wash water is obtained. Under basic conditions, a pH between 9 and 11 indicates that all of the alkali and alkaline earth metal salts have been removed. Under acidic conditions, a pH between 6 and 8 (depending on the alkalinity of the wash water) indicates that all of the acidic species have been removed or at least neutralized.

[0140] When washing is deemed complete, the solvent and any remaining portion of the polytertiary amine promoter and any remaining polar complexing agent (if present), as well as the reduction products of the monomer, are preferably separated and recovered from the reaction mixture, thereby removing the last traces of water from the reaction mixture. The dimers are removed azeotropically from the monomers. This separation operation should be continued until the resulting product mixture contains less than about 0.1 wt.% of the reduction products of the monomers. Further modification and shaping of the product distribution by reducing the monomer dimer content is desirable for some applications. For the higher boiling dimers, this is easily accomplished using a wiped film evaporator.

[0141] The present invention relates to a method for the hydrogen mediated anionic polymerization (HMAPS) of styrene which, under certain preferred conditions, results in the formation of novel and advantageous low molecular weight anionic chain transfer polymer distributions with extremely pure, "head-to-tail" microstructure and low asymmetry in high yield. The method comprises reacting styrene monomer with [DMEA - ] x Li y H z The method is characterized in that a suitable solvent containing a catalyst is supplied under an atmosphere containing molecular hydrogen, where chain transfer from the molecular hydrogen results in a number average molecular weight (M n ) is an important component of the mechanism that determines the number-average distribution of HMAPS products. The molecular weight is given by the formula:

number

[0142] The present invention also relates to an anionic chain transfer polymerization process which comprises adding vinyl aromatic monomers and / or preferably styrenic monomers to a reaction mixture having the formula [DMEA - ] x Li y H z(ii) optionally a TMEDA compound; (iii) about x equivalents of dimethylaminoethanol; (iv) optionally ethylbenzene; and (v) a hydrogen mediated chain transfer polymerization catalyst having a pK greater than that of H. a and (vi) molecular hydrogen, the amount of hydride produced, z, is given by the formula z=yx, where x, y, and z are positive real integers or fractions greater than zero, which formula further represents an N,N,N',N'-tetramethylethylenediamine (TMEDA) ligand complex, i.e., [DMEA - ] x Li y H z ·XTMEDA, TMEDA, catalyst [DMEA - ] x Li y H z The compound can be present in a molar ratio X per mole of the compound, where X=0.0001 to about 8.0.

[0143] Thus, the present invention further relates to a HMAPS process for anionic chain transfer polymerization, which comprises feeding styrene monomer to a reaction mixture in a reaction vessel under an atmosphere containing H2. The reaction mixture comprises a compound having the formula [DMEA - ] x Li y H z (i) about y equivalents of an organolithium compound and / or an organomagnesium compound; (ii) optionally a TMEDA compound; (iii) about x equivalents of dimethylaminoethanol; (iv) optionally ethylbenzene; (v) a pK a and (vi) molecular hydrogen, wherein the amount of hydride produced, z, is given by the formula z=yx, where x, y, and z are positive real integers or fractions greater than zero, and the solubility of the hydride containing catalyst or reagent is at least about 0.0080 moles per liter.

[0144] [DMEA - ] x Li y H z For forming catalysts and for use in said catalyst and / or reagent compositions The same non-limiting examples and amounts of the above ingredients are included in the [DMEA - ] x Li y H z may be used to carry out the HMAPS step of step 1 above, and does not need to be repeated.

[0145] Hydrocarbon solvents that may be used have a higher pK than molecular hydrogen (H2) under the reaction conditions. a The solvent is any hydrocarbon having a molecular weight of 0.01 to 0.01 wt.%. Non-limiting examples of such preferred solvents are cyclohexane, methylcyclohexane, with or without ethylbenzene. Other hydrocarbon solvents can be used as long as their use: 1) does not affect the solubility of the salt-like hydride catalyst, reactive intermediates, transient living polymer chains, and the polymer chain distribution product, or 2) does not act as a sufficiently active organic chain transfer agent to be introduced into the HMAPS product distribution at levels of 2 wt.% or greater.

[0146] In carrying out the HMAPS process of the invention to produce the most desirable HMAPS distribution of the invention, the monomer feed to lithium hydride generally ranges from about (10:1) to about (1000:1), preferably from about (50:1) to about (800:1), and most preferably from (100:1) to about (600:1), and depending on the total amount of styrene monomer fed, the lithium hydride concentration in a semi-batch operation of the process is from about 200 ppm to about 750 ppm at the start of the experiment and from about 65 ppm to about 350 ppm at the end of the experiment. In a continuous mode of operation, it is preferred to operate the process so that the lithium hydride concentration is between about 200 ppm and about 500 ppm throughout the course of the operation.

[0147] In the batch or semi-batch operation of the process technique of the present invention, the monomer (i.e., styrene) is fed to the reaction medium over time, and thus the vapor from the first drop or increment of monomer is formed at the moment it is fed. - ]xLiyHz catalyst model The initial ratio of monomers to the resulting [DMEA] is mathematically close to the limit (1:∞). Thus, the molar ratio of total monomers charged to initially formed salt-like lithium hydride outside the preferred range described, i.e., from the limit (1.00:∞ to 1.00:0.101), is about (1:10,000 to about 9.9:1.0). - ]xLiyHz touch The molar ratios of the catalyst are given as practical ranges at the start of each of the examples below. However, the monomer feed is usually continued until the higher desired monomer to lithium hydride ratio is reached. It is within the scope of the invention to practice charge molar ratios limited to (1:10,000 to about 9.9:1.0), but [DMEA - ]xLiyHz Used to form the catalyst This simply represents a wasteful use of organolithium compounds.

[0148] Conversely, the monomers may be initially mixed in a relative molar ratio of greater than about 1000:1 with [DMEA - ]xL Feeding to iyHz catalysts can be rendered impractical by viscosity levels, i.e., resulting in reduced chain transfer and producing compositions with poor molecular weight distribution (MWD). [DMEA - The process technology catalyzed by ]xLiyHz is characterized by the ease of formation of the catalyst, the microstructure The catalyst is characterized by high selectivity, and ultimately high catalytic activity. In Examples 14 and 15, it is demonstrated that a catalytic efficiency of 15,000% can be achieved with a monomer:lithium hydride loading ratio of >600:1. The combination of these two experiments shows that M w =730P D n = 1.4, resulting in an isolated yield of 75% dimer-free polymer distribution. was produced at a rate of

[0149] [DMEA - The amount of monomer fed relative to the amount of catalyst varies depending on the polymer composition. Dispersibility, i.e., PDn, and therefore M n , M w , M z , P.D. n , number average standard deviation (σ n ) , and asymmetry ( n α3) is the decisive reaction rate factor for setting the overall molecular weight distribution (MWD) as measured by the value of α3. Thus, at a given H2 activity (or partial pressure), It is prudent to feed monomers in certain relative ratios in the reactor design or configuration. It should be clear that a molar activity of Li below 1000 mol / L will result in undesirable levels of reduced (essentially hydrogenated) monomer and some dimer. Furthermore, the resulting compositions have less desirable high asymmetry values. On the other hand, higher relative feed rates generally result in wider molecular weight distributions and lower ethylbenzene and styrene dimer yields. w The HMAPS composition in the range of 850-1050 is low in ethylbenzene (4%-6%). After removal of the dimers (obtained in high yields of 8% to 12%) and the tetramers (obtained in low yields of 8% to 12%), it can be readily prepared in yields of about 82% to about 90%.

[0150] The temperature of the reaction mixture during the monomer feed is maintained in the range of about 20° C. to about 130° C., or in the range of about 40° C. to about 99° C., or in the range of about 60° C. to about 90° C. It is contemplated that higher temperatures may be used during the entire experiment or portions of the experiment, but temperatures that promote any decomposition of the catalyst and / or cause hydride elimination from the polymer chains and the formation of significant levels of unsaturated terminated chain length distribution should be avoided. The amount of such hydride elimination termination reactions may vary depending on temperature and catalyst composition.

[0151] The desired level of dispersion of monomer in the reaction medium depends on the efficiency with which hydrogen is transported from the gas phase and / or from the hydrogen gas feed to the condensed phase throughout the course of the experiment. Ideally, commercial, pilot, and even bench scale reactors can be designed and constructed such that hydrogen transfer from the gas phase to the condensed phase is essentially uniform throughout the course of the monomer feed. Under such uniform hydrogen transport between the phases, it is desirable to minimize the reduction of the monomer to its saturated analog by feeding the monomer such that there is a locally high concentration in the reactor. In bench or small pilot scale reactors, such locally high monomer concentrations are achieved by using relatively low feed rates and very high relative monomer to catalyst feed rates and feed ratios, controlled by the feed rate (volume / second) and the area over which the monomer is fed (set by the radius of the cylindrical feed tip) (i.e., cc / second divided by square cm). In large commercial equipment, the monomer can be fed to a reaction section that can be physically separate from or distinct from the bulk of the reaction mixture (i.e., pump-around loop). [DMEA - ] x Li y H z The catalyst has the advantage that such catalyst appears to be very stable under the process conditions and does not reduce the catalytic activity and thus does not result in the formation of impurities from the polytertiary amine promoter or aminoalkoxide polar complexing agent used. Under HMAPS process conditions, the formation of reduced ethylbenzene is maintained well below 10% of the total monomer charge. The dimer content can also be maintained below 12% of the product distribution. The yield of HMAPS distribution with styrene dimer content removed to less than 2%, preferably less than 1%, thus containing >98% trimers and above can be well above 80% to 90% of the total monomer charge.

[0152] Once the components have been mixed with the catalyst in the desired charge ratio and further activated if necessary, the catalyst is ready for use in the hydrogen-mediated anionic polymerization process of the present invention. Thus, styrene monomer is reacted with [DMEA] under a hydrogen partial pressure of between about 0.001 and about 10.0 bar, or about 0.3 and about 6.8 bar, or about 0.5 and about 5.2 bar, or about 1.0 and about 4.2 bar. - ]xLiyHz catalyst composition. Hydrogen partial pressures above about 10.0 bar are , which are tolerated for a period of time during the process with proper mixing under normal operation of the process conditions to maintain hydrogen transfer to the condensed phase. However, such high hydrogen partial pressures for any significant period of time usually lead to hydrogenation of the monomers with substantial reduction in the molecular weight of the polymer and increased yield of ethylbenzene. Conversely, hydrogen pressures below about 0.1 bar (below 1.5 PSI) are tolerated during normal operation of the process, but result in highly asymmetric compositions with a very high molecular weight tail having a 10% higher molecular weight than about 2000 Daltons as measured by GPC. The formation of such highly asymmetric compositions also occurs when reaction conditions provide poor mass transfer of hydrogen to the condensed phase. The production of such high molecular weight tails as a feature of the product molecular weight distribution can be attributed to feeding monomers for short periods of time under inadequate mixing conditions that produce a highly viscous reaction medium. This high viscosity makes the mass transfer of hydrogen increasingly inefficient, resulting in even higher viscosities. Reaction conditions that can result in high viscosity are: 1) reaction temperature, and / or 2) less than optimal catalyst concentration, and / or 3) less than optimal monomer to catalyst loading ratio, and / or 4) locally too high monomer concentration, and / or 5) feed duration when mixing becomes inefficient due to poor reactor geometry / design. Thus, the partial pressures above should be adjusted so that they reflect the condensed phase activity of molecular hydrogen, i.e., the steady state flow of H2 into the condensed phase. It is pointed out that this is only meaningful if adequate mass transfer of molecular hydrogen to the condensed phase is maintained so that mass transfer of H2 is established. Therefore, much higher H2 Partial pressure can be applied, however, if the viscosity becomes too great, increased mixing usually leads to foaming and even less efficient mass transfer to the condensed phase.

[0153] For example, at constant heat flux, this is indicated by a sudden drop in process temperature and / or cessation of H2 uptake. [DMEA - Styrene monomer supply and reaction in the ]xLiyHz catalyzed HMAPS process Upon completion of step 1, the reaction mixture is maintained under hydrogen pressure and then transferred to a wash reactor for quenching and water washing. The wash reactor is charged with water ( H2 (with or without mineral acids such as SO4 and / or organic acids such as acetic acid). Additionally, the wash reactor may be pre-charged with any additional amount of solvent, preferably a hydrocarbon solvent. Quenching can be carried out with cooling or at ambient temperature below the temperature at which the hydrocarbon solvent forms an azeotrope with water under the pressure conditions of the wash reactor. The product is water washed to remove the alkali lithium salts and at least a portion of the TMEDA promoter, if present, as well as the polar complexing agent. Under very acidic conditions, such reagents are almost completely removed along with the alkali and alkaline earth lithium salts resulting from the acid. Under basic conditions, where less than an equivalent amount of acid is used, the TMEDA promoter and DMEAH reagent, if present, are distributed between the organic reaction mixture and the aqueous wash. Water washing is continued until the desired pH of the outlet wash water is obtained. Under basic conditions, a pH of 9 to 11 indicates that all the alkali and alkaline earth lithium salts have been removed. Under acidic conditions, a pH of 6 to 8 (depending on the alkalinity of the wash water) indicates that all of the acidic species have been removed or at least neutralized. Under acidic wash conditions, it may sometimes be desirable to add a small amount (20 mg for a 2 liter run) of a surfactant, such as sodium dodecyl sulfate, to break up emulsion or micelle formation.

[0154] When washing is deemed complete, the solvent and any remaining polytertiary amine promoter and any remaining polar complexing agent (if present), as well as the ethylbenzene by-product, are preferably separated and recovered from the reaction mixture, whereby the last traces of water are azeotropically removed from the reaction mixture. This separation operation should be continued until the resulting product mixture has an ethylbenzene by-product content of less than about 0.1 wt.%. Modification by essentially complete removal of ethylbenzene is accomplished by reducing the styrene dimer content, preferably by distillation in a wiped film evaporator, and further shaping the HMAPS distribution.

[0155] Compared with other prior art (e.g., EPO 741147), the HMAPS process, characterized by its ability to form lithium alkoxides in situ, is convenient for laboratory use and advantageous for large-scale commercial use in the formation of hydrocarbon-soluble salt-like metal hydride catalysts. Thus, in the formation of LOXLiH and LOXMgH2 catalysts, lithium and Forming a magnesium alkoxide reagent precursor: (1) avoids the handling of flammable air and moisture reactive solids, (2) eliminates dissolving metal alkoxides in concentrates of large molar excesses of poly-tertiary amine promoters, (3) eliminates the need to remove traces of by-product alcohol from process streams prior to regeneration of solvents and other reagents, and (4) greatly reduces, and in some embodiments eliminates, the amount of poly-tertiary amine promoter required. Both the iH and LOXMgH2 catalysts are capable of forming It appears that the LOXLiH and LOXMgH2 catalysts are homogeneously dissolved, thus improving run-to-run variability substantially, i.e., more reproducible, thus resulting in a much more robust commercial process than the SASH process of Examples 38 and 39 or the HASH process of Example 40. The LOXLiH and LOXMgH2 catalysts also provide a high degree of adhesion to the walls and internal components of polymerization reactors and other related equipment. It appears to leave little, if any, substantial amount of objectionable solids behind. Deposition of insoluble catalyst on reactor surfaces is a significant problem with prior art organic chain transfer processes in which the catalyst is formed from reagents such as n-butyllithium, potassium tert-butoxide, TMEDA, and ethylbenzene under an inert atmosphere such as nitrogen.

[0156] LOXLiH and LOXMgH2 catalysts and their catalysis of hydrogen-mediated anion chain transfer An incidental advantage of the process is that these catalysts and processes give pure chain-transferred polystyrene compositions with a microstructure free of impurities or impurity distributions of fragmentation polymerization and chain isomerization. This was experimentally verified by gas chromatographic analysis of the first 4-6 oligomers (see Figures 3 and 4, which compare the microstructure of LOXLiH PS oligomers with that of oligomers derived from ethylbenzene chain-transferred PS of the prior art). The LOXKH catalytic process as well as the HASH and SASH processes generally produce polystyrene compositions with less desirable microstructures (see Figures 5-7), which are also common to the prior art (see also Figures 12-14). Thus, LOXLiH PS and LOXMgH2PS compositions are free from further reactions such as aromatic electrophilic substitution carried out on the product distribution. This is highly advantageous in the formation of commercial products derived from chemistry. It will be appreciated that, with further experimentation and by judicious selection of the amino alcohol component of the catalyst, including optically active amino alcohols, practitioners of the present invention may find ways to control other microstructural features, such as the tacticity, of vinyl aromatic polymers.

[0157] [ka] Thus, another embodiment of the present invention is an anionic chain transferred styrenic polymer distribution initiated with a salt analog hydride having a polymer microstructure that is greater than 97% head-to-tail microstructure, more preferably greater than 98% head-to-tail microstructure, and most preferably greater than 99% head-to-tail microstructure, as shown in the polystyrene structure 12 of the above polymer (specific to, but not limited to, styrene). In other words, the anionic chain transferred styrenic polymer composition of the present invention is initiated via the addition of a salt analog hydride to a styrenic monomer and has a chain length distribution in which less than 3.0%, more preferably less than 2.0%, and most preferably less than 0.8% of the polymer chains have one or more quaternary carbons in the polymer microstructure. Furthermore, said distribution of said hydride-initiated poly(styrenic) structures (again, specific to but not limited to styrene) 12 contains less than 3%, more preferably less than 2%, and even more preferably less than 1%, and most preferably less than 0.2% to below the detection limit of chain length distribution(s) as by-product distribution(s) resulting from the cleavage polymerization process, where the microstructure and purity of said chain length distribution is hereinafter determined by gas chromatographic analysis of the lowest molecular weight chains obtained from said hydrogen-mediated salt-like hydride-initiated polystyrene or poly(styrenic) or poly(vinyl aromatic) distribution of said polymer structures n=0 to n=4.

[0158] The most preferred initially generated hydrogen-mediated salt-analog hydride initiated styrenic distribution is derived from styrene monomer and hydrogen only and has the chain length distribution of structure (12) above. The chain length distribution consists of i-1 individual polymer chain lengths in a statistical number average distribution of relative molar content, where i is the total number of monomers incorporated into a given individual polymer chain. The number i is a positive integer between i=2 and i=i. Thus, (chain-1)n=0 (styrene dimer) if i=2, (chain-2)n=1 (styrene trimer) if i=3, (chain-3)n=2 (styrene tetramer) if i=4, (chain-4)n=3 (styrene pentamer) if i=5, (chain-5)n=4 (styrene hexamer) if i=6, ... and (chain-(i-1))n=i-2 if i=i. Thus, the (i-1)th individual polymer chain is the individual polymer chain with the longest chain length. We have found that, in general, the results of GPC MWD analysis for the polymer compositions of the present invention can be reasonably modeled with a gamma probability density function (PDF). However, more importantly, we have found that compositions resulting from catalysts other than monometallic lithium-based LOXLiH catalysts are generally more accurately modeled with a beta PDF. Most importantly, the GPC MWD results for LOXLiH PS are accurately modeled with a Weibull PDF, i.e., this may indicate that for LOXLiH catalyzed systems, the molecular weight distribution is determined solely by chain transfer without significant regeneration of dead polymer chains, as well as the activation, participation, and incorporation of ethylbenzene as an organic chain transfer agent in the generation of the polymer distribution.

[0159] When styrene is the monomer, the molecular weight distribution of the chain length distribution of the present invention is M n 315~93 4 Daltons range, M w is in the range of about 392 to about 1705 daltons, and M z ranges from about 512 to 2930 daltons, and PD n is in the range of 1.24 to 1.82, More preferably, the composition has a standard deviation in the range of 156 to 849 Daltons and an asymmetry in the range of 1.40 to about 3.00. n 410-680 Daltons In the range of M w is in the range of about 553 to about 1205 daltons, and M z is in the range of about 745 to 1950 Daltons, and PD n is in the range of 1.29 to 1.82, and the standard deviation The most preferred compositions have a molecular weight distribution with a difference in the range of 257 to 600 Daltons and an asymmetry in the range of 1.50 to about 2.60. n in the range of 444 to 683 Daltons Yes, M w is in the range of about 600 to about 1150 daltons, and M z is in the range of about 798 to 1768 Daltons, and PD n is in the range of 1.35 to 1.68 with a standard deviation of 26 It has a molecular weight distribution in the range of 3 to 565 Daltons and an asymmetry in the range of 1.50 to about 2.31.

[0160] Preferred unblended compositions of the present invention are those consisting essentially of, if not exclusively, styrene, having a "head-to-tail" microstructure of greater than 97 wt%, and whose chain length distributions have been further shaped or modified by the removal of a portion of the lowest molecular weight chains. Removal of low molecular weight chains, particularly styrene dimers, i.e., removing the lowest value(s) or a portion of the lowest value(s) from an arithmetic average of all other (e.g., grade point average), results in a new average with an increased overall molecular weight distribution. Thus, the preferred modified molecular weight distributions of the present invention overlap with the unmodified distribution, but may not be within the molecular weight distributions or molecular weight parameters specified above, simply due to the numerical results altered by the removal of a portion of the lower molecular weight fraction of the distribution. Thus, preferred compositions having reduced but still present dimer content, representing about 0.1 to about 1.0 wt% of the overall distribution (as measured by GPC analysis), have a Mn 40 7 to 1018 Daltons, M w is in the range of about 487 to about 1741 Daltons. , M z ranges from about 579 to 2938 Daltons, and PD n More preferred compositions have a molecular weight or chain length distribution with a M in the range of 1.40 to 1.71, a standard deviation in the range of 180 to 858 daltons, and an asymmetry in the range of 1.31 to about 3.016. n is in the range of 494 to 788 Daltons, and M w is in the range of about 623 to about 1278 daltons, and M z is in the range of about 782 to 1964 Daltons, and PD n is 1.26 to 1.62 The most preferred compositions have a molecular weight distribution in the range of M with a standard deviation in the range of 253 to 621 Daltons and an asymmetry in the range of 1.40 to about 2.40. n 5 The range is 21 to 737 Daltons, M w is in the range of about 661 to about 1202 Daltons. , M z is in the range of approximately 827 to 1783 Daltons, and PD n The molecular weight distribution has a mean diameter in the range of 1.27 to 1.63, a standard deviation in the range of 270 to 586 daltons, and an asymmetry in the range of 1.40 to about 2.50.

[0161] The blending operation, in which statistical distributions are combined, is called PD n The constraints specified for This may result in a non-statistical distribution where standard deviation is not applicable, however such blends are within the scope of the present invention in that they are produced by combination of the compositions of the present invention and result from the present invention.

[0162] [ka] Therefore, another embodiment of the present invention is a LOXLIH PS distribution called the HMAPS distribution. n ≈[styrene] / [H2] and the relative feed rates of styrene to catalyst at a given catalyst composition, catalyst concentration, and hydrogen pressure. w and M z The HMAPS distribution is initiated by lithium hydride and terminated by protons from the hydrogen, and has a polymer microstructure that is greater than 97% head-to-tail microstructure, more preferably greater than 98% head-to-tail microstructure, and most preferably greater than 99% head-to-tail microstructure, as shown in polystyrene structure 12 of the polymer above. In other words, the HMAPS polymer composition of the present invention is initiated via the addition of lithium hydride to styrene monomer and has a chain length distribution in which less than 3.0%, more preferably less than 2.0%, and most preferably less than 0.8% of the polymer chains have one or more quaternary carbons in the polymer microstructure. Furthermore, the HMAPS distribution of the above 12 contains less than 3%, more preferably less than 2%, and even more preferably less than 1%, and most preferably less than 0.2% to below the detection limit of chain length distribution(s) as by-product distribution(s) resulting from the cleavage polymerization process, in which case the fine structure and purity of the chain length distribution is determined below by gas chromatography analysis of the lowest molecular weight chain obtained from the HMAPS distribution of n=0 to n=2 of the above polymer structure 12.

[0163] The most preferred initially generated HMAPS distribution has a chain length distribution consisting of i-1 individual polymer chain lengths in a statistical number-averaged distribution of relative molar contents, where i is the total number of monomers incorporated into a given individual polymer chain. The number i is a positive integer between i=2 and i=i. Thus, i=2 if (chain-1)n=0 (styrene dimer), i=3 if (chain-2)n=1 (styrene trimer), i=4 if (chain-3)n=2 (styrene tetramer), i=5 if (chain-4)n=3 (styrene pentamer), i=6 if (chain-5)n=4 (styrene hexamer), ... and i=i if (chain-(i-1))n=i-2. Thus, the (i-1)th individual polymer chain is the individual polymer chain with the longest chain length. We have found that, in general, the results of GPC MWD analysis for the polymer compositions of the present invention can be reasonably modeled with a gamma probability density function (PDF). More importantly, however, we have found that HMAPS distributions are generally very well modeled with a Weibull PDF, which indicates that the polymerization process is nearly, if not exclusively, hydrogen-mediated: i) initiation, ii) chain propagation, and iii) chain termination stages. That is, ethylbenzene is interpreted to mean that it is not kinetically active as a chain transfer agent.

[0164] The molecular weight distribution of the HMAPS composition of the present invention was characterized by GPC (UV detector) analysis, n is in the range of 400-800 Daltons, and M w is in the range of about 600 to about 1200 daltons, and PD n is in the range of about 1.35 to about 1.75, and the standard deviation is about 270 to about 55 0 Daltons, M w 10% higher is less than about 3300 daltons. More preferred The composition is a HMAPS polymer, the distribution of which is characterized as determined by GPC (UV detector) analysis, M n is in the range of about 400 to about 800 daltons, and M w is in the range of about 600 to about 1200 daltons, and M zis in the range of about 750 to about 1500 daltons, and P D n is in the range of about 1.35 to about 1.75, with a standard deviation of about 270 to about 550 daltons. The asymmetry is in the range of about 1.60 to about 2.2, and M w 10% higher is about 2400 Less than Dalton.

[0165] The preferred HMAPS distributions of the present invention consist essentially of, if not exclusively, styrene and have a "head-to-tail" microstructure of greater than 97 wt. % and their chain length distributions are further shaped or modified by the removal of a portion of the lowest molecular weight chains. The removal of low molecular weight chains, particularly styrene dimers, significantly reduces the magnitude of each moment of the molecular weight distribution (i.e., M n , M w , and M z ) to new highs, and overall Thus, the preferred modified molecular weight distributions of the present invention overlap with the unmodified distributions, but may not be within the molecular weight distributions or molecular weight parameters specified above, simply as a result of the numerical modification by the removal of a portion of the lower molecular weight fraction of the distribution. Thus, the preferred HMAPS compositions, having a reduced but still present dimer content, representing about 0.1 to about 1.5 wt % of the total distribution (as measured by GPC analysis UV detector), have a reduced but still present dimer content, representing about 0.1 to about 1.5 wt % of the total distribution. n is in the range of about 500 to about 800 daltons, and M w is in the range of about 650 to about 1200 daltons, and M z is in the range of about 900 to about 1500 daltons, and P D n The range of the mean is about 1.25 to about 1.70, and the standard deviation is about 280 to about 600 da The asymmetry is in the range of about 1.45 to about 3.20, and the M w 10% higher It has a molecular weight distribution or chain length distribution that ranges from about 1500 daltons to about 3500 daltons.

[0166] The blending operation, in which statistical distributions are combined, is called PD n The constraints specified for This may result in a non-statistical distribution where standard deviation is not applicable, however such blends are within the scope of the present invention in that they are produced by combination of the compositions of the present invention and result from the present invention.

[0167] Thus, the present invention also relates to a polymeric flame retardant composition produced by electrophilic aromatic bromination of a pure polystyrene composition. The brominated polystyrene composition is prepared by a process involving bromination with bromine and a bromination catalyst in a solvent for polystyrene compositions produced by salt-analog hydride-initiated hydrogen-mediated anionic polymerization of styrene monomers, or other known bromination processes. Thus, the present invention provides a flame retardant composition comprising a brominated polystyrene of the above HMAPS distribution, which composition has: (i) a bromine content in the range of about 73 wt% to about 77 wt%, (ii) a thermal HBr value at 300°C below the detection limit of 50 ppm and below about 1000 ppm, where the wt% and ppm values ​​are based on the total weight of the composition, a 5% thermogravimetric (TGA) weight loss occurs at a temperature of greater than about 355°C to about 375°C, and a glass transition temperature in the range of about 110°C to about 155°C.

[0168] Components referred to anywhere in this specification or claims by chemical name or formula, whether referred to in the singular or plural, are considered to be present prior to contact with another substance referred to by its chemical name or chemical type (e.g., another component, solvent, etc.). The resulting mixture or solution is subjected to a chemical reaction or transformation, if any. It is not a problem if such a chemical change, transformation, and / or reaction occurs in the resulting mixture or solution, since such a change, transformation, and / or reaction is a natural consequence of bringing together the particular ingredients under the conditions required in accordance with the present disclosure. The ingredients are therefore considered to be ingredients that are to be brought together in connection with carrying out a desired operation or producing a desired composition. Also, although the following claims may refer to substances, ingredients, and / or ingredients in the present tense (such as "comprising," "is," etc.), the reference is to the substances, ingredients, or ingredients as they existed immediately prior to being first contacted, blended, or mixed with one or more other substances, ingredients, and / or ingredients in accordance with the present disclosure. The fact that a substance, ingredient, or ingredient may have lost its original identity through chemical reaction or transformation during the course of a contacting, blending, or mixing operation is of no practical concern when performed in accordance with the present disclosure and using the ordinary skills of a chemist.

[0169] The present invention described and claimed herein is not limited in scope by the specific examples and embodiments disclosed herein, since these examples and embodiments are intended to be illustrative of certain aspects of the invention. Any equivalent embodiments are intended to be within the scope of the invention. Indeed, various modifications of the invention in addition to those shown and described herein will become apparent to those skilled in the art from the foregoing description. Such modifications are also intended to be included within the scope of the appended claims.

[0170] The invention is illustrated by the following examples, however it should be understood that the invention, which is fully described and claimed herein, is not intended to be limited by the details of the following examples. EXAMPLES

[0171] Common equipment used The equipment used in the HMSHIP process is as follows: A 2-liter Parr autoclave made of 316 stainless steel equipped with a thermocouple, bottom drain valve, cooling coil, hot oil jacket, and either two, three, or four pitched blade turbine impellers (with each impeller configuration shown below and specified in the Examples) was further fitted with a piston pump, a diaphragm pump, a nitrogen purged 250 ml stainless steel charge vessel, a fully calibrated high pressure metering pump, and a 1 / 16" OD subsurface monomer feed line with either 0.02", 0.01", or 0.007" ID end section (as indicated or otherwise described in the Examples). The agitator magnetic device was connected to a high speed air driven motor and operated during polymerization such that the agitator impeller typically rotated at a speed of 1130±25 RPM (unless otherwise noted in the Examples). The autoclave was fitted with an oil bubbler and / or a 6-liter oil jacketed creased washout tank with bottom drain and equipped for overhead stirring and distillation. The reactor is vented to a vessel. The bottom drain valve and dip leg sampling port of the autoclave are both plumbed to a wash vessel for direct transfer of unquenched reaction mixture. A large amount of solvent (e.g., cyclohexane or methylcyclohexane or ethylbenzene or mixtures thereof recovered from a previous experiment) is charged to the reactor through the charging vessel by a piston pump. The catalyst components (e.g., TMEDA / potassium t-butoxide / solvent solution and butyllithium) are separately charged to the reactor through the charging vessel at flow rates controlled by precision metered vernier handle needle valves. The contents of the charging vessel are pumped with minimal nitrogen back pressure to the autoclave with either nitrogen or hydrogen or hydrogen / nitrogen atmosphere. Styrene is fed with a high pressure metering pump at a constant rate through basic alumina columns (one or two 0.5" OD columns, each containing 11.0 g of 60-325 mesh Al2O3) to remove inhibitors. Hydrogen is fed into the headspace and / or subsurface to maintain the desired pressure. The autoclave reactor is heated with oil having a temperature set point at or above the desired reaction temperature (+1°C to +3°C) and the reaction temperature is controlled by the reactor controller (typically ambient temperature). After the first 20-30 minutes of monomer feed, the reaction temperature was strictly maintained at the desired set point. Thus, the reaction temperature may have short-term temperature fluctuations, usually not exceeding 5° C. above the desired set point temperature.

[0172] In the course of developing the present invention, four separate configurations or arrangements (configurations I-IV below) containing two, three, or four pitched blade turbine impellers were used: I. Two angled blades, the first 6.25” and the second 10.0” from the top of the reactor. II. Three angled blades, the first 6.0”, the second 8.0”, and the third 10” from the top of the reactor. III. Three angled blades, the first 5.0”, the second 7.0”, and the third 10” from the top of the reactor. IV. Four angled blades, the first 4.0”, the second 6.0”, the third 8”, and the fourth 10” from the top of the reactor. The 2 liter autoclave is a cylinder 10 inches deep, so each inch represents 200 ml of volume. Configurations II and III with three impellers provided uniform hydrogen uptake throughout the course of the feed, as long as the feed was limited so that the total volume in the reactor did not exceed a level at which the top impeller was ineffective in terms of mass transfer. In the Parr 2 liter reactor, configuration IV with four pitched blade impellers was the preferred configuration for the present operation, especially with the LOXSH catalyst of the present invention, which allowed full utilization of the reactor volume with uniform mass transfer of the vapor space to the condensed phase, and thus hydrogen uptake, throughout the styrene monomer feed. The polymerization reactor has a volume of 2000 ml, with a practical maximum volume of 1750 ml, and since the initially produced reaction mixture is usually 400-600 ml in volume, the maximum volume of styrene that can be safely fed is in the range of 1350-1150 ml (not taking into account temperature or density changes during polymerization). Thus, feeding such a volume of styrene (1150 ml to 1350 ml) is considered a full charge of styrene or monomer for this reactor configuration. The terms full charge of styrene or partial charge of styrene, or any term or other phrase used to include the meaning of a small portion of the styrene being charged, are limitations or restrictions of the above equipment and in no way represent limitations to the process or practice of the present invention in reactor system(s) having different reactor arrangements or configurations or operation modes (batch, semi-batch, semi-continuous, continuous, backmixed, or plug flow are all modes and / or configurations within the scope of the present invention). The examples set forth below are representative of batch or semi-batch operation of the present invention. Clearly, one skilled in the art can take the teachings of these examples and extend the application of the present invention to include operation modes with continuous operation with and / or without some degree of backmixing, and thus such modes are well within the scope of the present invention.

[0173] When charging the polymerization reactor under nitrogen atmosphere, the autoclave reactor is pressurized and then vented with 65 PSIG of H2 (venting 65 PSIG to 0 PSIG). Purge at least three times. The polymerization reactor is then pressurized to the desired H2 pressure. If the vessel is being charged with a hydrogen atmosphere, the reactor is usually pressurized and evacuated twice with 50 PSIG H2. Styrene (99%, Acros), TMEDA (Al Aldrich), 2-methoxymethanol (99.9% Aldrich HPLC grade), 2-N,N-dimethylethanolamine (99.5% Aldrich), 2-[2-(dimethylamino)ethoxy]ethanol (98% Aldrich), potassium hydride (30% in mineral oil, Aldrich), di-n-butylmagnesium 1.0 M in heptane, and n-butyllithium (2 M in cyclohexane, Aldrich) were each used as received from the supplier. Anhydrous cyclohexane, methylcyclohexane, and ethylbenzene (all Aldrich) were handled under an inert atmosphere of dry nitrogen.

[0174] Examples 1 to 24 The experimental details (reaction conditions, reagent loadings, and initial and final catalyst concentrations), scale-up parameters (relative feeds and relative feeds per hour), and results (polymer molecular weight distribution [MWD] and polymer yield as measured by GPC) for Examples 1-24 are shown in tabular form in Tables III-VI. It should be clear that the LOXSH catalysts and polymerization reaction conditions of the present invention afford an infinite number of combinations of the reagents and reaction parameters under which the processes to synthesize them are carried out. Thus, Examples 1-5 and Examples 6-13 comprise initial scoping experiments designed to explore this novel catalyst system and reaction conditions. Thus, these examples used only about 25%-50% of the preferred monomer amount per experiment. The amount of styrene monomer used was reduced and impeller configuration II was used. Thus, except for the impeller arrangement and shortened styrene monomer feed in the polymerization reaction, the preparation and execution of these experiments were essentially the same as Examples 14-24. Thus, Examples 3, 14-15, 20-21, and 24 are considered representative and will be described in more detail. It should be noted that GC analysis of the four to six most volatile styrene oligomers of the LOXLiH PS compositions thus produced (Examples 1-24) showed that 99.4% to 99.9% of the separate polymer chains have a pure linear "head-to-tail" polymer microstructure. In addition, these LOXLiH PS compositions are essentially free of any fragmentation polymerization impurities or by-product distributions. Based on the individual monomer repeat units, a statistical model of these distributions (Weibull PDF) indicates that between 99.986 mol % and 99.999 mol % of the styrene repeat units have either 2° (methylene) or 3° (methine) benzylic carbon atoms. In other words, these LOXLiH PS compositions have less than 10 ppm to no more than 140 ppm of quaternary carbon "tail-to-head-to-tail" bonds in the microstructure.

[0175] Example 3 25% LOXLiH of the full monomer feed volume, approximately [DMEA - ]5Li 12 H7 Catalyst Representative example at 80℃ 345 ml of anhydrous cyclohexane in 495 ml (384.9 g) was charged to the reactor at 25° C. under an atmosphere of dry hydrogen (0 PSIG H2). The stirred solvent (800 RPM, as above) A solution previously generated from 2.27 g (0.0255 mol.) of N,N-dimethylethanolamine, 134.7 g (1.27 mol.) of ethylbenzene, and 12.22 g (0.105 mol.) of TMEDA was charged through a charge vessel with positive nitrogen pressure. The charge vessel and the transfer line to the reactor were flushed with a 50 mL aliquot from the total amount of anhydrous cyclohexane. Next, 30.37 mL (0.0607 mol.) of 2.0 M n-butyllithium was transferred through the charge vessel to the reactor, followed by two 50 mL aliquots from the total amount of anhydrous cyclohexane. During the course of the organolithium charge, the agitation speed was increased to 1130 RPM, so that the reactor pressure dropped to -3 PSIG over the 15 minute charge period as the hydrogen was consumed. The reactor headspace was flushed twice with 21 PSIG dry H2 (through a subsurface feed line). The reactor was then inflated and vented (vented slowly to avoid foaming the contents outside the reactor) and the reactor was brought to 0 PSIG. The reactor was then heated to 70°C with increasing pressure to 4 PSIG. Heating was provided by oil at 81°C in the reactor jacket. Once 70°C was reached, a styrene monomer feed was started, feeding 257.2g (2.47mol.) of styrene. Styrene was fed through a subsurface feed line (0.02" ID tip, 2.02ft / s) against a hydrogen head pressure of 6 PSIG over a period of 38 minutes while controlling the reaction temperature at 80°C. Within 10 minutes of starting the monomer feed, the reactor temperature had reached 79°C and the pressure had risen to 13 PSIG. The valve to the regulator was closed and hydrogen uptake was monitored periodically by measuring the time required for a 5 PSIG drop in pressure (-1). In this manner, the time in seconds required for the pressure to drop 1 PSIG (-1) was recorded.

[0176] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (basic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated for 3 min. A positive pressure of H2 was applied to a cleaning vessel containing 00 ml of deoxygenated water and 200 ml of cyclohexane. was transported.

[0177] A 10 ml sample was taken for analysis during the transfer of the unquenched reaction mixture. This sample was essentially water white, i.e., colorless and transparent to light, with no precipitated or suspended solids. This sample was quenched by adding methanol drops from a volumetric pipette. This methanol quench produced hydrogen very slowly but steadily for over an hour, appearing to release hydrogen from very small particles only produced in the first quench. Thus, the catalyst thus produced surprisingly undergoes methanolysis in cyclohexane very slowly under polymerization termination conditions. GPC analysis of the crude quenched reaction mixture, including dimer content, was as follows: M n :702, M w :1091, M z :1489, PD:1.554, σ n =523, n α3=1.537. Thus, these conditions produce a linear (unbranched) anion chain transfer distribution with exceptionally low asymmetry.

[0178] Standard workup and product isolation The two-phase product mixture was heated to 65°C in the wash reactor and the phases were then separated. Phase cut was easy at 65°C and was rapid, requiring little settling time. Water and any debris or emulsion were removed through the bottom drain valve. The pH of the wash water removed from the reactor was measured and the first wash was always (meaning all similar runs before and after) pH = 14. An additional deoxygenated water wash was performed. The removed water wash phase had a pH ≈ 12. The organic phase was then washed with 300 ml 3 wt% H2SO4, followed by two washes with 300 ml tap water, with an end pH of 7. Cyclohexane and ethylbenzene were removed from the water-washed product mixture in the wash reactor by conventional distillation while gradually heating the jacket temperature of the wash reactor to 165°C. The distillation was considered complete when the pot temperature reached a temperature above 140°C. The solution was cooled and 394.75 g of solution was collected. The solution was then further stripped of ethylbenzene using a wiped thin film evaporator (WFE, 2" glass Pope Still, operated at 50.0 mmHg vacuum, 140°C, wiper speed at 60% of maximum speed, and a feed of 1.0 liters / hour). This first WFE run removed the dimer-containing M n :702, M w :1091, M z :148 9, PD: 1.554, σ n =523, n 24 with GPC MWD of α3=1.537 A 5.0 g LOXLiH PS distribution was obtained. The second WFE run (0.1-0.3 mmHg vacuum, 172.5°C, wiper speed 60% of maximum speed, 1.0 L / hr feed) gave a styrene dimer content of 2.40 GPC area % and M n :821, M w :1152, M z :1505, PD:1.403, σ n =521, n A distribution of 217.9 g of LOXLiH PS was obtained with a GPC MWD of α3 = 1.417.

[0179] Examples 14 and 15 LOXLiH [DMEA - Representative full-scale monomer feed rate at 80 °C for 4Li6H2 catalyst and oligomer microstructure analysis 150 ml of 300 ml (233.7 g) of anhydrous cyclohexane was charged to the reactor at 37° C. under an atmosphere of dry hydrogen (10 PSIG H2). The stirred solvent (800 RPM 2.72 g (0.0305 mol.) of N,N-dimethylethanolamine, 140.0 g (1.32 mol.) of ethylbenzene, and 1.82 g (0.0157 mol.) of T were previously charged into the turbine (three pitched blade turbines in the above configuration III) by positive pressure of nitrogen through a charging vessel. A solution generated from MEDA was charged. The charge vessel and transfer line to the reactor were flushed with 50 mL aliquots from the total amount of anhydrous cyclohexane. Next, 22.90 mL (0.0458 moles) of 2.0 M n-butyllithium was transferred to the reactor through the charge vessel, followed by two 50 mL aliquots from the total amount of anhydrous cyclohexane. During the course of the organolithium charge, the agitation speed was increased to 1130 RPM, and the reactor pressure dropped to 9 PSIG over the 15 minute charge period. The reactor headspace was purged and evacuated three times with dry H2 (through a subsurface feed line) from 50 PSIG to 0 PSIG. The reactor was vented (vented slowly to avoid foaming the contents outside the reactor) and the reactor was brought to 45 PSIG. The reactor was then heated to 74°C while increasing the pressure to 63 PSIG. Heating was provided by oil at 81°C flowing through the reactor jacket. When the reaction temperature reached 73°C, the styrene monomer feed was started and 960.4g (9.22 mol.) of styrene was fed. Styrene was fed through a subsurface feed line (0.02" ID tip, 1.88 ft / s) against hydrogen head pressure over 151 minutes while controlling the reaction temperature at 80°C. Within 10 minutes of starting the monomer feed, the reactor temperature reached 81°C and the pressure dropped to 13 PSIG. The hydrogen regulator was set to maintain a pressure of 16 PSIG. The valve to this regulator was closed and hydrogen uptake was monitored periodically by measuring the time required for a 5 PSIG drop. In this way, the time in seconds required for the pressure to drop 1 PSIG (-1) was recorded. When this value was adjusted for the estimated reactor headspace, the hydrogen uptake in moles of H2 per mole of styrene feed was , appeared to be constant or nearly constant.

[0180] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (basic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated for 300 min. The reaction mixture was transferred under positive H2 pressure to a washing vessel containing 100 ml of deoxygenated water. The mixture was carefully quenched in the wash reactor. The above procedure was repeated as Example 15 with the same charges and conditions within small run-to-run variability in measuring out the reagents and reproducing the conditions, except that 1020.4 g (9.80 mol.) of styrene was fed over 160 minutes. Hydrogen uptake decreased slightly during the additional 9 minutes of feed as above.

[0181] During the course of transfer of the unquenched reaction mixtures (Examples 14 and 15), 10 ml samples were taken from each reaction mixture for analysis. These samples were essentially water white, i.e., colorless and transparent to light, with no precipitated or suspended solids. These samples were quenched by the addition of methanol drops via a volumetric pipette, which immediately resulted in the production and release of hydrogen gas. GPC analysis of the crude quenched reaction mixtures, including dimer content, was as follows: Example 14M n :439, M w :628, M z :886, PD:1.411, σ n =288, n α3=2.108, Example 15M n :428, M w :636, M z :979, PD:1.539, σ n =298, n α3=2.778.

[0182] Standard workup from above gave 3271 g of solution. Wiped thin film evaporation (WFE, 2" glass Pope Still, operated at 50.0 mmHg vacuum, 140°C, wiper speed 60% of maximum speed, feeding 1.0 liters / hour) yielded M containing dimer. n : 434, M w :630, M z :934, PD:1.452, σ n =292, n α3=2.54 A distribution of 1793 g of LOXLiH PS was obtained with a GPC MWD of 3. A second WFE run (vacuum 0.1-0.3 mmHg, 172.5°C, wiper speed 60% of maximum speed, 1.0 L / hr feed) gave a styrene dimer content of 2.40 GPC area % and B.M. n :530, M w :731, M z :1150, PD:1.379, σ n =326, nA 1492 g LOXLiH PS distribution was obtained with a GPC MWD of α3=3.661. A third WFE run was performed to obtain low molecular weight oligomers in order to determine the microstructure of this LOXLiH PS distribution. Thus, a 163.2 g sample of the 1492 g product distribution collected from the second WFE run was stripped of oligomers (0.13 mmHg vacuum, 199.5° C., wiper speed 85% of maximum speed, 2.0 g / min feed). In this third WFE run, M n :310, M w :323, M z GPC M:337, PD:1.043 A mixture of 31.24 g of styrene oligomers with WD was produced. GC analysis showed that 99.940% of the chains had the desired "head-to-tail" microstructure and were cleaved (FW i -14) showed that few, if any, linkages had fine structure (see Figure 3).

[0183] Note that Examples 14 and 15 are nearly equivalent except for the additional amount of styrene monomer used in Example 15. These examples use impeller configuration III, which proved to be more than sufficient for uniformity in hydrogen transfer to the condensed phase for Example 14, but less than completely sufficient for the additional 60 grams of monomer fed in Example 15. This is due to the PD n , σ n , and n This is reflected in the increasing values ​​of α3 (Table V). Therefore, a fourth impeller was added to the agitator shaft at the spacing as described above for configuration IV to feed more monomer to the same size starting reaction medium. Configuration IV was used in Examples 20-21 and 24. Example 21 was identical to Example 20, except that only 25% of the total preferred monomer feed was used in Example 21. This was done to investigate how the molecular weight distribution evolved during the experiment. The experiment showed that as the molecular weight increased, the PD n , and nThe value of α3 is decreasing, and as the supply continues, it will gradually differ It shows that each increment of styrene monomer fed produces a narrower, less asymmetric distribution while simultaneously forming a statistical distribution of dead polymer chains and regenerating the LOXLiH catalyst. This combination of experiments shows that a continuous process operated at steady-state conditions can be used to produce even more favorable molecular weight distributions with the desired low polydispersity, breadth, and asymmetry.

[0184] Examples 20 and 21 Full-scale monomer feed of LOXLiH[DMEA at 80 °C - ]2Li6H4 Catalyst Examples 150 mL of 300 mL (231.0 g) of anhydrous methylcyclohexane was charged to the reactor at -5°C under an atmosphere of dry hydrogen (12 PSIG H2). A solution previously made from 1.00 g (0.0112 mol.) of N,N-dimethylethanolamine, 140.0 g (1.32 mol.) of ethylbenzene, and 2.60 g (0.022 mol.) of TMEDA was charged with positive nitrogen pressure through a charge vessel. The charge vessel and the transfer line to the reactor were flushed with a 50 mL aliquot from the total amount of anhydrous methylcyclohexane. Next, 16.81 mL (0.0336 mol.) of 2.0 M n-butyllithium was transferred to the reactor through the charge vessel, followed by two 50 mL aliquots from the total amount of anhydrous methylcyclohexane. During the course of the organolithium charge, the agitation speed was increased to 1130 RPM and the reactor pressure increased to 14 PSIG over the 15 minute charge period. The headspace of the reactor was purged three times with dry H2 (through a subsurface feed line) at 50 PSIG and The reactor was then vented (vented slowly to avoid foaming the contents outside the reactor) and the reactor was brought to 40 PSIG. The reactor was then heated to 70°C and by the time the reactor temperature reached 18°C ​​the pressure had increased from 2 PSIG to 42 PSIG, indicating hydrogen uptake upon heating. The H2 pressure was increased to 46 PSIG and by the time the reactor reached 72°C the pressure had increased from 2 PSIG to 42 PSIG. The pressure had increased to 60 PSIG. This heating process was carried out with 81% CO flowing through the reactor jacket. The reaction was carried out by oil at 72°C. Once 72°C was reached, the styrene monomer feed was started, feeding 1042.5g (10.01 mol.) styrene. The styrene was fed through a subsurface feed line (0.02" ID tip, 1.88 ft / s) against hydrogen head pressure over 164 minutes while controlling the reaction temperature at 80°C. Within 10 minutes of starting the monomer feed, the reactor temperature had reached 80°C and the pressure had dropped to 32 PSIG. The hydrogen regulator was set to maintain a pressure of 14 PSIG. The valve to this regulator was closed and the hydrogen uptake was monitored periodically by measuring the time it took for 4 PSIG to drop. In this way, the time in seconds required for the pressure to drop 1 PSIG (-1) was recorded. When this value was adjusted according to the estimated reactor headspace, the hydrogen uptake in moles of H2 per mole of styrene feed appeared to be constant or nearly constant.

[0185] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (basic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated for 300 min. The reaction mixture was transferred under positive H2 pressure to a washing vessel containing 100 ml of deoxygenated water. The mixture was carefully quenched in the wash reactor. The above procedure was repeated as Example 21 with the same charges and conditions within small run-to-run variability in measuring out the reagents and reproducing the conditions, except that 255.0 g (2.45 mol.) of styrene was fed over 40 minutes.

[0186] During the course of transfer of the unquenched reaction mixtures (Examples 20 and 21), 10 ml samples were taken from each reaction mixture for analysis. These samples were essentially water white, i.e., colorless and transparent to light, with no precipitated or suspended solids. These samples were quenched by the addition of methanol drops via a volumetric pipette, which immediately resulted in the production and release of hydrogen gas. GPC analysis of the crude quenched reaction mixtures, including dimer content, was as follows: Example 20M n :466, M w :675, M z :951, PD:1.409, σ n =312, n α3=2.033, Example 21M n :408, M w :598, M z :932, PD:1.559, σ n =278, n α3=2.993.

[0187] Standard workup from above but at 82° C. gave 1631.5 g of solution. Wiped thin film evaporation (WFE, 2″ glass Pope Still, operated at 50.0 mm Hg vacuum, 140° C., wiper speed at 60% of maximum speed, feeding 1.0 liter / hr) gave the M 2 , including the dimer. n :424, M w :626, M z :979, PD:1.476, σ n =293, nA distribution of 1168 g of LOXLiH PS was produced with a GPC MWD of α3=2.9794. The second WFE run (vacuum 0.1-0.3 mmHg, 172.5°C, wiper speed 60% of maximum speed, feed 1.0 liters / hour) produced a styrene dimer content of 1.40 GPC area % and M n :536, M w :722, M z :1049, PD:1. 379, σ n =326, n 946g LOXL with GPC MWD of α3=2.912 iH PS distribution was obtained.

[0188] Example 24 Full-scale monomer feed of LOXLiH[DMEA at 80 °C - ]5Li 12 H7 Catalyst Representative examples and microstructural analysis of oligomers 150 mL of 300 mL (231.0 g) of anhydrous methylcyclohexane was charged to the reactor at -5°C under an atmosphere of dry hydrogen (13 PSIG H2). 2.27 g (0.0255 mol.) of N,N-dimethylethanolamine, 14 A solution made from 0.0 g (1.32 mol) ethylbenzene and 12.40 g (0.107 mol) TMEDA was charged. The charge vessel and transfer line to the reactor were flushed with 50 mL aliquots from the total amount of anhydrous methylcyclohexane. Next, 30.79 mL (0.0616 mol) of 2.0 M n-butyllithium was transferred to the reactor through the charge vessel, followed by two 50 mL aliquots from the total amount of anhydrous methylcyclohexane. The agitation speed was increased to 1130 RPM during the organolithium charge, and the reactor pressure increased to 14 PSIG over the 15 minute charge period. The reactor headspace was flushed with 50 PSIG to 0 PSIG and dry H2 (through a subsurface feed line). ) and vented three times (venting slowly to avoid foaming the contents outside the reactor) to bring the reactor to 41 PSIG. The reactor was then heated to 73°C, and the pressure had increased to 62 PSIG by the time the reactor temperature reached 72°C. This heating step was accomplished by oil flowing through the reactor jacket at 81°C. Once at 73°C, the styrene monomer feed was started and 1041.0 g (10.00 mol.) of styrene was fed. Styrene was fed through a subsurface feed line (0.02" ID tip, 1.88 ft / s) against hydrogen head pressure over 164 minutes while controlling the reaction temperature at 80°C. Within 10 minutes of starting the monomer feed, the reactor temperature reached 81°C and the pressure dropped to 34 PSIG. The hydrogen regulator was set to maintain a pressure of 14 PSIG. The valve to this regulator was closed and hydrogen uptake was monitored periodically by measuring the time required for a 4 PSIG drop in pressure. In this manner, the time in seconds required for a 1 PSIG drop in pressure (-1) was recorded. When this value was adjusted for the estimated reactor headspace, the hydrogen uptake in moles of H2 per mole of styrene feed remained constant or nearly constant. It seemed likely.

[0189] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (acidic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated to 300 ml. The reaction mixture was transferred under positive H2 pressure to a washing vessel containing 100 ml of deoxygenated water. The material was carefully quenched in this wash reactor.

[0190] During the course of the unquenched reaction mixture transfer, a 10 ml sample was taken from the reaction mixture for analysis. The sample was essentially water white, i.e., colorless and transparent to light, with no precipitated or suspended solids. The sample was quenched by the addition of methanol drops via a volumetric pipette. The methanol quench resulted in the immediate production and release of hydrogen gas. GPC analysis of the crude quenched reaction mixture, including dimer content, was as follows: M n :466, M w :675, M z :951, PD:1.409 , σ n =312, n α3=2.033.

[0191] Standard workup from above but at 82° C. gave 1312.9 g of solution. Wiped thin film evaporation (WFE, 2″ glass Pope Still, operated at 50.0 mm Hg vacuum, 140° C., wiper speed at 60% of maximum speed, feeding 1.0 liter / hr) gave the M 2 elution product including the dimer. n :477, M w :685, M z :961, PD:1.436, σ n =315, n A distribution of 966.2 g of LOXLiH PS was obtained with a GPC MWD of α3=2.032. A second WFE run (vacuum 0.1-0.3 mmHg, 172.5°C, wiper speed 60% of maximum speed, feed 1.0 liters / hour) gave a styrene dimer content of 1.2 GPC area % and M n :575, M w :753, M z :933, PD:1.310 , σ n =320, n 828.4 g LOXLi with GPC MWD of α3=1.933 A third WFE run was performed to obtain low molecular weight oligomers in order to determine the microstructure of this LOXLiH PS distribution. A 106.2 g sample of the 966.2 g product distribution was stripped of oligomers (<0.1 mmHg vacuum, 199.5°C, wiper speed 85% of maximum speed, 2.0 g / min feed). n :372, M w :398, M z :426, P D: 33.17 g of a mixture of styrene oligomers was produced with a GPC MWD of 1.069. GC analysis showed that 99.82% of the chains had the desired "head-to-tail" microstructure and were cleaved (FW i -14) Few, if any, chains have fine structure. (See Figure 4.)

[0192] After completion of a series of LOXLiH experiments (Examples 29-35), the autoclave reactor was rinsed with standard drum-grade (not anhydrous) cyclohexane, thoroughly purged with nitrogen, and then opened for inspection. The heated reactor walls and cold surfaces (i.e., cooling coils, agitator parts, dip legs, monomer feed lines, and thermowells) were in no way free of any solids.

[0193] Examples 25 to 29 The experimental details (reaction conditions, reagent loadings, and initial and final catalyst concentrations), scale-up parameters (relative feeds and relative feeds per hour), and results (polymer molecular weight distribution and polymer yield as measured by GPC) of Examples 25-29 are tabulated in Table VII. It should be clear that the LOXSH catalysts and polymerization reaction conditions of the present invention provide an infinite number of combinations of reagents to synthesize them and reaction parameters under which the process is carried out. These Examples 25-29 include bimetallic catalysts including other salt-like hydrides. Thus, Examples 25-27 involve the use of potassium hydride to form the LOXKH catalyst, and Examples 28-29 involve the formation of the LOXMgH2 catalyst using an organomagnesium reagent. Examples 26, 28, and 29 are described in more detail.

[0194] 4 to 6 of the LOXMgH2PS compositions (Examples 28 to 29) thus prepared It should be noted that GC analysis of the most volatile styrene oligomers of the present invention showed 99.2% essentially linear "head-to-tail" polymer microstructures free of any fragmentation polymerization impurities or by-product distributions. A statistical model of these distributions (beta PDF) indicates that approximately 99.982 mole % of the styrene repeat units have either a 2° (methylene) or 3° (methine) benzylic carbon atom. In other words, these LOXMgH2PS compositions have less than 185 ppm of quaternary carbon "tail-to-head-to-tail" Analysis of oligomers produced by LOXKH showed extremely high levels of composition, i.e., 8-12% of the separate polymer chains, with a single quaternary carbon head "tail-to-head-to-tail" bond. Thus, according to a statistical model (beta PDF) of these compositions, these LOXKH compositions may have less than 99.725 mole % styrene repeat units with either a 2° (methylene) or 3° (methine) benzylic carbon atom. This means that these compositions may have more than 2750 ppm of quaternary carbon "tail-to-head-to-tail" bonds making them less preferred compositions for certain applications.

[0195] Surprisingly, even the composition of Example 27, made from a LOXKH catalyst with a Li:K ratio of 15:1, produced a composition having greater than 8 wt.% of the chains with the undesired single quaternary carbon "tail-to-head-to-tail" bond. The results, shown in Table VII, indicate that, in part, the two Group I metals (M + ) to 1 part DMEAH catalyst, Formula [DMEA - ]4M8H4. According to this assumption, the catalyst of Example 27 (15:1 Li:K) is a complex of the formula [DMEA - ]4Li8H4 and one aggregate with the formula [DMEA -The catalyst of Example 25 (3:1 Li:K) may consist of one aggregate having the formula [DMEA - ]4Li6K2H4 aggregate or aggregates The catalyst of Example 26 (7:1 Li:K) is obtained by the reaction of the formula [DMEA - ]4Li7KH4 Here, in each of these aggregate catalyst systems, the most active hydride species, both in terms of initiation and therefore formation of less desirable polymer microstructures, is KH as these three examples (25, 26, and 27) give as well as all other potassium-based catalyst systems.

[0196] In contrast to LOXKH, Examples 28 and 29 show LOXMgH2 aggregates. It is a representative example of a catalytic system, and the LOXLiH aggregate catalyst is thought to be more active than LOXMgH2. With respect to Example 28, the stoichiometric ratio of DMEAH to n-butyllithium to dibutylmagnesium is such that, when one single aggregate is produced, the empirical formula [DMEAH] is - ] 21 Li 28 Mg4H 15 Therefore, both active species of LiH and MgH2 should exist. Or at least there may be. It is expected that several different aggregates will occur, some of which will not contain magnesium, and therefore LiH form should be present in the catalyst composition as the active reagent. In contrast, the loading of n-butyllithium and dibutylmagnesium in Example 29 was such that all of the lithium alkyl radicals (butyllithium groups) were consumed leaving only magnesium alkyl radicals (dibutylmagnesium groups). The stoichiometric and predicted empirical formula of Example 29 is [DMEA - ]4Li4MgH2, and therefore no explicit form of LiH should exist.

[0197] Given that Example 28 could be run at significantly lower hydrogen pressures than Example 29 with similar product MWD, it is likely that agglomerates of all-lithium catalyst were present that were more active as catalysts for hydrogen-mediated, salt-like hydride-initiated polymerization processes than catalyst agglomerates containing some amount of magnesium hydride. Furthermore, the catalyst of Example 29 was formed such that no active LiH was present (i.e., the moles of DMEAH exceeded the moles of organolithium loaded). This catalyst system was highly effective, but required much higher H2 pressures than Example 28. The demands of a commercial reactor (necessary for constant pressure and proper sealing) may have contributed to the lack of H2 pressures. Considering the challenges in maintaining a simple amount of backpressure required, the results for a conservatively high H2 pressure are This need for oxidization is seen as an incidental advantage over the LOXLiH catalysts (Examples 1-24) and the mixed LOXLiH LOXMgH2 catalyst of Example 28.

[0198] [DMEA for Examples 25 to 27 - ] Preparation of 2LiK·2TMEDA stock solution Unlike potassium tert-butoxide, which is easily dissolved in hydrocarbon solvents with 2-5 moles of TMEDA, potassium alkoxides derived from N,N-dimethylethanolamine, i.e., [DMEA - It seems that K is not fully dissolved even when TMEDA is added. However, the mixed metal alkoxides generated from potassium hydride, n-butyllithium, and DMEAH were readily soluble in ethylbenzene. Thus, the mixed metal aminoalkoxides complexed with TMEDA, “[DMEA -A homogeneous 206.71 g stock solution of 6.12 wt% of [2LiK·2TMEDA] in ethylbenzene was prepared under nitrogen atmosphere from 1.10 g (0.274) of dry virgin KH, 4.90 g (0.0550 mol) of DMEAH, 6.51 (0.560 mol) of TMEDA, and 15.12 ml (0.0302 mol) of 2.0 M n-butyllithium in cyclohexane in 182.5 (1.72 mol) of anhydrous ethylbenzene. This was accomplished by loading 3.67 g of a 30 wt% KH solution in mineral oil into a pre-weighed oven-dried 500 ml borosilicate glass bottle and glass-coated stir bar placed on a stirrer hot plate in a nitrogen-purged glove box. The potassium hydride suspension was then washed and decanted three times with 30 ml of anhydrous n-pentane. After drying to constant weight under a stream of dry nitrogen, 182.46 g of ethylbenzene, 6.51 g of TMEDA (about 99.5%), and 4.90 g of DMEAH (about 99.5%, added in portions as H2 evolved) were then charged. The resulting heterogeneous solution was heated to 50°C. A homogeneous solution resulted after slowly adding n-butyllithium and gradually warming to 500° C. A 10% molar excess of n-butyllithium was required to produce a homogeneous solution with a persistent dark red color indicating the presence of other proton species. One drop of DMEAH was added to eliminate the red color, and upon cooling to room temperature, the solution The stock solution remained homogeneous. Aliquots of this 6.12 wt % homogeneous stock solution containing the desired amount of potassium ion were then used to generate the reaction mixtures of Examples 25-27.

[0199] Example 26 LOXKH [DMEA - Microstructural analysis of representative and oligomers of 4Li7KH4 catalyst at 80℃ 150 ml of 300 ml (233.7 g) of anhydrous cyclohexane was charged to the reactor at 37° C. under an atmosphere of dry hydrogen (10 PSIG H2). The stirred solvent (800 RPM The above-mentioned three pitched blade turbines in configuration III were charged with 51.68 g of the above 6.12 wt % homogeneous solution mixed with an additional 1.23 g (0.0138 mol.) of N,N-dimethylethanolamine and 1.63 g (0.0140 mol.) of TMEDA dissolved in 50.0 mL of anhydrous cyclohexane through a charge vessel by positive nitrogen pressure. The charge vessel and the transfer line to the reactor were flushed with a 50 mL aliquot from the above total amount of anhydrous cyclohexane. Next, 20.66 mL (0.0413 mol.) of 2.0 M n-butyllithium diluted with 42.71 g (0.403) of anhydrous EB was transferred to the reactor through the charge vessel, followed by two 50 mL aliquots from the above total amount of anhydrous cyclohexane. During the organolithium charge, the agitation speed was increased to 1130 RPM and the reactor pressure dropped to 8 PSIG over the 18 minute charge time. The reactor headspace was purged and evacuated three times with dry H2 (through a subsurface feed line) at 50 PSIG (to the outside of the reactor). The contents were vented slowly to avoid foaming, and the reactor was brought to 41 PSIG. The reactor was then heated to 75°C while increasing the pressure to 62 PSIG. Heating was provided by oil at 81°C in the reactor jacket. Once 75°C was reached, the styrene monomer feed was started and 996.9g (9.57mol.) of styrene was fed. Styrene was fed through a subsurface feed line (0.02" ID tip, 1.88 ft / s) against hydrogen head pressure over 156 minutes while controlling the reaction temperature at 81.5°C. Within 10 minutes of starting the monomer feed, the reactor temperature reached 82°C and the pressure dropped to 47 PSIG. The hydrogen regulator was set to maintain a pressure of 22 PSIG. The valve to this regulator was closed and hydrogen uptake was monitored periodically by measuring the time required for a 5 PSIG drop. In this way, the time in seconds required for the pressure to drop 1 PSIG (-1) was recorded. When this value was adjusted for the estimated reactor headspace, the hydrogen uptake in moles of H2 per mole of styrene feed was somewhat This indicated that ethylbenzene, in addition to hydrogen, behaved as a chain transfer agent with this catalyst composition.

[0200] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (basic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated for 300 min. The unquenched reaction mixture was transferred under positive H2 pressure to a washing vessel containing 100 ml of deoxygenated water. During the course of the reaction mixture transfer, a 10 ml sample was taken from the reaction mixture for analysis. The sample was red in color and clear to light with no precipitated or suspended solids. The sample was quenched by the addition of methanol drops via a volumetric pipette. The methanol quench resulted in the immediate production and release of hydrogen gas. By GPC, the analysis of the crude quenched reaction mixture, including dimer content, was as follows: M n :688, M w :1051, M z :1461, PD:1.527, σ n =500, n α3=1.725.

[0201] Standard workup from above but at 82° C. gave 1159.5 g of solution. Wiped thin film evaporation (WFE, 2″ glass Pope Still, operated at 50.0 mm Hg vacuum, 140° C., wiper speed at 60% of maximum speed, feeding 1.0 liter / hr) was used. ) containing dimers, M n :689, M w :1051, M z :1461,PD:1.527, σ n =500, n 935g LOXLKH P with GPC MWD of α3=1.725 A second WFE run (vacuum 0.1-0.3 mmHg, 172.5°C, wiper speed 60% of maximum speed, 1.0 liter / hr feed) produced a styrene dimer content of 0.48 GPC area % and M n :765, M w :1099,M z :1486, PD: 1.437, σ n =505, n 845g LO with GPC MWD of α3=1.667 A third WFE run was performed to obtain low molecular weight oligomers in order to determine the microstructure of this LOXKH PS distribution. Thus, a 150.2 g sample of the 845 g product distribution collected from the second WFE run was stripped of oligomers (<0.1 mmHg vacuum, 199.5°C, wiper speed 85% of maximum speed, 2.0 g / min feed). In this third WFE run, M n :34, M w :371, M z :400, PD: 18.94 g of a mixture of styrene oligomers was obtained with a GPC MWD of 1.077. GC analysis showed that 89.53% of the chains had the desired "head-to-tail" microstructure and were cleaved (FW i -14) The proportion of chains with fine structure is 0.78%, and the remainder of the chains is The results showed that the individual polymer chains have only a single undesirable quaternary "tail-to-head-to-tail" bond (see FIG. 6).

[0202] Example 28 LOXMgH2[DMEA - ] 21 Li 28 Mg4H 15 Complete monomer at 80℃ against catalyst Representative supply examples 175 mL of 375 mL (288.8 g) of anhydrous methylcyclohexane was charged to the reactor at -5°C under an atmosphere of dry hydrogen (13 PSIG H2). A solution previously made from 3.32 g (0.0372 mol.) of N,N-dimethylethanolamine, 30.0 g (0.28 mol.) of ethylbenzene, and 6.51 g (0.056 mol.) of TMEDA was charged by positive pressure of nitrogen through a charge vessel. The charge vessel and the transfer line to the reactor were flushed with 50 mL portions from the total amount of anhydrous methylcyclohexane. Then, 24.50 mL (0.0490 mol.) of a 2.0 M solution of n-butyllithium in cyclohexane in 80 g (0.75 mol.) was transferred through the charge vessel to the reactor, followed by two 50 mL aliquots from the total amount of anhydrous methylcyclohexane. Then, 7.00 mL (0.007 mol) of a 1.0 M heptane solution of dibutylmagnesium in 30.0 g (0.28 mol) of ethylbenzene was charged and transferred to the reactor through the charging vessel, followed by a 50 mL aliquot of anhydrous methylcyclohexane from the total amount. During the organolithium / organomagnesium charge, the agitation speed was increased to 1130 RPM, and the reactor pressure increased to 16 PSIG over the 15 minute charge period. The reactor headspace was flushed three times with dry H2 (through a subsurface feed line) at 50 PSIG. After purging and venting (venting slowly to avoid foaming the contents outside the reactor), the reactor was brought to 46 PSIG and -3.4°C. The reactor was then heated to 40°C and by the time the reactor temperature reached 40°C (45 minutes), the pressure had increased to 55 PSIG. The reactor was vented to 46 PSIG and heating continued. After an additional 15 minutes of heating, the reactor reached 67°C and the pressure was 63 PSIG. This heating step was performed with oil flowing through the reactor jacket at 81°C. At 72°C and 64 PSIG, the styrene monomer feed was started and 1009.0 g (9.69 mol.) of styrene was fed. Styrene was fed through a subsurface feed line (0.02" ID tip, 1.88 ft / s) against an overhead pressure of hydrogen over 159 minutes while controlling the reaction temperature at 82°C. Within 10 minutes of starting the monomer feed, the reactor temperature reached 80°C and the pressure dropped to 36 PSIG. The hydrogen regulator was set to maintain a pressure of 14 PSIG for the next 40 minutes of feed. After a total of 60 minutes of monomer feed, the hydrogen pressure was set to 11 PSIG. The valve to this regulator was closed and hydrogen uptake was monitored periodically by measuring the time required for a 4 PSIG drop in pressure (-1). The time in seconds was recorded. When this value was adjusted for the estimated reactor headspace, the hydrogen uptake in moles of H2 per mole of styrene feed remained fairly constant. It seemed likely.

[0203] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (acidic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated to 300 ml. The quenched sample was transferred to a washing vessel containing 100 ml of 3 wt% H2SO4 under positive H2 pressure. During the course of the reaction mixture transfer, a 10 ml sample was taken from the reaction mixture for analysis. The sample was light yellow in color with no visible solids. The sample was quenched by the addition of methanol drops from a volumetric pipette. The methanol quench immediately eliminated the yellow color and resulted in the production and release of hydrogen gas. GPC analysis of the crude quenched reaction mixture, including dimer content, was as follows: M n :504, M w :773, M z :11 80, PD:1.534, σ n =368, n α3=2.538.

[0204] The biphasic product mixture was heated to 82°C in a wash reactor and the phases were then separated. Phase cut was easy at 82°C and was rapid, requiring little settling time. The organic phase was then washed with 4 x 300 ml tap water until an end point of pH 7 was achieved. Standard solvent removal from the standard product isolation above yielded 1561.8 g of solution. Wiped thin film evaporation (WFE, 2" glass Pope Still, operated at 50.0 mmHg vacuum, 140°C, wiper speed 60% of maximum speed, feed of 1.0 liter / hr) yielded M containing dimer. n :511, M w :780,M z :1187,PD:1.526, σ n =371, n 962 g of LOXMgH2PS distribution was produced with a GPC MWD of α3 = 2.530. The second WFE run (0.1-0.3 mmHg vacuum, 172.5°C, wiper speed 60% of maximum speed, 1.0 L / hr feed) produced a styrene dimer content of 1.1 GPC area % and M n :622, M w :853, M z :1207, PD:1. 371, σ n =379, n 828.4g LO with GPC MWD of α3=2.417 The XMgH2PS distribution was obtained.

[0205] Example 29 LOXMgH2[DMEA - Representative example of 50% monomer feed rate at 80℃ for 4Li4MgH2 catalyst and microstructure analysis of oligomers 175 mL of 375 mL (288.8 g) of anhydrous methylcyclohexane was charged to the reactor at -5°C under an atmosphere of dry hydrogen (12 PSIG H2). A solution previously prepared from 5.00 g (0.0561 mol.) of N,N-dimethylethanolamine, 30.0 g (0.28 mol.) of ethylbenzene, and 8.15 g (0.056 mol.) of TMEDA was charged by positive nitrogen pressure through a charge vessel. The charge vessel and the transfer line to the reactor were flushed with a 50 mL aliquot from the total amount of anhydrous methylcyclohexane. Then, 28.05 mL (0.0561 mol.) of a 2.0 M solution of n-butyllithium in cyclohexane in 80 g (0.75 mol.) was transferred through the charge vessel to the reactor, followed by two 50 mL aliquots from the total amount of anhydrous methylcyclohexane. Then, 14.00 mL (0.014 moles) of a 1.0 M heptane solution of dibutylmagnesium in 30.0 g (0.28 moles) of ethylbenzene was charged and transferred to the reactor through the charging vessel, followed by a 50 mL aliquot of anhydrous methylcyclohexane from the total amount. During the organolithium / organomagnesium charge, the agitation speed was increased to 1130 RPM, and the reactor pressure increased to 17 PSIG over the 16 minute charge period. The reactor headspace was evacuated to 0 PSIG, then purged to 65 PSIG with dry H2 (surface The reactor was pressurized (through the lower feed line) and vented three times (venting slowly to avoid foaming the contents outside the reactor) until the reactor reached 44 PSIG and -4.4°C. The reactor was then heated to 71°C in 120 minutes. This heating step was accomplished with oil at 81°C in the reactor jacket. Once at 71°C and 61 PSIG, the styrene monomer feed was started and 509.0 g (4.89 mol.) of styrene was fed. Styrene was fed through a subsurface feed line (0.02" ID tip, 1.88 ft / s) against hydrogen head pressure over 80 minutes while controlling the reactor temperature at 81°C. Within 10 minutes of starting the monomer feed, the reactor temperature reached 80°C and the pressure dropped to 49 PSIG. (However, it was noted that hydrogen consumption as evidenced in the pressure drop was delayed by approximately 0.25-0.75 minutes compared to the LOXLiH run.) The hydrogen regulator was set to maintain a pressure of 46 PSIG for the next 40 minutes of feed. After a total of 60 minutes of monomer feed, the hydrogen pressure was controlled at 65 PSIG. The valve to this regulator was closed and hydrogen uptake was monitored periodically by measuring the time required for a 4 PSIG drop in pressure. In this way, the time in seconds required for the pressure to drop 1 PSIG (-1) was recorded. When this value was adjusted according to the estimated reactor headspace, it was possible to calculate the moles of H2 per mole of styrene feed in units of The hydrogen uptake appeared to be nearly constant.

[0206] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (basic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated for 300 min. The mixture was transferred to a washing vessel containing 1 ml of 3 wt% H2SO4 under positive H2 pressure. During the course of the undissolved reaction mixture transfer, a 10 ml sample was taken from the reaction mixture for analysis. The sample was light yellow in color with some large precipitate particles. The sample was quenched by the addition of methanol drops from a volumetric pipette. The methanol quench immediately eliminated the yellow color and resulted in the production and release of hydrogen gas. GPC analysis of the crude quenched reaction mixture, including dimer content, was as follows: M n :481, M w :713, M z :1008, PD:1.482, σ n =334, n α3=1.969.

[0207] The work-up and stripping procedure of Example 28 yielded 729.9 g of solution. Wiped thin film evaporation (WFE, 2" glass Pope Still, operated at 50.0 mm Hg vacuum, 140°C, wiper speed at 60% of maximum speed, and a feed of 1.0 liter / hr) revealed the presence of M, including dimer. n :485, M w :718, M z :1018, PD:1.480, σ n =336, n 492 g of LOXMgH2PS distribution was produced with a GPC MWD of α3=2.000. The second WFE run (0.1-0.3 mmHg vacuum, 172.5°C, wiper speed 60% of maximum speed, 1.0 liter / hr feed) produced a styrene dimer content of 1.1 GPC area % and M n :593, M w :805, M z :1116, PD:1.358, σ n =355, n 427g LOXMgH2PS distribution with GPC MWD of α3=2.256 A third WFE run was performed to determine the fine structure of this LOXMgH2PS distribution. Thus, oligomers were removed from a 94.5 g sample of the 492 g product distribution collected from the second WFE run (0.12 mmHg vacuum, 199.5° C., wiper speed 85% of maximum speed, 2.0 g / min feed). n :314, M w :329, M z :344, PD:1.049 A mixture of 15.73 g of styrene oligomers was produced with a GPC MWD of 15.73 g. GC analysis showed that 99.21% of the chains had the desired "head-to-tail" microstructure and were cleaved (FW i -14) No chains with fine structure, no traces of oligomers initiated with butyl groups (See FIG. 8.) The slight delay in hydrogen consumption observed and the presence of traces of butyl-initiated polystyrene distribution suggest that the formation of the magnesium hydride composition occurs more rapidly following alkylation of styrene with residual butylmagnesium radicals in the catalyst composition. This may suggest that the benzylmagnesium or benzylmagnesite reagents are more easily reduced by hydrogen than the aliphatic magnesium or aliphatic magnesite reagents.

[0208] After completing this series of LOXMgH2 experiments (Examples 28 and 29), the autoclave The reactor was rinsed with standard drum-grade (not anhydrous) cyclohexane, purged thoroughly with nitrogen, and then opened for inspection. The heated reactor walls and cold surfaces (i.e., cooling coils, agitator parts, dip legs, monomer feed lines, and thermowell) were covered with a scaly white solid. Rinsing the solid from the reactor surfaces with tap water yielded a rinse solution with a pH=11. Analysis (ICP) revealed that the scaly solid consisted of lithium and magnesium salts, 84.0 mg (3.51 mmol Li, or 3.34% of total lithium) as LiOH and 0.24 mmol Mg(OH)2. grams (0.004 mmol Mg, i.e., 0.02% of the total magnesium). Since 105.1 mmol lithium and 21.02 mmol magnesium were loaded between the two experiments, this solid residue represents only a small proportion of the lithium and essentially a trace of the magnesium loaded.

[0209] Examples 30 to 32 The experimental details (reaction conditions, reagent charges, and initial and final catalyst concentrations), scale-up parameters (relative feeds and relative feeds per hour), and results (polymer molecular weight distributions and polymer yields as measured by GPC) for Examples 30-32 are tabulated in Table VIII. Examples 30-32 are reactions in which the complexing ligand is lithium methoxyethoxide [MEOE - ]Li + or lithium 2-N,N-dimethylaminoethoxyethoxide [DMAEOE - ]Li + Example 30 involves the formation and processing of other LOXLiH catalysts having the empirical formula [MEOE - This demonstrates that a hydrocarbon-soluble lithium hydride reagent or catalyst having the empirical formula [MEOEH]4Li8H4·4TMEDA can be generated from 2-methoxyethanol [MEOEH], n-butyllithium, in the presence of TMEDA under a hydrogen atmosphere. Example 30 also shows that although this catalyst system will initiate the polymerization of styrene monomer, the hydrogen-mediated or chain transfer step is inefficient under the conditions of this example, yielding only 0.86 moles of polymer chains per mole of complexed lithium hydride. This may imply that the presence of amine functionality in the lithium alkoxide complexing agent of this catalyst is necessary if this catalyst is to promote or facilitate hydrogen chain transfer reactions involving living poly(styryl)lithium species. The empirical formula [MEOE - ]4Li 12 Hydrocarbons with H8 It should be noted that the soluble lithium hydride composition has a very high hydride content relative to the hydrocarbon soluble form of LiH, i.e., 2.06 wt.% hydride. Similarly, the empirical formula [MEOE- The composition 4Li8H4 has a high hydride content, i.e., 1.12 wt% hydride.

[0210] In Examples 31 and 32, 2-N,N-dimethylaminoethoxyethanol [DMAEOEH] was used to form the hydride reagent or catalytic species. The reagent loading used in Example 31 was 2-N,N-dimethylaminoethoxyethanol [DMAEOEH], - ]4Li8H4·4TMEDA. However, from the outset, it was clear that very little catalyst was being formed, as there was little evidence of hydrogen uptake. - ]L i + It is presumed that this promoted the decomposition of the species by n-butyllithium. Under these conditions, the catalyst produces very high molecular weight (M w =183,233) polystyrene composition was produced. TMEDA was [DMAEOE - ] Li + It is presumed that this promoted the decomposition of the n-butyllithium species used in Example 32. The reagent loading was determined using the empirical formula [DMAEOE - ]4Li6H2. In addition, this catalyst was initially formed at -5°C. Under the reaction conditions of Example 32, the desired catalyst was produced, at least for the catalyst initially formed from DMAEH. The catalyst had activity comparable to that of the DMAEOE, but the activity of this catalyst dropped rapidly during the course of the styrene monomer feed, resulting in the formation of a high molecular weight tail as indicated by Mz=139,795 and asymmetry of 34.4. It is speculated that decomposition of the catalyst occurred under the temperature conditions of this reaction. Whether during the catalyst formation or the polymerization process, [DMAEOE - ]Li +Decomposition of is believed to involve metallation alpha to the dimethylamino functionality followed by elimination of the dilithium alkoxide of ethylene glycol and formation of vinyldimethylamine (enamine) as shown below. Therefore, this ligand and any other ligands susceptible to such potential decomposition steps are less preferred to DMEAH for the formation of catalysts for hydrogen-mediated salt-like hydride initiated polymerization processes involving monometallic lithium catalysts. [ka]

[0211] Example 30 LOXLiH[MEOE - Representative example of ]4Li8H4·4TMEDA catalyst 400 ml of anhydrous cyclohexane in 550 ml (428.5 g) was charged to the reactor at 20° C. under an atmosphere of dry hydrogen (0 PSIG H2). The stirred solvent (800 RPM, as above) A solution previously generated from 2.10 g (0.0276 mol.) of 2-methoxyethanol, 15.0 g (0.14 mol.) of ethylbenzene, and 3.35 g (0.029 mol.) of TMEDA was charged through a charge vessel with positive nitrogen pressure. The charge vessel and the transfer line to the reactor were flushed with 50 mL portions from the total amount of anhydrous cyclohexane. Next, 28.77 mL (0.0575 mol.) of a 2.0 M solution of n-butyllithium in 80 g (0.75 mol.) of cyclohexane was transferred through the charge vessel to the reactor over 15 minutes, followed by two 50 mL aliquots from the total amount of anhydrous cyclohexane. During the course of the organolithium charge, the agitation speed was increased to 1130 RPM, and the reactor pressure dropped to -4 PSIG and the temperature rose to 22°C, indicating consumption of H2. The head space of this reactor was then 50 PS Purge and evacuate three times with 100-150 psig dry H2 (through a subsurface supply line) The reactor was then heated to 35 PSIG (venting slowly to avoid foaming the contents outside the reactor). The reactor was then heated to 73°C in 60 minutes. This heating step was accomplished by oil flowing through the reactor jacket at 81°C. Once 73°C and 51 PSIG was reached, the styrene monomer feed was started, feeding 160.0g (1.54 mol.) of styrene. Styrene was fed through a subsurface feed line (0.02" ID tip, 1.35 ft / s) against the hydrogen head pressure over 35 minutes while controlling the reaction temperature at 80°C. Within 10 minutes of starting the monomer feed, the reactor temperature reached 78°C and the pressure rose to 52 PSIG. The valve to the hydrogen regulator was left closed and the pressure rose as the head space was compressed by the styrene monomer feed. After a total of 35 minutes of feeding, the hydrogen pressure reached 55 PSIG.

[0212] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (basic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually 100 ml. The quenching is indicated by the permanent closure of the automatic coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated for 300 The unquenched reaction mixture was transferred under positive H2 pressure to a washing vessel containing 100 ml of deoxygenated water. A 10 ml sample was taken from the reaction mixture during the transfer process. The sample was colorless and transparent to light with no precipitated or suspended solids. The sample was quenched by adding methanol drops via a volumetric pipette. The methanol quench resulted in the immediate production and release of hydrogen gas.

[0213] Standard workup and solvent removal from above was followed, except that the distillation was considered complete when no more ethylbenzene was removed overhead with nitrogen headspace injection. The resulting resin was transferred through the bottom drain valve to a pre-weighed metal tray reinforced with aluminum foil. The resin was then further stripped of ethylbenzene by gradually heating from 100°C to 165°C in a vacuum oven and gradually increasing the vacuum from 50.0 mmHg to 1.0 mmHg vacuum. After cooling, the resulting brittle colorless resin was collected and analyzed by GPC: n :61 79, M w :14,450,M z :22,964,PD:1.578,σ n =7192, n α3=2.338.

[0214] Example 32 LOXLiH formed from 2-N,N-dimethylaminoethoxyethanol [DMAEOE - ]4Li6H2 Catalyst Representative Example 150 ml of 300 ml (231.0 g) of anhydrous methylcyclohexane was charged to the reactor at -5°C under an atmosphere of dry hydrogen (0 PSIG H2). The stirred solvent (800 RPM A solution previously generated from 4.00 g (0.0300 mol.) of 2-N,N-dimethylaminoethoxyethanol and 16.0 g (0.14 mol.) of ethylbenzene was charged through a charge vessel by positive nitrogen pressure. The charge vessel and the transfer line to the reactor were flushed with 50 mL portions from the total amount of anhydrous methylcyclohexane. Next, 22.54 mL (0.0451 mol.) of a 2.0 M solution of n-butyllithium in 120 g (1.13 mol.) of cyclohexane was transferred through the charge vessel to the reactor over 15 minutes, followed by two 50 mL aliquots from the total amount of anhydrous methylcyclohexane. The agitation speed was increased to 1130 RPM during the course of the organolithium charge, without increasing or decreasing the reactor pressure. The headspace of the reactor was then pressurized to 50 PSIG with dry H2 (through a subsurface feed line), The reactor was vented three times (venting slowly to avoid foaming the contents outside the reactor) and brought to 36 PSIG. The reactor was then heated to 73°C in 60 minutes. This heating step was performed with 81°C oil in the reactor jacket. Upon reaching 72°C and 59 PSIG, the styrene monomer feed was started, feeding 131.1g (1.26 mol.) of styrene. Styrene was fed through a subsurface feed line (0.02" ID tip, 1.35 ft / s) against hydrogen head pressure over 29 minutes while controlling the reaction temperature at 80°C. Within 10 minutes of starting the monomer feed, the reactor temperature reached 82°C and the pressure dropped to 52 PSIG. The hydrogen regulator was set to 36 PSIG. For the first 10-15 minutes of the styrene monomer feed, the process appeared to proceed in line with the catalyst system formed from DMEA. However, by 20 minutes, it was very clear that hydrogen uptake was rapidly declining.

[0215] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (acidic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated to 300 ml. The reaction was transferred under positive H2 pressure to a wash vessel containing 100 ml of deoxygenated water. A 10 ml sample was taken from the reaction mixture during the course of the mixture transfer. The sample was colorless and transparent to light with no precipitated or suspended solids. The sample was quenched by adding methanol drops via a volumetric pipette. The methanol quench resulted in the immediate production and release of hydrogen gas.

[0216] Standard workup and solvent removal from above was followed, except that the distillation was considered complete when no more ethylbenzene was removed overhead with nitrogen headspace injection. The resulting resin was transferred through the bottom drain valve to a pre-weighed metal tray reinforced with aluminum foil. The resin was then further stripped of ethylbenzene by gradually heating from 100°C to 165°C in a vacuum oven and gradually increasing the vacuum from 50.0 mmHg to 1.0 mmHg vacuum. After cooling, the resulting brittle colorless resin was collected and analyzed by GPC: n :74 5. M w :23,605,M z :139,795,PD:5.922,σ n =4127, n α3=34.431.

[0217] Examples 33 to 37 The experimental details (reaction conditions, reagent charges, and initial and final catalyst concentrations), scale-up parameters (relative feeds and relative feeds per hour), and results (polymer molecular weight distributions and polymer yields as measured by GPC) for Examples 33-37 are also tabulated in Table VIII. These Examples (33-37) were purposefully run under a hydrocarbon atmosphere with little, if any, hydrogen present. The purpose of these Examples is to demonstrate four points: (1) the LOXLiH catalysts of the present invention will initiate polymerization of monomers such as styrene; (2) the M of these Examples obtained n The molecular weight of the formed L (3) provide some experimental evidence of the actual composition of the OXLiH catalyst aggregates, (4) demonstrate that the additional promoter TMEDA does indeed play a role in determining catalyst activity, and (5) demonstrate that the absence of hydrogen in these examples clearly demonstrates the powerful and surprising effect that hydrogen has in mediating and perhaps even activating the salt-like hydride-initiated polymerization process of the present invention.

[0218] Therefore, the empirical formula [DMEA - ]2Li3H with LiH:styrene ratio of 1:31.9 (M nExample 33, which used a catalyst having a calc. value of 3316, had M n =6707% efficiency ≒ 50% Assuming there is no chain transfer from ethylbenzene, this implies that only one of the two LiH is available in the aggregate to initiate polymerization, and that the actual catalytic or initiating species is of the formula [DMEA - In comparison, Example 34, which uses the same catalyst system but has 1 mole of TMEDA per mole of lithium metal, shows that M n =5084 salt-like hydride start Polystyrene compositions were produced. Thus, this TMEDA loading appears to increase the efficiency and possibly the availability of hydride for the catalyst formed from 2 moles of DMEAH and 3 moles of n-butyllithium. In contrast to Examples 33 and 34, the catalyst systems of Examples 35 and 36 unexpectedly exhibit completely different behavior. Thus, Examples 35 and 36 show the empirical formula [DMEA - ] A catalyst with LiH was used (Example 35 without TMEDA, Example 3 As shown in Table VIII, the percent efficiency for Examples 35 and 36 was 35% and 26%, respectively. Again assuming little or no participation of ethylbenzene as a chain transfer agent, this is the same as the empirical or actual chemical formula, [DMEA - ]3Li6H3 and [DMEA - ]4Li8H4·4TMEDA, in both cases with only one hydride available for addition to styrene and formation of the polymer initiating species. The percent efficiencies of the catalysts in Examples 33-36, i.e., about 50%, about 66.7%, about 33.3%, and about 0.25%, should make it clear that the LOXLiH catalysts, and by extension the LOXSH catalysts of the present invention, likely exist as relatively simple aggregates of defined stoichiometry depending on the reagents used to form them. Example 37, however, It may be suggested that the formation of much more complex, but well-defined, superaggregates may occur. - ]Li3H2 with LiH:styrene ratio of 1:18.6 (M n Example 37, which used a catalyst having a calculated value of 1933, had a M n =17,972% efficiency ≒ 11% This implies that only one of the nine LiHs was available to add to styrene and thus initiate polymerization. This corresponds to the empirical formula [DMEA - ]8Li 16 H8 and [DMEA - ]6Li 18 H 12 A mixture of aggregates having a ratio of 75:25, 1 of 8 and 1 of 12 This indicates that LiH was available to initiate polymerization. Thus, while not wishing to be bound by theory as just presented regarding the actual chemical formula of the LOX LiH catalyst, Examples 33-37 clearly demonstrate the above four points (1)-(4). Example 37 is presented as representative of Examples 33-37.

[0219] Example 37 LOXLiH[DMEA at 82℃ under a hydrocarbon atmosphere - ]Li3H2·2TMEDA touch Representative examples of media A reactor was charged with 450 mL of 650 mL (506.4 g) of anhydrous cyclohexane at 10° C. under an atmosphere of dry hydrogen (11 PSIG H2). The stirred solvent (800 RPM, The three pitched blade turbines in configuration III were charged with a solution of 3.02 g (0.0339 mol.) of N,N-dimethylaminoethanol and 7.90 g (0.068 mol.) of TMEDA dissolved in 50 mL portions of the total amount of anhydrous cyclohexane through a charge vessel under positive nitrogen pressure. The charge vessel and the transfer line to the reactor were flushed with 50 mL portions of the total amount of anhydrous cyclohexane. Next, 50.90 mL (0.1018 mol.) of a 2.0 M solution of n-butyllithium in 65 g (0.61 mol.) in cyclohexane was transferred through the charge vessel to the reactor over 15 minutes, followed by two 50 mL aliquots from the total amount of anhydrous cyclohexane. During the course of the organolithium charge, the agitation speed was increased to 1130 RPM, causing the reactor pressure to drop to 5 PSIG and the temperature to rise to 13°C. The headspace of the reactor is then filled with dry H2 to 50 PSIG. The reactor was brought to 46 PSIG by pressurizing (through a subsurface feed line) at 100° C. and then venting to 0 PSIG (gradual venting to avoid foaming the contents out of the reactor) a total of three times. The reactor was then heated to 70° C. in 50 minutes. This heating step was accomplished with 85° C. oil flowing through the reactor jacket. Upon reaching 73° C. and 57 PSIG, the hydrogen atmosphere was vented to a mineral oil bubbler (0 PSIG). Heating continued until the reactor temperature reached 82° C. and the vent line began to warm from condensing cyclohexane vapor, thus purging the remaining hydrogen and establishing a hydrocarbon atmosphere. The valve to the mineral oil bubbler was closed, the agitation reduced to 794 RPM, and the styrene monomer feed was started, feeding 131.3 g (1.26 mol.) styrene. Styrene was fed to the hydrocarbon atmosphere through a subsurface feed line (0.02" ID tip, 1.29 ft / s) over 30 minutes while controlling the reaction temperature at 82°C.

[0220] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (basic alumina), were flushed with 50 ml of anhydrous ethylbenzene. The reactor was pressurized to 65 PSIG H2 with the pressure decreasing to 60 PSIG when the agitation was increased to 1130 RPM. Such a hydrogen-quenched anionic polymerization reaction mixture was preheated (N2 atmosphere) and preheated. The sample was transferred to a washing vessel containing 300 ml of deoxygenated water under positive H2 pressure. A 10 ml sample was taken from the reaction mixture during the transfer of the undissolved hydride reaction mixture. The sample was faintly pink and clear to light with no precipitated or suspended solids. The faint pink color disappeared upon shaking the sample with air trapped in the sample vial. The sample was quenched by adding a drop of methanol via a volumetric pipette. The methanol quench resulted in the immediate production and release of hydrogen gas.

[0221] Standard workup and solvent removal from above was followed, except that the distillation was deemed complete when no more ethylbenzene was removed overhead with nitrogen headspace injection. The resulting resin (154 g) was transferred through the bottom drain valve to a pre-weighed metal tray reinforced with aluminum foil. The resin was then further stripped of ethylbenzene by gradually heating from 100° C. to 165° C. in a vacuum oven and gradually increasing the vacuum from 50.0 mm Hg to 1.0 mm Hg vacuum. After cooling, the resulting brittle colorless resin (128 g) was collected and analyzed by GPC: M n :17,972,M w :37,183,M z :49,015, PD:1 .318, σ n =18,581, n α3=1.299.

[0222] Examples 38 to 40 Examples 38-40 are examples of hydrogen-mediated salt analog hydride initiated polymerization processes involving styrene monomer and other forms of salt analog hydrides as catalysts. The superactive salt analog hydride (SASH) catalyst of Example 38 was prepared from butyl lithium and t-butyl alcohol in the presence of TMEDA. This catalyst was at best sparingly soluble and resulted in the production of high molecular weight HMSHIP distributions. The SASH catalyst of Example 39 was prepared from butyl lithium plus potassium t-butoxide in the presence of TMEDA. This catalyst was highly efficient in forming low molecular weight HMSHIP distributions, but the SASH catalysis process produced undesirable quaternary "tail-to-head-to-tail" linkages in the polymer microstructure (as with all other potassium-based anionic chain transfer polymerization reactions). Example 40 used a highly active salt analog hydride (HASH) catalyst generated by feeding styrene monomer to a THF dispersion of sodium potassium alloy under a hydrogen atmosphere. This HASH catalyst was relatively inefficient based on the gram atoms of sodium and potassium required to produce the resulting molecular weight distribution, and, as expected, this HASH catalyst gave a complex mixture of polymers with different microstructures, especially the distribution of cleaved oligomers.

[0223] Example 38 Superactive lithium hydride catalyzed process for producing high molecular weight polystyrene distribution compositions 300 g of anhydrous ethylbenzene was charged to the reactor under hydrogen atmosphere (0 PSIG) at 20° C. The stirred solvent (800 RPM, twin pitched blade, configuration III blade arrangement) was charged through a charging vessel with a solution previously made from 3.62 g (0.0489 mol.) of tert-butyl alcohol, 69.9 g (0.66 mol.) of ethylbenzene, and 23.50 g (0.202 mol.) of TMEDA. The charging vessel and the transfer line to the reactor were flushed with 50 g portions of ethylbenzene. The stirring was increased to 1130 RPM, and then 54.10 ml (0.11 mol.) of 2.0 M n-butyllithium dissolved in 100 g of ethylbenzene was slowly transferred through the charging vessel to the reactor. The reactor temperature was increased from 5°C to 25°C and the pressure increased to 2 PSIG, then dropped to -4 PSIG with the butyllithium solution withdrawn, followed by a 50g rinse aliquot of ethylbenzene into the reactor. The reactor, containing a total of 570g (5.4 mol.) of ethylbenzene, was heated to 90°C. Traces of N2 introduced during catalyst component loading were purged by pressurizing with dry H2 (through the headspace) to 50 PSIG and venting three times (venting slowly to avoid foaming the contents out of the reactor). The H2 regulator was initially set at 21 PSIG. Styrene, 462.2 g (4.44 mol.), was fed through a subsurface feed line (0.02" ID tip, 1.2 ft / s) over 116 minutes against the head pressure of hydrogen, controlling the temperature at 90°C and gradually increasing the hydrogen pressure to 41 PSIG. At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column, were flushed with 50 ml of anhydrous cyclohexane. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by permanent closure of the automatic coiling coil control valve. During the course of this experiment, the valve to the hydrogen regulator was periodically closed to check for hydrogen uptake in the styrene feed. The reaction was Hydrogen was taken up, albeit very slowly.

[0224] The unquenched contents of the reaction mixture were transferred to a wash vessel (N2 atmosphere) previously charged with 300 ml of deoxygenated water preheated to 65°C and subsequently washed with deoxygenated water (3 x 300 ml). The reaction mixture was then appropriately disposed of upon isolation of the aqueous quench. During the course of the unquenched reaction mixture transfer, a 10 ml aliquot of the unquenched reaction mixture was taken. The colorless sample was rich in very finely divided solids that were uniformly suspended. Quenching of the sample with methanol resulted in the immediate production and release of hydrogen gas from the viscous mixture. GPC analysis of the sample using a standard high molecular weight column and polystyrene standards was as follows: GPC MWD M n :1030,M w :5635, M z :10,066,PD:5.47,σ n =2178, n α3=4.13.

[0225] Example 39 Representative of SASH catalytic experiments in ethylbenzene at moderate temperatures of 70°C with 80% monomer feed and microstructure analysis of oligomers 200 g of 300 g (2.83 moles) of anhydrous ethylbenzene was charged to the reactor at 20° C. under a dry nitrogen atmosphere. The stirred solvent (800 RPM, twin pitched blade, blade arrangement of configuration I) was charged through a charging vessel with a solution previously made from 4.57 g (0.0407 moles.) of potassium t-butoxide, 44 g (0.41 moles.) of ethylbenzene, and 20.83 g (0.179 moles.) of TMEDA. The charging vessel and the transfer line to the reactor were flushed with 50 g portions of the 300 g of ethylbenzene. 20.34 ml (0.0407 moles.) of 2.0 M n-butyllithium was then transferred through the charging vessel to the reactor, followed by the 50 g aliquot of ethylbenzene. The reactor was heated to 65° C. The agitation was then increased to 1130 RPM and the reactor was flushed with dry H2 (upper The reactor was purged of N2 by pressurizing to 65 PSIG (through the air space) and venting three times (venting slowly to avoid foaming the contents outside the reactor). The H2 regulator was set to 11 PSIG and 800 g (7.68 mol.) of styrene was fed through a subsurface feed line (0.01" ID tip, 5.2 ft / s) over 183 minutes against the head pressure of hydrogen while controlling the temperature at 70°C. At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column, were flushed with 50 ml of anhydrous cyclohexane. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by a permanent closure of the automatic coiling coil control valve.

[0226] The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and cooled to 300 100 ml of deoxygenated water was transferred under positive H2 pressure to a wash vessel charged with 500 ml of recovered distilled cyclohexane from the previous experiment. During the course of the transfer of the unquenched reaction mixture A 10 ml sample of this reaction mixture was taken for analysis. This sample was red and transparent to light, giving it an appearance similar to the color of samples from the living APS process. The appearance of this sample was completely different from the characteristic dark black-red (black cherry) color of samples from anionic chain transfer polymerizations carried out in the absence of a hydrogen atmosphere. Such samples of SASH catalysts, where the catalyst components are mixed at 100° C., may generally contain large (mm-sized) catalyst particles. The sample was quenched by the addition of a drop of methanol, which immediately caused the red color to disappear and the immediate production and release of hydrogen gas. GPC analysis of the crude quenched reaction mixture was as follows: n :367, M w :497, M z :695, PD:1.35, σ n =218, n α3=2.38.

[0227] Standard workup and stripping procedures from above gave 1303 g of solution. Wiped thin film evaporation (WFE, 2" glass Pope Still, 50.0 mmHg vacuum, 14 Operated at 0°C, 60% of maximum wiper speed, and 1.0 liter / hour delivery) n :3 76, M w :508, M z :707, PD:1.35, σ n =223, n G for α3=3.34 A SASH PS distribution of 827.9 g was produced with a PC MWD. ​​A second WFE run (0.1-0.3 mmHg vacuum, 172.5°C, 60% of maximum wiper speed, 1.0 L / hr feed) produced a styrene dimer content of 0.99 GPC area % and M n :48 6. M w :593, M z :750, PD:1.22, σ n =228, n GP of α3=2.15 A SASH PS distribution of 608.7 was obtained with a C MWD. ​​A third WFE run was performed to obtain low molecular weight oligomers in order to determine the microstructure of this SASH PS distribution. Thus, a 180.2 g sample of the 608.7 g product distribution collected from the second WFE run was stripped of oligomers (<0.1 mmHg vacuum, 199.5° C., wiper speed 85% of maximum speed, 2.0 g / min feed). In this third WFE run, M n :33 2. M w :348, M z 33.17 g of a mixture of styrene oligomers was produced with a GPC MWD of 363 and PD of 1.048. GC analysis showed that 93.49% of the chains had the desired "head-to-tail" microstructure and were cleaved (FW i -14) Fine structure It was shown that the linkage was only 0.11% (see Figure 7).

[0228] Example 40 Hydrogen-mediated styrene polymerization over highly active salt-like hydride catalysts and microstructural analysis of oligomers. The anion chain transfer step was carried out in a modified 2 liter autoclave reactor as described in U.S. Patents 5,777,162 and 5,866,720. 818 g of anhydrous tetrahydrofuran and 6.2 g (0.183 g atoms of alkali metal) of sodium potassium alloy (NaK2) were charged to the reactor at 20° C. under a dry nitrogen atmosphere. The nitrogen mixture was purged with hydrogen (3x70 PSIG) and pressurized to 70 PSIG H2. High speed high shear mixing (1900 RPM) was applied and 208.0 g (2.00 moles) of styrene was fed to the reaction mixture over 73 minutes (3.15 ml / min). The reactor pressure was maintained between 70-60 PSIG H2 during the styrene monomer feed. After the feeds were completed, the reactor pressure was maintained between 70-60 PSIG H2. The H2 was evacuated and the reaction mixture was carefully quenched with isopropyl alcohol. A sample of the reaction mixture was analyzed by GPC and had the following MWD: n :591, M w :943, M z :1438, PD:1.60, σ n =456, n α3=2.38. The reaction mass was transferred to a creased wash reactor containing ethylbenzene, washed with water and THF was removed. A wiped thin film evaporator WFE (2" glass Pope Still, graphite impeller, operated at 300.0 mmHg vacuum, 140°C, 60% of maximum wiper speed, 1.0 liter / hr feed rate) was used to remove M n :603, M w :956, M z :1373, P D: 1.58, σ n =461, n 191g polysaccharide with GPC MWD of α3=1.906 A 164 g sample of the 191 g from above was subjected to a second WFE run (0.4 mmHg vacuum, 230° C., 60% of maximum wiper speed, 1.0 liter / hour feed rate) to produce a M n:802, M w :1081,M z :1418, PD:1 .35, σ n =473, n 153.6 g of resin with GPC MWD of α3=1.645 This second WFE run yielded 18.2 g of a complex mixture of dimers, trimers, tetramers, pentamers, and hexamers. GC analysis indicates that this complex mixture results from reaction pathways including head-to-tail polymerization, chain isomerization, and chain fragmentation polymerization (see FIG. 5).

[0229] After the preparation of LOXLiH and LOXMgH2 from which dimers had been removed, hydrogen-mediated salt-like water was The brominated polymers were brominated according to the process techniques of PCT Publication No. WO2010 / 127091 (US 8,802,787 B2) to form brominated anionic chain transfer vinyl aromatic polymers (Br-ACTVAPs). The averages and standard deviations of the physical properties of these brominated polymers are listed below, along with the properties of the Br-ACTVAPs formed by blending and then stripping the product distributions of Examples 14-15. The dimer-removed compositions were characterized as M w =731 and PD n = 1.38 These compositions were further tested as polymeric flame retardants in high impact polystyrene (HIPS) and were found to provide flame retardant (UL94 V0 at 1 / 8" and 1 / 16") HIPS formulations with excellent overall properties including color (YI), Izod impact, heat distortion temperature, and VICAT softening temperature. [Table 4]

[0230] The catalyst compositions of Examples 14 and 15 are - ]Li3H2·1.0TMEDA Because of the excellent overall properties that this composition afforded upon bromination, and because further development of this particular LOXLiH catalyst and the resulting hydrogen-mediated anionic polystyrene (HMAPS) was deemed necessary.

[0231] Examples 41 to 42 Examples 41 to 42 are [DMEA - ] x Li y H z Further experiments designed to further elucidate the complex stoichiometry of are presented. These examples were carried out under identical conditions except for the DMEAH:n-butyllithium loading ratio. Numerical details for these two examples are given in Table IX. Experimental details are given below.

[0232] Example 41 [DMEA] at 77-79°C under a hydrocarbon atmosphere - ]Representative example of Li3H2 catalyst 220 mL of anhydrous cyclohexane in a total of 500 mL (385.3 g) was charged to the reactor at 37.6° C. under an atmosphere of dry hydrogen (20 PSIG H2). This stirred solvent (600 A solution of 5.18 g (0.0581 mol.) of N,N-dimethylaminoethanol dissolved in 20 ml of the total amount of anhydrous cyclohexane was charged to the reactor (Configuration VI, 4 pitched blade turbine) through a charge vessel with positive nitrogen pressure. The charge vessel and the transfer line to the reactor were flushed with 50 ml portions from the total amount of anhydrous cyclohexane. 44.95 ml (0.0899 mol.) of a 2.0 M solution of n-butyllithium in cyclohexane in 120 ml of the total amount of 500 ml of cyclohexane was then transferred through the charge vessel to the reactor over 20 minutes, followed by another 50 ml aliquot from the total amount of anhydrous cyclohexane. During the course of the organolithium charge, the agitation speed was maintained at 600 RPM, the reactor pressure rose to 24 PSIG and then fell to 18 PSIG, and the temperature rose to 39.9°C. The headspace of the reactor was then filled with dry H2 to 53 PSIG. Pressurization was then applied (through a subsurface feed line), the agitation was increased to 1000 RPM, and the catalyst solution was brought to 69.9°C in 30 minutes. During this heating step, the H2 pressure reached 64 PSIG. The reactor was further pressurized to 76 PSIG and stirred for 2.5 hours before being vented to 0 PSIG at 73.2°C. The reactor was then heated to 92°C in 30 minutes. This heating step was accomplished by flowing 115°C oil through the reactor jacket. Upon reaching 92°C and 8 PSIG, the hydrogen atmosphere was vented to a mineral oil bubbler to 4 PSIG and cyclohexane vapor began to condense overhead, establishing a hydrocarbon atmosphere. The valve to the mineral oil bubbler was closed, stirring was increased to 1100 RPM and the reactor was cooled to 76.9°C and a pressure of -2 PSIG. Styrene monomer, 98.0 g (0.94 mol.), was mixed with 90 g cyclohexane. The styrene / cyclohexane feed was fed through a subsurface feed line (0.02" ID tip) to the hydrocarbon atmosphere over 60 minutes (5.0 ml / min) while controlling the reaction temperature to never exceed the jacket oil temperature of 79.4°C (80-85°C).

[0233] At the end of the styrene feed, the monomer feed line to the reactor, including the alumina column (basic alumina), was flushed with 50 ml of anhydrous cyclohexane. The reactor was pressurized to 65 PSIG H2. The hydrogen quenched anionic polymerization reaction mixture was transferred under positive H2 pressure to a wash vessel that was preheated (N2 atmosphere) and precharged with 300 ml of deoxygenated water. A 10 ml sample of the unpasteurized hydride reaction mixture was taken during the transfer of the reaction mixture. The sample was faintly pink and clear to light with no precipitated or suspended solids. The faint pink color disappeared when the sample was shaken with air trapped in the sample vial. Standard workup and solvent removal from above was used except that the distillation was considered complete when no more ethylbenzene was removed from the top with nitrogen injecting into the headspace. The resulting resin (90 g) was transferred through the bottom drain valve (with considerable difficulty, using a hot air gun) to a pre-weighed metal tray reinforced with aluminum foil. Analysis of the cooled resin by GPC gave the following: M n :13, 845, M w :38,933,M z :65,777,PD:2.812,σ n =18,63 7. n α3=2.84.

[0234] Examples 42 to 51 Examples 42 to 51 show a reduction in the formation of by-products ethylbenzene and styrene dimer (M n of The results show the improvement in yield typically brought about by a higher relative feed rate and slightly lower hydrogen pressure when TMEDA was used as promoter with catalyst concentrations varying from about 275±50 ppm LiH to about 80±20 ppm LiH during the feed. Details and results regarding these examples are given in Table X. In the course of carrying out this series of examples, it was found that the presence of TMEDA during catalyst generation can have a deactivating effect. Thus, For Examples 42-47, TMEDA was charged to the reactor only after mixing DMEAH and n-butyllithium under hydrogen atmosphere, but the reactor contained some heal from previous experiments (except for Example 42, where the reactor was previously cleaned). n Generally, increases with increasing feed rate and decreasing H2 pressure. Example 48, however, shows that M nThe M decreased to 457 Daltons with increasing feed rate and decreasing H2 (9 PSIG) pressure used. Over two weeks had passed since Examples 47 and 48 were carried out, during which time any reaction mixture left on the reactor surface, i.e., including TMEDA, had flowed to the bottom of the reactor. Additionally, because the reactor had been left for such an extended period of time, a 500 ml flush of anhydrous cyclohexane was used to purge any residues in Example 47 prior to catalyst formation in Example 48. Thus, in Example 49, TMEDA was charged to the reactor prior to charging n-butyllithium, resulting in a high M2 despite the high H2 (11 PSIG) pressure used in this example. n = 540. In the next two experiments, Examples 50 and 51, the catalyst component loading was in a thoroughly rinsed reactor. It is speculated that TMEDA promotes the formation of a lithium hydride which would be formed directly from the superactive but insoluble n-butyllithium, TMEDA, and hydrogen without the intermediate DMEAH to give the hydrocarbon soluble form of LiH. Thus, both Examples 50 and 51 are considered representative of the Examples of Table X and representative of the preferred process of the Examples of this Table.

[0235] Examples 50 and 51 [DMEA - Representative full-scale monomer feed rate at 80 °C for 4Li6H2·2TMEDA catalyst 150 mL of 300 mL (233.7 g) of anhydrous cyclohexane was charged to a well-rinsed reactor at 37° C. under an atmosphere of dry hydrogen (16 PSIG H2). (800 RPM, 4 pitched blade turbine in configuration IV above) was charged with a solution previously generated from 2.53 g (0.0284 mol.) of N,N-dimethylethanolamine, 20 g of ethylbenzene from a total of 170.0 g (1.60 mol), and 50 ml of the 300 ml above, through a charge vessel with positive pressure of nitrogen. Next, 120 g of anhydrous ethylbenzene (from the 170 g above) and 21.25 ml (0.0425 mol) of 2.0 M n-butyllithium dissolved in an additional 50 ml aliquot from the total amount of anhydrous cyclohexane above were mixed in the charge vessel and then pumped under hydrogen into the stirred (800 RPM) reaction mixture over 15 minutes. At the end of the organolithium charge, the agitation speed was increased to 1130 RPM, causing the reactor pressure to drop from a peak pressure of 19 PSIG to an end pressure of 14 PSIG. The temperature rose 2-3°C during the course of catalyst formation. Finally, 3.40 g (0.0293 mol) of TMEDA dissolved in 30 g of anhydrous ethylbenzene was mixed with a final 50 mL aliquot of anhydrous cyclohexane and pumped into the stirred reaction mixture. The reactor headspace was evacuated to 0 PSIG and then pumped with dry H2 (through a subsurface feed line) to 45 PSIG. The reactor was then heated to 73.2°C and the pressure increased to 63 PSIG. Heating was provided by oil at 80°C flowing through the reactor jacket. Once the reaction temperature reached 73°C, the styrene monomer feed was started, feeding 1058.7g (10.17mol.) of styrene. Styrene was fed through a subsurface feed line (0.02" ID tip) against a hydrogen head pressure of 11 PSIG over 116 minutes while attempting to control the reaction temperature at 80°C. Within 10 minutes of starting the monomer feed, the reactor temperature reached 82.8°C. The hydrogen uptake was periodically monitored by closing the valve to the regulator and measuring the time required for a 5 PSIG drop. In this way, the time in seconds required for the pressure to drop 1 PSIG (-1) was recorded. When this value was adjusted for the estimated reactor headspace, the hydrogen uptake in moles of H2 per mole of styrene feed was calculated as: appeared to be constant or nearly constant.

[0236] At the end of the styrene feed, the monomer was added to the reactor, including the alumina column (basic alumina). The feed line was flushed with 50 ml of anhydrous cyclohexane. The styrene feed and flush to the reactor was deemed complete when no further heat of reaction was observed, usually indicated by permanent closure of the coiling coil automatic control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated for 300 The mixture was transferred to a washing vessel containing 1 ml of 5 wt% H2SO4 aqueous solution under positive H2 pressure. The reaction mixture was carefully quenched in the wash reactor at 300 mL. The charge vessel and reactor were then rinsed with 300 mL of anhydrous cyclohexane, and the rinse was transferred to the wash reactor and combined with the crude quench reaction mixture.

[0237] As in Example 51, except for using 10 PSIG H2, the same reagents were weighed out and the conditions were the same. The above steps were repeated with equal loading and conditions within the small inter-experimental variability in reproducibility. Despite a drop in H activity of approximately 10%, hydrogen uptake was approximately 10% higher than in Example 1. It was even faster in Example 51 compared to Example 50.

[0238] During the course of transfer of the unquenched reaction mixtures (Examples 50 and 51), 10 ml samples were taken from each reaction mixture for analysis. These samples were slightly pink to water white, i.e., essentially colorless and transparent to light, with no precipitated or suspended solids. Any color was eliminated by gently shaking / rolling the mixtures or otherwise exposing them to air. These samples were submitted for GPC analysis without quenching the crude reaction mixtures. The GPC analysis, excluding ethylbenzene but including dimer content, was as follows: Example 50M n :525, M w :804, M z :1165, PD:1.449, σ n =383, n α3=2.075, and Mw 10% higher= 2048, Example 51M n :506, M w :758, M z :1080,PD:1.425, σ n =357, n α3=2.001, and M w 10% higher = 1844.

[0239] Standard workup from above gave 2613 g of solution. Wiped thin film evaporation (WFE, 2" glass Pope Still, operated at 50.0 mmHg vacuum, 140°C, wiper speed at 60% of maximum speed, feeding 1.0 liters / hr) yielded M containing dimer. n : 519, M w :783, M z :1122, PD:1.452, σ n =370, n α3=2.0 274, and M. w 10% higher = HMAP of 1997.5 with GPC MWD of 1922 A styrene dimer content of 2.38 GPC area % and M S distribution were obtained in the second WFE run (vacuum 0.1-0.3 mmHg, 172.5°C, wiper speed 60% of maximum speed, feed 1.0 liter / hr). n :601, M w :836, M z :1142, PD: 1.391, σ n =326, n α3=1.923, and M w A HMAPS distribution of 1800.0 g was obtained with a GPC MWD of 10% high=1955.

[0240] Examples 52 to 59 Examples 52-59 demonstrate that the HMAPS process can be carried out without the benefit of additional aromatic solvents, including ethylbenzene. These examples fully demonstrate that the HMAPS process is extremely robust in that it reproducibly produces nearly identical HMAPS distributions under a variety of process conditions. Examples 56-59 demonstrate that any process benefits provided by the use of the promoter TMEDA can be supplemented with increased hydrogen pressure, thereby reducing or even eliminating the use of promoter. This series of high yield examples (polymer yields of about 96% to about 97%, dimer-removed polymer yields of about 86% to about 87%) produced HMAPS distributions with asymmetry values ​​ranging from about 1.67 to 2.00 and HMAPPS distributions with dimer-removed asymmetry values ​​ranging from about 1.63 to 1.82. Examples 58 and 59 are considered representative of these examples. In the practice of these two examples, it was inadvertently discovered that aging of the catalyst provided a more active and preferred catalyst.

[0241] Examples 58 and 59 [DMEA - Representative full-scale monomer feed rate at 80°C for 4Li6H2 catalyst 200 mL of 500 mL (389.5 g) of anhydrous cyclohexane was charged to a well-rinsed reactor at 37° C. under an atmosphere of dry hydrogen (16 PSIG H2). (800 RPM, 4 pitched blade turbine in configuration IV above) was charged with a solution of 2.55 g (0.0285 mol.) of N,N-dimethylethanolamine, previously generated from 70 ml of the total 500 ml of cyclohexane, via positive pressure of nitrogen through the charge vessel. 21.47 ml (0.0429 mol.) of 2.0 M n-butyllithium further dissolved in 170 ml of anhydrous cyclohexane was then transferred from the 500 ml to the charge vessel and then pumped under hydrogen into the stirred (800 RPM) reaction mixture over 15 minutes. At the end of the organolithium charge, the agitation speed was increased to 1130 RPM, causing the reactor pressure to drop back from a peak pressure of 19 PSIG to an end pressure of 16 PSIG. The temperature increased by 2-3°C during the course of catalyst formation. The headspace of the reactor was evacuated to 0 PSIG and then pressurized to 45 PSIG with dry H2 (through a subsurface feed line). The reactor was then heated to 73.2°C with increasing pressure to 63 PSIG. Heating was provided by oil at 80°C flowing through the reactor jacket. Once the reactor temperature reached 73°C, the styrene monomer feed was started, feeding 1061.0 g (10.19 mol.) of styrene. Styrene was fed through a subsurface feed line (0.02" ID tip) over 117 minutes while controlling the reactor temperature at 80°C, against a hydrogen head pressure of 15-17 PSIG. Within 10 minutes of starting the monomer feed, the reactor temperature reached 81.7°C. The hydrogen uptake was periodically monitored by closing the valve to the regulator and measuring the time required for a 5 PSIG drop. In this manner, the time in seconds required for the pressure to drop 1 PSIG(-1) was recorded. When this value was adjusted according to the estimated reactor headspace, the hydrogen uptake in moles of H2 per mole of styrene feed remained constant or nearly constant. It seemed to be pretty constant.

[0242] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (basic alumina), were flushed with 50 ml of anhydrous cyclohexane. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated for 3 h. The solution was transferred under positive H2 pressure to a wash vessel charged with 0.00 ml of 5 wt% aqueous H2SO4 and ≈250 g of ethylbenzene recovered from the wiped film evaporator from the solvent removal in the previous experiment. The reaction mixture was thus carefully quenched in the wash reactor. The charge vessel and reactor were then rinsed with 200 ml of anhydrous cyclohexane, and the rinse was transferred to the wash reactor and combined with the crude quench reaction mixture.

[0243] For Example 59, the catalyst was aged for 3 hours, resulting in a reduction in H2 to 14 PSIG. The above steps were repeated with equal loadings and conditions within the small run-to-run variability in reagent weighing, but adjusted to match the incorporation of Example 58. However, it is clear that the HMAPS distributions produced were nearly identical, except that Example 59 was less asymmetric than Example 58, i.e., 1.826 vs. 1.928, respectively.

[0244] During the course of transfer of the unquenched reaction mixtures (Examples 58 and 59), 10 ml samples were taken from each reaction mixture for analysis. These samples were slightly pink to water white, i.e., essentially colorless and transparent to light, with no precipitated or suspended solids. Any color was eliminated by gently shaking / rotating the mixtures or otherwise exposing them to air. These samples were submitted for GPC analysis without quenching the crude reaction mixtures. All ethylbenzene, but not dimer, was detected. GPC analysis including amounts were as follows: Example 58Mn :570, M w :890,M z :1276, PD:1.434, σ n =427, n α3=1.928, and M w 10% higher= 2168, Example 59M n :584, M w :909, M z :1286,PD:1.415, σ n =436, n α3=1.826, and M w 10% higher = 2166.

[0245] Standard workup from above gave 2487 g of solution. Wiped thin film evaporation (WFE, 2" glass Pope Still, operated at 50.0 mmHg vacuum, 140°C, wiper speed at 60% of maximum speed, feeding 1.0 liters / hour) removed the M, excluding the dimer. n : 690, M w :970,M z :1328, PD:1.406, σ n =440, n α3=1.8 89, and M. w 10% higher = 2094.3 g (washed) with a GPC MWD of 2263 When corrected for the dimer content of the recycled ethylbenzene from the WFE in the 2011 reaction, a HMAPS distribution of 2052 g was produced. The total distribution, including the dimers produced during the course of the reaction, when statistically corrected, is estimated to be: n :612, M w :919.18, M z :1294, P D: 1.406, σ n =434, n α3=1.8791. Second WFE operation (0.1~0. At 3 mmHg vacuum, 160°C, wiper speed 65% of maximum speed, and 1.0 liter / hour feed, the styrene dimer content was 0.48 GPC area % and M n :704, M w:984, M z :1334, PD:1.398, σ n =444, n α3=1.815, and M w 1 A HMAPS distribution of 1825.7 g was obtained with a GPC MWD of 0% high=2268.

[0246] A third WFE run was performed to obtain low molecular weight oligomers in order to determine the microstructure of this HMAPS PS distribution. Thus, a 125 g sample of the 1825 g product distribution recovered from the second WFE run was stripped of oligomers (0.13 mmHg vacuum, 199.5°C, wiper speed 85% of maximum speed, 2.0 g / min feed). This third WFE run yielded 22 g of styrene oligomers, whose GC analysis showed that 99.97% of the chains had the desired "head-to-tail" microstructure, with few, if any, chains having unsaturated chain ends due to lithium hydride elimination (FW). i -2) It has a fine structure It was shown that this was expected (see Figure 16). Spiking experiments on the real (FWi-14) material clearly demonstrated that this composition does not contain this microstructure.

[0247] Examples 60 to 67 Examples 60-67 demonstrate that the HMAPS process can be performed with dry (<10 ppm moisture) reclaimed solvent obtained from the preceding examples. Solvent reclamation involves combining cyclohexane and ethylbenzene from the wash reactor strip and the first WFE run and azeotropic distillation of water followed by simple distillation to a pot temperature of about 140° C. at 1 atmosphere. Further drying is achieved using activated molecular sieves. Due to the less than favorable process conditions used in Examples 61 and 62 and, to a lesser extent, Examples 60 and 67, these examples show a decline in the MWD produced and H2 uptake during the last 8-13% of the feed. As is evident from the figure, higher molecular weight material was produced at the end of the monomer feed.

[0248] Of the experiments, Example 61 produced the most unfavorable results, with M w 10% increase to 2629da For Example 61, under the less favorable relative styrene to catalyst feed ratio as a result of using a lower catalyst loading, hydrogen mass transfer became inefficient during the last 13% of the feed. Example 60 is comparable to Examples 58 (no aging) and 59 (3 hour aging) except that the catalyst was aged for 1 hour and the solvent contained recycled ethylbenzene. Initially, this catalyst appeared to be more active than either Examples 58 or 59, but the catalyst activity seemed to decrease during the last 8 minutes of the styrene feed, resulting in a slightly higher molecular weight tail. For Example 61, an attempt was made to reduce the catalyst loading by 20%, but this resulted in a high molecular weight tail as hydrogen uptake slowed during the last 13 minutes of the feed. In the course of further establishing the scope of the invention (Examples 62-67), a mixture It was found that the reduction in the catalyst speed (1000 rpm vs. the standard 1130 rpm) could be offset by: i) increasing the temperature, and / or ii) decreasing the total monomer feed rate, and / or iii) decreasing the monomer feed rate, and / or iv) increasing the hydrogen pressure, and v) increasing the catalyst age time. The results of these experiments are shown in Table XII. Examples 64 and 65 are considered representative.

[0249] Examples 64 and 65 Recycled solvent recovered from the previous example was used [DMEA - Representative full-scale monomer feed rate at 90°C for 4Li6H2 catalyst 220 mL of a total of 320 mL (252.65 g) of regenerated anhydrous solvent [79.4 wt% cyclohexane (CH), 20.6 wt% ethylbenzene (EB)] was charged to a well-rinsed reactor at 37° C. under an atmosphere of dry hydrogen (16 PSIG H2). This stirred solvent (800 RPM, 4 pitched blade turbine in configuration IV above) was charged with a solution previously generated from 2.55 g (0.0285 mol.) of N,N-dimethylethanolamine and 20 ml of cyclohexane combined with 50 ml of the regenerated solvent via positive nitrogen pressure through the charge vessel. 21.47 ml (0.0429 mol.) of 2.0 M n-butyllithium dissolved in 120 ml of anhydrous cyclohexane was then transferred to the charge vessel and combined with 50 ml of the regenerated solvent (negligible backmixing). This unmixed solution was then pumped under hydrogen into the stirred (800 RPM) reaction mixture over 15 minutes. At the end of the organolithium charge, the agitation speed was increased to 1130 RPM and the reactor pressure dropped from a peak pressure of 19 PSIG back to an end pressure of 16 PSIG. The temperature increased by 2-3°C during the course of catalyst formation. The reactor headspace was evacuated to 0 PSIG and then flushed with dry H2 ( The reactor was then heated to 72° C. with increasing pressure to 63 PSIG and further pressurized to 72 PSIG. Heating was accomplished by 80° C. oil flowing through the reactor jacket, i.e., the reactor was held at 72° C. and 72 PSIG for 60 minutes and then vented to 17 PSIG. The reactor was then heated to 82° C. and pressure was maintained at 17 PSIG by venting as needed. Heating was accomplished by 90° C. oil flowing through the reactor jacket, i.e., the reactor was held at 82° C. and 17 PSIG for 75 minutes, at which point a styrene monomer feed was started and 1015.0 g (9.75 mol.) styrene was fed. Styrene was fed through a subsurface feed line (0.02" ID tip) over 119 minutes with the reactor temperature controlled at 80°C against a hydrogen head pressure of 13-15 PSIG. Within 10 minutes of starting the monomer feed, the reactor temperature reached 81.7°C. Hydrogen uptake was periodically monitored by closing the valve to the regulator and measuring the time required for a 5 PSIG drop. In this manner, the time in seconds required for the pressure to drop 1 PSIG(-1) was recorded. When this value was adjusted according to the estimated reactor headspace, the hydrogen uptake in moles of H2 per mole of styrene feed appeared to be constant or nearly constant.

[0250] At the end of the styrene feed, the monomer feed lines to the reactor, including the alumina column (basic alumina), were flushed with 50 ml of anhydrous cyclohexane. The styrene feed and flush to the reactor was considered complete when no further heat of reaction was observed, usually indicated by the permanent closure of the automatic coiling coil control valve. The unquenched polymerization reaction mixture was preheated (N2 atmosphere) and preheated for 3 h. 5.13 g of acetic acid dissolved in 300 ml of HO and the original solvent from the previous experiment. The mixture was transferred under positive H2 pressure to a washing vessel loaded with 300 ml of regeneration solvent that had been previously collected from the removal. The reaction mixture was thus carefully quenched in the wash reactor. The charge vessel and reactor were then rinsed with 200 ml of regenerating solvent, and the rinse was transferred to the wash reactor and combined with the crude quench reaction mixture.

[0251] In Example 65, 1035.8 g of styrene was fed over 121 minutes, and the catalyst was The above steps were repeated with equal loadings and conditions within the small inter-experimental variability in the weighing out of reagents, except for aging for 34 min at 72° C. and 26 min at 82° C. It is clear that the HMAPS distributions produced were approximately equal within the experimental error of the GPC analysis.

[0252] During the course of transfer of the unquenched reaction mixtures (Examples 64 and 65), 10 ml samples were taken from each reaction mixture for analysis. These samples were slightly pink to water white, i.e., essentially colorless and transparent to light, with no precipitated or suspended solids. Any color was eliminated by gently shaking / rolling the mixtures or otherwise exposing them to air. These samples were submitted for GPC analysis without quenching the crude reaction mixtures. The GPC analysis, excluding ethylbenzene but including dimer content, was as follows: Example 64M n :550,M w :835, M z :1173, PD:1.405, σ n =396, n α3=1.832, and M w 10% higher = 1982, Example 65M n :558, M w :848, M z :1188, PD:1.401, σ n =402, n α3=1.805, and M w 10% higher = 2003.

[0253] Standard workup from above gave 2487 g of solution. Wiped thin film evaporation (WFE, 2" glass Pope Still, ...

Claims

1. 1. A method for conducting a hydrogen-mediated, salt-like hydride initiated polymerization, comprising feeding one or more anionically polymerizable hydrocarbon monomers to a reaction medium containing a soluble salt-like hydride catalyst under an atmosphere containing molecular hydrogen.

2. A method for carrying out hydrogen mediated salt-like hydride initiated polymerization comprising the step of reacting one or more anionically polymerizable hydrocarbon monomers with (i) molecular hydrogen, (ii) organolithium and / or organomagnesium compounds, (iii) optionally a polytertiary amine compound, (iv) a polar complexing agent selected from a tertiary amino alcohol compound, a tertiary amino ether alcohol, an ether alcohol, or combinations thereof, (v) optionally an alkali metal or metal alloy and / or a solid salt-like hydride and / or a salt-like metal amide, (vi) optionally a pK of at least one C—H covalent bond. a is the pK of toluene a 2.75 pK higher than that of a From the unit , pK of toluene a -4.30 pK a Aromatic hydrocarbons falling within the range below the unit, and (vii) H 2 pK a said process comprising feeding said aromatic hydrocarbon to a reaction medium comprising a soluble salt-like hydride LOXSH catalyst formed from a hydrocarbon solvent, which may be the same as or different from said aromatic hydrocarbon, having a high molecular weight.

3. 3. The method of claim 1 or 2, wherein the anionically polymerizable hydrocarbon monomer is a vinyl aromatic monomer.

4. 3. The method according to claim 1 or 2, wherein the anionically polymerizable hydrocarbon monomers are styrene, the o-, m- and p-isomers of methylstyrene, p-isopropylstyrene, 2,4-diethylstyrene, o-ethylstyrene, 3,5-diisobutylstyrene, 2,6-dimethylstyrene, 2-ethyl-4-methylstyrene.

5. 3. The method of claim 1 or 2, wherein the anionically polymerizable hydrocarbon monomer is 1) a vinyl aromatic monomer and a styrenic monomer, or 2) a styrenic monomer and styrene, or 3) styrene.

6. The reaction medium has a pK a H 2 3. The method according to claim 1 or 2, wherein the hydrocarbon solvent is higher than that of claim 1.

7. 3. The method of claim 1 or 2, wherein the partial pressure of molecular hydrogen is maintained at a pressure between about 0.5 bar and about 19.0 bar.

8. 3. The method of claim 1 or 2, wherein the temperature of the method is maintained in the range of about 20° C. to about 130° C.

9. 3. The process of claim 1 or 2, wherein the molar ratio of total monomer charge to initially formed soluble salt-like hydride catalyst is from about 10:1 to about 1000:

1.

10. 3. The method of claim 1 or 2, wherein the salt-like hydride catalyst is a LOXSH catalyst.

11. the monomer is styrene, the salt-like hydride LOXSH catalyst is a LOXLiH catalyst formed from molecular hydrogen, an organolithium compound, and optionally TMEDA, N,N-dimethylethanolamine, in a reaction medium of a hydrocarbon solvent comprising one or more of ethylbenzene, cyclohexane, and methylcyclohexane, the polymerization temperature is maintained between about 20° C. and less than about 100° C., the partial pressure of molecular hydrogen is maintained between about 0.5 bar and about 6.0 bar, and the ratio of the total monomer charge to the moles of soluble salt-like hydride catalyst initially formed is about 1.0 bar.

3. The method of claim 2, wherein the ratio is from about 10:1 to about 600:

1.

12. The LOXLIH catalyst has the formula [DMEA - ] x Li y H z (i) about y equivalents of an organolithium compound; (ii) optionally a TMEDA compound; (iii) about x equivalents of dimethylaminoethanol; (iv) optionally ethylbenzene; (v) H 2 pK a and (vi) molecular hydrogen, the amount of hydride produced from the step of contacting said aromatic hydrocarbon with a hydrocarbon solvent, which may be the same or different from said aromatic hydrocarbon, and (vi) molecular hydrogen, wherein the amount of hydride produced, z, is given by the formula z=y−x, where x, y, and z are positive real integers or fractions greater than zero, and said formula further represents an N,N,N′,N′-tetramethylethylenediamine (TMEDA) ligand complex, i.e., [DMEA - ] x Li y H z XTMEDA was reacted with the catalyst [DMEA - ] x Li y H z 12. The method of claim 11, wherein the hydroxyl group can include a molar ratio of X moles of TMEDA per mole of hydroxyl group, where X=0.0001 to about 8.

0.

13. The monomer is styrene and the salt-like hydride LOXSH catalyst is a bimetallic LOXMgH formed from molecular hydrogen, an organolithium compound, and an organomagnesium compound, optionally TMEDA, N,N-dimethylethanolamine, in a reaction medium of a hydrocarbon solvent including one or more of ethylbenzene, cyclohexane, and methylcyclohexane. 2 catalyst 3. The process of claim 2, wherein the polymerization temperature is maintained between 20° C. and 90° C., the molecular hydrogen partial pressure is maintained between about 0.5 bar and about 6.0 bar, and the molar ratio of total monomer charge to initially formed soluble salt-like hydride catalyst is from about 10:1 to about 600:

1.

14. 14. The method of claim 2, 11, or 13, wherein the soluble LOXSH catalyst comprises a polytertiary amine (PTA) promoter and is formed with an alkali metal or metal alloy and / or a solid salt-like hydride and / or a salt-like metal amide, and the molar ratio of PTA to the total alkali metal and alkaline earth metal charged in forming the LOXSH catalyst is from 1:10,000 to about 8:

1.

15. 14. The method of claim 2, 11, or 13, wherein the organolithium compound is an n-butyllithium, sec-butyllithium, t-butyllithium, allyllithium, vinyllithium, phenyllithium, 1-hexyl-1-phenyllithium, 1-hexyl-1,1-diphenyllithium, cyclohexyllithium, or poly(styryl)lithium compound, which may be added or generated in situ.

16. 14. The method of claim 2 or 13, wherein the organomagnesium compound is a butylethylmagnesium (BEM), di-n-butylmagnesium (DBM), n-butyl-n-octylmagnesium, di-n-octylmagnesium, dicyclohexylmagnesium, or poly(styryl)magnesium compound which may be added or generated in situ.

17. The polar complexing agent has the structure: 【Chemistry 1】 R is independently an organic group capable of forming bonds with one or more tertiary amines and one hydroxyl; R 1 is independent and can be used by other 3rd class ami i) for I, II, III, IV, V, and VI, O or NR 1 and ii) and VII is O or N.R. 1 or CH 2 and index value n is independently an integer equal to or greater than 0.

18. 3. The method of claim 2, wherein the polar complexing agent is at least one amino alcohol selected from dimethylaminoethanol, diethylaminoethanol, N-methyldiethanolamine, 3-dimethylamino-1-propanol, 2-[2-(dimethylamino)ethoxy]ethanol, 1-(2-hydroxyethyl)piperidine, 1-(2-hydroxyethyl)morpholine, 1-(2-hydroxyethyl)pyrrolidine, or 1-methyl-2-pyrrolidinemethanol.

19. 3. The method of claim 2, wherein the PTA promoter is comprised in a molar ratio of the sum of alkali metals and alkaline earth metals to PTA of about 10,000 to 1.0 to about 1.0 to about 8.

0.

20. 3. The method of claim 2, wherein the PTA accelerator is at least one of N,N,N',N'-tetramethylethylenediamine (TMEDA), N,N,N',N'',N''-pentamethyldiethylenetriamine (PMDETA), sparteine, isosparteine, and 1,4-methylpiperazine.

21. 3. The method of claim 2, wherein the aromatic hydrocarbon is at least one of benzene, toluene, mesitylene, ethylbenzene, n-propylbenzene, n-butylbenzene, isobutylbenzene, amylbenzene, 1.2-darylethane, 1,3-diarylpropane, cumene, t-butylbenzene, 1-alkylnaphthalene, 2-alkylnaphthalene, styrene dimer, or low molecular weight styrene oligomer distribution.

22. The catalyst has the empirical chemical formula: a) [PCA - ] 4 Li 6 H 2 , b) [PCA - ] 4 Li 8 H 4 , c) [PCA - ] 2 Li 6 H 4 , d) [PCA - ] 4 Li 12 H 8 , e) [PCA - ] 5 Li 15 H 10 , H - ] 5 Li 12 H 7 g)[PCA - ] 2 Li 5 H 3 h)[PCA - ] 4 Li 4 MgH 2 、i)[PCA - ] 4 Li 4 Mg 2 H 4 、j)[PCA - ] 2 Li 4 MgH 4 、k)[PCA - ] 4 Li 6 Mg 3 H 8 、l)[PCA - ] 5 Li 9 Mg 3 H 10 m)[PCA - ] 5 Li 6 Mg 3 H 7 、n )[PCA - ] 2 Li 3 MgH 3 、o)[PCA - ] 4 Li 5 KH 2 p)[PCA - ] 4 Li 7 K H 4 , and q) [PCA - ] 2 Li 5 KH 4 wherein: - ] independently represents an alkoxide of an alcohol of the corresponding polar complexing agent reagent that has donated one proton to a more basic species, and said empirical chemical formula can optionally further include a PTA ligand complex in a molar ratio of the sum of the alkali metal and alkaline earth metal to PTA of about 10,000 to about 1.0 to about 1.0 to about 8.

0.

23. [PCA - ] is independently [DMEA - ], "DMAEOE - ] or [MEOE - 23. The method of claim 22, wherein

24. (i) an organolithium compound and optionally an organomagnesium compound; (ii) optionally a poly-tertiary amine accelerator compound; (iii) a polar complexing agent selected from a tertiary amino alcohol, a tertiary amino ether alcohol, an ether alcohol, or a combination thereof; (iv) optionally a pK of at least one C—H covalent bond. a is the pK of toluene a 2.75 pK higher than that of a From the units, the pK of toluene a -4.30 pK a Aromatics within the range below the unit (v) optionally a solid alkali metal or alkaline earth metal hydride, or an alkali metal or alkali metal alloy, or an alkali or alkaline earth amide; (vi) H 2 pK a a hydrocarbon solvent, which may be the same as or different from said aromatic hydrocarbon, having a high molecular weight; and (vii) molecular hydrogen.

25. The polar complexing agent has the structure: 【Chemistry 2】 R is an organic group capable of forming bonds with one or more tertiary amines and one hydroxyl; R 1 is independently further substituted with another tertiary amine. an optionally substituted organic group, Σ being: i) O or NR for I, II, III, IV, V, and VI; 1 and ii) O or NR for VII. 1 or CH 2 of 25. The hydrocarbon soluble catalyst or reagent composition of claim 24, wherein index value n is independently an integer equal to or greater than 0.

26. 25. The hydrocarbon soluble catalyst or reagent composition of claim 24 formed from reagents including solid alkali hydrides, alkali metals and / or alkali metal alloys, and / or salt-like metal amides, wherein the total ratio of polar complexing agent to alkali metal ranges from about 1:1.05 to about 1:6, and the molar ratio of organolithium compound to alkali metal is from 10,000:1 to 1:

2.

27. 25. The hydrocarbon soluble catalyst or reagent composition of claim 24, wherein the catalyst is a monometallic lithium hydride LOXLiH catalyst, and wherein the ratio of polar complexing agent to lithium is in the range of from 1:1.05 to about 1:

6.

28. A hydrocarbon soluble catalyst or reagent composition, said catalyst having the formula [DMEA - ] x Li y H z wherein z=y-x, and x, y, and z are positive real integers or fractions greater than zero, and optionally said formula can further include a N,N,N',N'-tetramethylethylenediamine (TMEDA) ligand complex in a molar ratio of the sum of the lithium to the TMEDA of from about 10,000 to 1.0 to about 1.0 to about 8.

0.

29. 29. The lithium hydride LOXLiH catalyst of claim 28 having one or more of the following formulas: [DMM] - ]Li 2 H[DMEEA - ] 2 Li 3 H[DMEEA - ]Li 3 h 2 [DME] - ]Li 4 h 3 [DME] - ] 2 Li 4 h 2 [DME] - ] 3 Li 4 H[DMEEA - ]Li 5 h 4 [DME] - ] 2 Li 5 h 3 [DME] - ] 3 Li 5 h 2 [DME] - ] 4 Li 5 H[DM E A - ]Li 6 h 5 [DME] - ] 2 Li 6 h 4 [DME] - ] 3 Li 6 h 3 [DME] - ] 4 Li 6 h 2 [DME] - ] 5 Li 6 H[DMEEA - ]Li 7 h 6 [DME] - ] 2 Li 7 h 5 [DME] - ] 3 Li 7 h 4 [DME] - ] 4 Li 7 h 3 [DME] - ] 5 Li 7 h 2 [DME] - ] 6 Li 7 H[DMEEA - ]Li 8 h 7 [DME] - ] 2 Li 8 h 6 [DME] - ] 3 Li 8 h 5 [DME] - ] 4 Li 8 h 4 [DME] - ] 5 Li 8 h 3 [DME] - ] 6 Li 8 h 2 [DME] - ] 7 Li 8 H[DMEEA - ]Li 9 h 8 [DME] - ] 2 Li 9 h 7 [DME] - ] 3 Li 9 H 6 [DMEA - ] 4 Li 9 H 5 [DMEA - ] 5 Li 9 H4 [DMEA - ] 6 Li 9 H 3 [DMEA - ] 7 Li 9 H 2 [DMEA - ] 8 Li 9 H[DMEA - ]L) 10 H 9 [DMEA - ] 2 Li 10 H 8 [DMEA - ] 3 Li 10 H 7 [DMEA - ] 4 Li 10 H 6 , [DME A - ] 5 Li 10 H5 [DMEA - ] 6 Li 10 H 4 [DMEA - ] 7 Li 10 H 3 [DMEA - ] 8 Li 10 H 2 [DMEA - ] 9 Li 10 H[DMEA - ]L) 11 H 10 [DMEA - ] 2 Li 11 H 9 [DMEA - ] 3 Li 11 H 8 [DMEA - ] 4 Li 11 H 7 [DMEA - ] 5 Li 11 H 6 [DME] - ] 6 Li 11 h 5 [DME] - ] 7 Li 11 h 4 [DME] - ] 8 Li 11 h 3 [ DM - ] 9 Li 11 h 2 [DME] - ] 9 Li 11 H[DMEEA - ]Li 12 h 11 [DME] - ] 2 Li 12 h 10 [DME] - ] 3 Li 12 h 9 [DME] - ] 4 Li 12 h 8 [DME] - ] 5 Li 12 H7 [DMEA - ] 6 Li 12 H 6 [DMEA - ] 7 Li 12 H 5 [DMEA - ] 8 Li 12 H 4 [DMEA - ] 9 Li 12 H 3 [DMEA - ] 10 Li 12 H 2 [DMEA - ] 11 Li 12 H[DMEA - ]L) 13 H 12 [DMEA - ] 2 Li 13 H 11 [DMEA - ] 3 Li 13 H 10 [DMEA - ] 4 Li 13 H 9 [DMEA - ] 5 Li 13 H7 [DMEA - ] 6 Li 13 H 7 , [ DM - ] 7 Li 13 h 6 [DME] - ] 8 Li 13 h 5 [DME] - ] 9 Li 13 h 4 [DM] EA - ] 10 Li 13 H 3 [DMEA - ] 11 Li 13 H 2 [DMEA - ] 12 Li 13 H[DME A - ]Li 14 h 13 [DME] - ] 2 Li 14 h 12 [DME] - ] 3 Li 14 h 11 [DME] - ] 4 Li 14 h 10 [DME] - ] 5 Li 14 H9[DMEA - ] 6 Li 14 h 8 [DME] - ] 7 Li 14 h 7 [DME] - ] 8 Li 14 h 6 [DME] - ] 9 Li 14 h 5 [DME] - ] 10 Li 14 h 4 [DME] - ] 11 Li 14 h 3 [DME] - ] 12 Li 14 h 2 [DME] - ] 13 Li 14 H[DMEEA - ]Li 15 h 14 [DME] - ] 2 Li 15 h 13 [DME] - ] 3 Li 15 h 12 、DME - ] 4 Li 15 h 11 [DME] - ] 5 Li 15 h 10 [DME] - ] 6 Li 15 h 9 [ DM - ] 7 Li 15 h 8 [DME] - ] 8 Li 15 h 7 [DME] - ] 9 Li 15 h 6 [DM] EA - ] 10 Li 15 H 5 [DMEA - ] 11 Li 15 H 4 [DMEA - ] 12 Li 15 H 3 [DMEA - ] 13 Li 15 H 2 [DMEA - ] 14 Li 15 H.

30. Chemical formula [DMEA - ] x Li y H z 29. The lithium hydride LOXLiH catalyst of claim 28, comprising: (i) y equivalents of an organolithium compound; (ii) any amount of (iii) x equivalents of dimethylaminoethanol; (iv) optionally ethylbenzene; (v) H 2 pK a the amount of hydride produced from the step of contacting in a hydrocarbon solvent having a high catalytic activity, which may be ethylbenzene or another aromatic hydrocarbon, and (vi) molecular hydrogen, z, is given by the formula z=y−x, where z, y, and z are positive real integers or fractions greater than zero.

31. Chemical formula [DMEA - ] x Li y H z 29. The monometallic lithium hydride LOXLiH catalyst of claim 28 having: a) forming a solution or suspension of about y equivalents of (i), optionally (ii), about x equivalents of (iii), and optionally (iv) thoroughly mixed and reacted in (v) under an inert atmosphere to form a precursor "ate" complex, which is then converted into a precursor "ate" complex by exchanging or otherwise replacing the inert atmosphere with hydrogen [DMEA - ] x Li y H z or b) forming in an external reactor a solution or suspension of about x equivalents of a portion of (i) and optionally (ii), about x equivalents of (iii), and optionally (iv) thoroughly mixed and reacted during (vi), and transferring said solution under hydrogen to a hydride forming reactor, followed by charging with about z or y-x equivalents of the remainder of (i); or c) forming a solution or suspension of thoroughly mixed and reacted, optionally (ii), about x equivalents of (iii), and optionally (iv) in (v) under a hydrogen atmosphere, and then feeding y equivalents of (i) all at once or in large part gradually; or d) forming a solution or suspension of thoroughly mixed and reacted, optionally (ii), about x equivalents of (iii), and optionally (iv) in (v) under a hydrogen atmosphere, followed by continuously or gradually feeding about y equivalents of (i) over a period of more than about 3 minutes; or e) forming a solution or suspension of about x equivalents of (iii) and, optionally, (iv) in (v) under a hydrogen atmosphere, which are thoroughly mixed and reacted, followed by continuously or gradually feeding about y equivalents of (i) over a period of more than about 3 minutes, followed by the addition of the desired amount of (ii); or f) forming a solution or suspension of x equivalents of (iii) and, optionally, (iv) in a portion of (v) under a hydrogen atmosphere, which have been thoroughly mixed and reacted, and then continuously or gradually feeding about y equivalents of (i), previously diluted further with a portion of (iv) and / or (v), over a period of more than about 3 minutes, followed by the addition of the desired amount of (ii); or g) forming a solution or suspension of about x equivalents of (i) and, optionally, (iv) in a portion of (v) under a hydrogen atmosphere, thoroughly mixed and reacted, and then feeding about x equivalents of (iii), previously diluted further with a portion of (iv) and / or (v), all at once or continuously or gradually, until the entire charge of (iii) is completed, followed by feeding about z or y-x equivalents of (i), followed by the desired amount of (ii); or h) (a) dissolving about 3 equivalents of (i) in a solvent comprising ethylbenzene at 1 to 10 times the weight of a 2.0 M solution of (i); (b) feeding (a) over a period of about 15 to 25 minutes to about 2 equivalents of (iii) dissolved in 24 to 28 parts by weight of (iv) and / or (v) not including (ii) under a hydrogen atmosphere of 16 to 21 PSIG at about 35° C. to about 40° C. with just enough stirring for mass transfer of hydrogen to the condensed phase; (c) optionally adding (ii); (d) increasing the hydrogen pressure to about 40 to about 50 PSIG and then increasing the mixing for more efficient hydrogen mass transfer; (e) warming the solution formed in (b) to about 65 to about 85° C.; (f) further increasing the hydrogen pressure to about 75 PSIG; and (g) aging the catalyst for a period of about 1 hour to greater than about 5 hours.

32. The catalyst is bimetallic lithium magnesium hydride LOXMgH 2 24. A catalyst.

1. The hydrocarbon soluble catalyst or reagent composition according to claim 1, wherein the ratio of polar complexing agent to total metal equivalents, with lithium providing 1 equivalent and magnesium providing 2 equivalents, ranges from 1:1.05 to about 1:

6.

33. The catalyst has the empirical formula: a) [PCA - ] 4 Li 6 H 2 , b) [PCA - ] 4 Li 8 H 4 , c) [PCA - ] 2 Li 6 H 4 , d) [PCA - ] 4 Li 12 H 8 , e) [PCA - ] 5 Li 15 H 10 , f) [PCA - ] 5 Li 12 H 7 g)[PCA - ] 2 Li 5 H 3 h)[PCA - ] 4 Li 4 MgH 2 、 i)[PCA - ] 4 Li 4 Mg 2 H 4 、j)[PCA - ] 2 Li 4 MgH 4 、k)[PCA - ] 4 L i 6 Mg 3 H 8 , l) [PCA - ] 5 Li 9 Mg 3 H 10 , m) [PCA - ] 5 Li 6 Mg 3 H 7 , n) [PCA - ] 2 Li 3 MgH 3 , o) [PCA - ] 4 Li 5 KH 2 , p) [PCA - ] 4 Li 7 KH 4 , and q) [PCA - ] 2 Li 5 KH 4 wherein: - ] are independently more basic 25. The hydrocarbon soluble catalyst or reagent composition of claim 24, wherein the empirical formula represents an alkoxide of an alcohol of the corresponding polar complexing agent reagent that has donated one proton to a polar species, said empirical formula optionally further comprising a PTA ligand complex in a molar ratio of the sum of alkali metal and alkaline earth metal to PTA of about 10,000 to 1.0 to about 1.0 to about 8.

0.

34. [PCA - ] is independently [DMEA - ], "DMAEOE - ] or [MEOE - 34. The hydrocarbon soluble catalyst or reagent composition of claim 33, wherein

35. 25. The hydrocarbon soluble catalyst or reagent composition of claim 24 further formed from a reagent comprising a solid alkali hydride, an alkali metal and / or an alkali metal alloy, and / or a salt-like metal amide, wherein the total ratio of polar complexing agent to alkali metal is in the range of about 1:1.05 to about 1:6, and the molar ratio of organolithium compound to alkali metal is from 10,000:1 to 1:

2.

36. 25. The hydrocarbon soluble monometallic catalyst or reagent composition of claim 24 formed from molecular hydrogen and any of the following: a) a polar complexing agent and an organolithium compound reacted to form a lithium alkoxide, the total molar ratio of polar complexing agent to alkali metal being in the range of from about 1:1.05 to about 1:6; or b) a polar complexing agent and an organolithium compound, the molar ratio of polar complexing agent to lithium being in the range of from about 1:1.05 to about 1:6; or c) a polar complexing agent, at least one solid lithium hydride and / or lithium metal and / or lithium amide, and an organolithium compound, with the total molar ratio of polar complexing agent to lithium ranging from about 1:1.05 to about 1:

6.

37. 25. The hydrocarbon soluble bimetallic catalyst or reagent composition of claim 24 formed from molecular hydrogen and any of the following, wherein the molar ratio of lithium to magnesium in said catalyst composition is from 10,000:1 to 1:6: a) a polar complexing agent and an organolithium compound and / or an organomagnesium compound reacted to form at least one alkali metal or alkaline earth metal alkoxide, the total molar ratio of polar complexing agent to alkali metal being in the range of from about 1:1.05 to about 1:6; or b) a polar complexing agent, an organolithium compound and / or an organomagnesium compound reacted to form lithium and / or magnesium alkoxides, the molar ratio of polar complexing agent to total metal equivalents being in the range of about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium providing 2 equivalents; or c) a polar complexing agent, an organolithium compound, and an organomagnesium compound, wherein the molar ratio of polar complexing agent to total metal equivalents is in the range of about 1:1.05 to about 1:6, with 1 equivalent of lithium being and magnesium provides 2 equivalents; or d) a polar complexing agent, at least one of solid lithium hydride, metallic lithium, solid magnesium hydride, lithium amide, magnesium diamide, at least one organolithium compound and / or organomagnesium compound, wherein the molar ratio of polar complexing agent to total metal equivalents is in the range of about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium providing 2 equivalents; or e) a polar complexing agent, at least one solid magnesium hydride and / or metallic lithium, and an organolithium compound, wherein the molar ratio of polar complexing agent to total metal equivalents ranges from about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium providing 2 equivalents; or f) a polar complexing agent, solid magnesium hydride, and an organolithium compound, wherein the molar ratio of polar complexing agent to total metal equivalents ranges from about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium providing 2 equivalents.

38. 25. The method of claim 24, further comprising: (i) an organolithium compound with or without an organomagnesium compound; (ii) optionally a poly-tertiary amine promoter compound; (iii) a polar complexing agent selected from a tertiary amino alcohol, a tertiary amino ether alcohol, an ether alcohol, or a combination thereof; (iv) optionally a polar complexing agent selected from a pK of at least one C-H covalent bond. a is the pK of toluene a 2.75 pK higher than that of a From the unit , pK of toluene a -4.30 pK a (v) optionally a solid alkali metal or alkaline earth metal hydride, or an alkali metal or alkali metal alloy, or an alkali or alkaline earth amide; (vi) H 2 pK a and (vii) molecular hydrogen.

39. 39. The method of claim 38, wherein (i), (ii), (iii), optionally (iv), and optionally (v) and (vi) are: a) forming a solution or suspension of thoroughly mixed and reacted (i), optionally (ii), (iii), optionally (iv), and optionally (v) in (vi) under an inert atmosphere, followed by: 1) providing a portion of the monomer to the “ate” complex thus formed, followed by 2) replacing the inert atmosphere with H 2 Exchange with or otherwise H 2 or by converting to LOXSH by replacing b) forming a solution or suspension of thoroughly mixed and reacted (i), optionally (ii), (iii), optionally (iv), and optionally (v) in (vi) under an inert atmosphere to produce a precursor "ate" complex, which is then converted to LOXSH by exchanging or otherwise replacing the inert atmosphere with hydrogen; or c) by forming in an external reactor a solution or suspension of a portion of (i) and optionally (ii), (iii), a desired amount of (iv), and optionally (v), thoroughly mixed and reacted in (vi), and transferring said solution under hydrogen to the polymerization reactor, followed by charging the remainder of (i); or d) forming a solution or suspension of thoroughly mixed and reacted, optionally (ii), (iii), optionally (iv), and optionally (v) in (vi) under a hydrogen atmosphere, by feeding a portion of the monomers and then adding (i) in one portion; or e) forming a solution or suspension of thoroughly mixed and reacted, optionally (ii), (iii), optionally (iv), and optionally (v) in (vi) under a hydrogen atmosphere, followed by feeding (i) for a period of more than about 3 minutes, followed by feeding monomers, if desired or necessary; or f) forming a solution or suspension of (iii), optionally (iv), and optionally (v) under a hydrogen atmosphere in (vi) that have been thoroughly mixed and reacted, followed by providing (i) for a period of more than about 3 minutes, followed by the addition of a desired amount of (ii), followed optionally by or The process as described above, optionally contacting or otherwise mixing by providing a monomer.

40. 40. The method of claim 38 for forming the hydrocarbon soluble catalyst or reagent composition, wherein the hydrogen partial pressure used in forming the catalyst ranges from about 0.1 bar to about 300 bar.

41. 40. The method of claim 38 for forming the hydrocarbon soluble catalyst or reagent composition, wherein the temperature used in forming the catalyst ranges from about -96°C to about 130°C.

42. 40. The method of claim 38 for forming the hydrocarbon soluble catalyst or reagent composition, wherein the loading ratio of the polar complexing agent to the molar equivalents of the organolithium compound and / or organomagnesium used in forming the catalyst is in the range of from about 1:1.05 to about 1:6 moles of polar complexing agent per mole of metal alkyl equivalent, with lithium providing one equivalent and magnesium providing two equivalents.

43. 40. The method of claim 38 for forming the hydrocarbon soluble catalyst or reagent composition, wherein the molar ratio of PTA to total metal is from about 10,000 to 1.0 to about 1.0 to about 8.

0.

44. 40. The method of claim 38 for forming the hydrocarbon soluble catalyst or reagent composition, comprising: a) first contacting said polar complexing agent with an alkali alkoxide-forming reagent, thereby forming a reaction mixture, wherein the stoichiometric molar equivalent ratio of polar complexing agent to alkoxide-forming reagent is from about 1:1 to less than 1:1; b) the alkoxide-forming reagent is at least one of a) a solid alkali hydride, b) an alkali metal, c) an alkali metal alloy, d) and an alkali amide, e) a magnesium amide, f) an organolithium compound, g) an organomagnesium compound; c) further adding the organolithium compound and / or the organomagnesium compound; d) the ratio of the total polar complexing agent to the alkali metal ranges from about 1:1.05 to about 1:6; e) the molar ratio of lithium to non-lithium alkali metal is in the range of from 1:2 to about 10,000:1, or the alkali metal of the catalyst composition is lithium only; f) further reducing the reaction product formed with hydrogen to form said hydrocarbon soluble salt-like hydride catalyst or reagent.

45. 40. The method of claim 38 for forming the hydrocarbon soluble catalyst or reagent composition, comprising: a) contacting said polar complexing agent first with at least one of the following alkoxide-forming reagents: a) solid lithium hydride, b) lithium metal, c) magnesium hydride, d) lithium amide, e) magnesium amide, f) organolithium compound, g) organomagnesium compound, thereby forming a reaction mixture, wherein the stoichiometric molar equivalent ratio of polar complexing agent to alkoxide-forming reagent is from about 1:1 to less than 1:1, with lithium providing 1 equivalent and magnesium providing 2 equivalents; b) further adding the organolithium compound and / or the organomagnesium compound; c) the ratio of polar complexing agent to total metal equivalents ranges from about 1:1.05 to about 1:6, with lithium providing 1 equivalent and magnesium providing 2 equivalents; d) the molar ratio of lithium to magnesium is from about 10,000:1 to about 1.0:6.0, or the catalyst consists solely of lithium metal; e) further reducing the reaction product formed with hydrogen to form said hydrocarbon soluble salt-like hydride catalyst or reagent.

46. 46. ​​The method of any of claims 38, 42, 44, or 45 for forming the hydrocarbon soluble catalyst or reagent composition, the method further comprising providing a styrenic monomer to form poly(styryl)magnesium and / or poly(styryl)lithium and / or anionic poly(styryl) compounds which are then reduced by contact with molecular hydrogen to form the soluble salt-like hydrides, wherein the molar ratio of styrenic monomer to total metal is from about 1:10 to about 20:

1.

47. 46. ​​The method of any of claims 38, 42, 44, or 45 for forming the hydrocarbon soluble catalyst or reagent composition, the method further comprising providing a styrenic monomer to form a transient 1-phenylhexylmagnesium compound and / or a poly(styryl)magnesium compound which is further reduced with molecular hydrogen to form the soluble salt-like hydride, wherein the molar ratio of styrenic monomer to magnesium is from about 1:5 to about 20:

1.

48. 48. The method of claim 46 or 47, wherein the styrenic monomer is styrene.

49. Initiated with a salt-like hydride catalyst, the polymer structure is: 【Chemistry 3】 1. An anionic chain transferred polystyrene distribution composition having a polymer microstructure of greater than 97 wt % head-to-tail microstructure as shown in Figure 1, wherein said polystyrene composition has a chain length distribution(s) as by-product distribution(s) resulting from a) chain isomerization and b) cleavage polymerization steps in an amount of less than 3% to below the detection limit, said microstructure and purity of said chain length distribution being determined by gas chromatography analysis of the lowest molecular weight chains obtained from said hydrogen mediated salt analog hydride initiated polystyrene distribution of said polymer structure n=0 to n=4.

50. 50. The anionic chain transfer polystyrene distribution composition of claim 49, wherein the molecular weight distribution of the chain length distribution is: M n ranges from about 315 to about 934 daltons, and M w ranges from about 392 to about 1705 daltons, and M z ranges from about 512 to about 2930 Daltons. ,PD n ranges from about 1.24 to about 1.82 with a standard deviation of about 156 to in the range of about 849 Daltons and an asymmetry in the range of about 1.40 to about 3.

00.

51. Hydrogen-Mediated Anionic Polymerization of Styrene (HMAPS) polystyrene comprising greater than 99 wt % of the following polymer structure: 【Chemistry 4】 and having a polymer chain length distribution in which less than 1.0% of the polymer chains in said polymer microstructure have one or more quaternary carbons, and containing less than 1.0% to below the detection limit of said chain length distribution(s) as by-product distribution(s) resulting from a cleavage polymerization process, said microstructure and purity of said chain length distribution being determined by gas chromatography analysis of the lowest molecular weight chains obtained from said HMAPS distribution from n=0 to n=2 as follows:

52. 52. The HMAPS polymer of claim 51, wherein the molecular weight distribution of the HMAPS composition as measured by GPC (UV detector) analysis of the chain length distribution is: M n About 400 to about 800 Daltons, and M w ranges from about 600 to about 1200 Daltons. ,PD n ranges from about 1.35 to about 1.75, with a standard deviation of about 270 to about 550 Dalton range, M w 10% higher is less than about 3,300 daltons , the polymer.

53. 52. The HMAPS polymer of claim 51, wherein the molecular weight distribution of the HMAPS composition as measured by GPC (UV detector) analysis of the chain length distribution is: M n About 400 to about 800 Daltons, and M w ranges from about 600 to about 1200 Daltons. Ri, M z is in the range of about 750 to about 1500 Daltons, and PD n ranges from about 1.35 to about 1.75, the standard deviation ranges from about 270 to about 550 Daltons, the asymmetry ranges from about 1.60 to about 2.2, and M w 10% higher is less than about 2400 Daltons The polymer,

54. (i) molecular hydrogen, (ii) an organolithium compound and / or an organomagnesium compound, (iii) optionally a poly-tertiary amine compound, (iv) a polar complexing agent selected from a tertiary amino alcohol compound, a tertiary amino ether alcohol, an ether alcohol, or a combination thereof, (v) optionally an alkali metal or metal alloy and / or a solid salt-like hydride, (vi) optionally a pK of at least one C—H covalent bond. a is the pK of toluene a 2.75 pK higher than that of a From the units, the pK of toluene a -4.30 pK a Within the range below the unit (viii) from an aromatic hydrocarbon in the range 2 From p K a The aromatic hydrocarbon may be the same or different from the aromatic hydrocarbon, and the aromatic hydrocarbon may have a high molecular weight. A catalyst or reagent composition.

55. 55. The catalyst or reagent composition of claim 24 or 54, wherein the molecular hydrogen is isotopically enriched with a) deuterium, or b) tritium to form a deuteride or tritide.

56. 56. The catalyst or reagent composition of claim 55, wherein the hydride, deuteride, or tritide formed is a polyhydride, polydeuteride, or polytritide.

57. (i) molecular hydrogen, (ii) organolithium compounds and / or organomagnesium compounds, (iii) optionally poly-tertiary amine compounds, (iv) polar complexing agents selected from tertiary amino alcohol compounds, tertiary amino ether alcohols, ether alcohols, or combinations thereof, (v) optionally alkali metals or metal alloys and / or solid salts similar to hydrogen. (vi) optionally, a pK of at least one C—H covalent bond; a is the pK of toluene a 2.75 pK higher than that of a From the units, the pK of toluene a -4.30 pK a (vii) H from an aromatic hydrocarbon within the range below the unit 2 pK a High 1. A method for forming a brominated polystyrene composition formed by a process involving aromatic electrophilic bromination of a polystyrene composition formed solely from polystyrene by carrying out a hydrogen mediated, salt-like hydride initiated polymerization, characterized in that styrene is provided to a reaction medium containing a soluble salt-like hydride LOXSH catalyst formed in a hydrocarbon solvent which may be the same as or different from said aromatic hydrocarbon, quenching and washing said polymerization reaction mixture to remove catalyst components, removing solvent and dimers, and then brominating.